3D Bioprinting of Melanoma Cells with commercially available Bio Inks - Schmidt, Sarah; Schmid, Rafael; Arkudas, Andreas; Kengelbach-Weigand, Annika; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

3D hydrogel-based microcapsules as an in vitro model to study tumorigenicity, cell migration and drug resistance. - Ertekin, Özlem; Monavari, Mahshid; Krüger, René; Fuentes Chandia, Miguel Angel; Parma, Beatrice; Letort, Gaelle; Tripal, Philipp; Boccaccini, Aldo R.; Boßerhoff, Anja Katrin; Ceppi, Paolo; Kappelmann-Fenzl, Melanie; Leal-Egaña, Aldo (Acta Biomaterialia, 2022)
In this work, we analyzed the reliability of alginate-gelatin microcapsules as artificial tumor model. These tumor-like scaffolds are characterized by their composition and stiffness (∼25 kPa), and their capability to restrict -but not hinder- cell migration, proliferation and release from confinement. Hydrogel-based microcapsules were initially utilized to detect differences in mechano-sensitivity between MCF7 and MDA-MB-231 breast cancer cells, and the endothelial cell line EA.hy926. Additionally, we used RNA-seq and transcriptomic methods to determine how the culture strategy (i.e. 2D v/s 3D) may pre-set the expression of genes involved in multidrug resistance, being then validated by performing cytotoxicological tests and assays of cell morphology. Our results show that both breast cancer cells can generate elongated multicellular spheroids inside the microcapsules, prior being released (mimicking intravasation stages), a behavior which was not observed in endothelial cells. Further, we demonstrate that cells isolated from 3D scaffolds show resistance to cisplatin, a process which seems to be strongly influenced by mechanical stress, instead of hypoxia. We finally discuss the role played by aneuploidy in malignancy and resistance to anticancer drugs, based on the increased number of polynucleated cells found within these microcapsules. Overall, our outcomes demonstrate that alginate-gelatin microcapsules represent a simple, yet very accurate tumor-like model, enabling us to mimic the most relevant malignant hints described in vivo, suggesting that confinement and mechanical stress need to be considered when studying pathogenicity and drug resistance of cancer cells in vitro. STATEMENT OF SIGNIFICANCE: In this work, we analyzed the reliability of alginate-gelatin microcapsules as an artificial tumor model. These scaffolds are characterized by their composition, elastic properties, and their ability to restrict cell migration, proliferation, and release from confinement. Our results demonstrate four novel outcomes: (i) studying cell migration and proliferation in 3D enabled discrimination between malignant and non-pathogenic cells, (ii) studying the cell morphology of cancer aggregates entrapped in alginate-gelatin microcapsules enabled determination of malignancy degree in vitro, (iii) determination that confinement and mechanical stress, instead of hypoxia, are required to generate clones resistant to anticancer drugs (i.e. cisplatin), and (iv) evidence that resistance to anticancer drugs could be due to the presence of polynucleated cells localized inside polymer-based artificial tumors.

3D Spheroids Versus 3D Tumor-Like Microcapsules: Confinement and Mechanical Stress May Lead to the Expression of Malignant Responses in Cancer Cells - Fuentes-Chandía, Miguel; Vierling, Andreas; Kappelmann-Fenzl, Melanie; Monavari, Mahshid; Letort, Gaelle; Höne, Lucas; Parma, Beatrice; Antara, Sharmin Khan; Ertekin, Özlem; Palmisano, Ralf; Dong, Meng; Böpple, Kathrin; et al. (Advanced Biology, 2021)
As 2D surfaces fail to resemble the tumoral milieu, current discussions are focused on which 3D cell culture strategy may better lead the cells to express in vitro most of the malignant hints described in vivo. In this study, this question is assessed by analyzing the full genetic profile of MCF7 cells cultured either as 3D spheroids-considered as “gold standard” for in vitro cancer research- or immobilized in 3D tumor-like microcapsules, by RNA-Seq and transcriptomic methods, allowing to discriminate at big-data scale, which in vitro strategy can better resemble most of the malignant features described in neoplastic diseases. The results clearly show that mechanical stress, rather than 3D morphology only, stimulates most of the biological processes involved in cancer pathogenicity, such as cytoskeletal organization, migration, and stemness. Furthermore, cells entrapped in hydrogel-based scaffolds are likely expressing other physiological hints described in malignancy, such as the upregulated expression of metalloproteinases or the resistance to anticancer drugs, among others. According to the knowledge, this study represents the first attempt to answer which 3D experimental system can better mimic the neoplastic architecture in vitro, emphasizing the relevance of confinement in cancer pathogenicity, which can be easily achieved by using hydrogel-based matrices.
CRIS-Team Scopus Importer:2021-05-28
Keywords: 3D cancer models; 3D cell culture; biomaterials for cancer research; solid stress; tumor-like microcapsules

Acidic tumor microenvironment in human melanoma - Böhme, Ines; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2016)
One characteristic of solid tumors such as malignant melanoma is the acidification of the tumor microenvironment. The deregulation of cancer cell metabolism is considered a main cause of extracellular acidosis. Here, cancer cells utilize aerobic glycolysis instead of oxidative phosphorylation even under normoxic conditions, as originally described by Otto Warburg. These metabolic alterations cause enhanced acid production, especially of lactate and carbon dioxide (CO2 ). The extensive production of acidic metabolites and the enhanced acid export to the extracellular space cause a consistent acidification of the tumor microenvironment, thus promoting the formation of an acid-resistant tumor cell population with increased invasive and metastatic potential. As melanoma is one of the deadliest and most metastatic forms of cancer, understanding the effects of this extracellular acidosis on human melanoma cells with distinct metastatic properties is important. The aim of this review was to summarize recent studies of the acidification of the tumor microenvironment, focusing on the specific effects of the acidic milieu on melanoma cells and to give a short overview of therapeutic approaches.
EVALuna2:4736

Acidification is an essential process of cold atmospheric plasma and promotes the anti-cancer effect on malignant melanoma cells - Schneider, Christin; Gebhardt, Lisa; Arndt, Stephanie; Karrer, Sigrid; Zimmermann, Julia L.; Fischer, Michael; Boßerhoff, Anja Katrin (Cancers, 2019)
(1) Background: Cold atmospheric plasma (CAP) is ionized gas near room temperature. The anti-cancer effects of CAP were confirmed for several cancer types and were attributed to CAP-induced reactive species. However, the mode of action of CAP is still not well understood. (2) Methods: Changes in cytoplasmic Ca2+ level after CAP treatment of malignant melanoma cells were analyzed via the intracellular Ca2+ indicator fura-2 AM. CAP-produced reactive species were determined by fluorescence spectroscopic and protein nitration by Western Blot analysis. (3) Results: CAP caused a strong acidification of water and solutions that were buffered with the so-called Good buffers, while phosphate-buffered solutions with higher buffer capacity showed minor pH reductions. The CAP-induced Ca2+ influx in melanoma cells was stronger in acidic pH than in physiological conditions. NO formation that is induced by CAP was dose-and pH-dependent and CAP-treated solutions only caused protein nitration in cells under acidic conditions. (4) Conclusions: We describe the impact of CAP-induced acidification on the anti-cancer effects of CAP. A synergistic effect of CAP-induced ROS, RNS, and acidic conditions affected the intracellular Ca2+ level of melanoma cells. As the microenvironment of tumors is often acidic, further acidification might be one reason for the specific anti-cancer effects of CAP.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Acidification; Calcium signaling; Cold atmospheric plasma; Malignant melanoma; Nitration

Acidified nitrite contributes to the antitumor effect of cold atmospheric plasma on melanoma cells - Zimmermann, Tom; Gebhardt, Lisa; Kreiß, Lucas; Schneider, Christin; Arndt, Stephanie; Karrer, Sigrid; Friedrich, Oliver; Fischer, Michael Jochen Marco; Boßerhoff, Anja Katrin (International Journal of Molecular Sciences, 2021)
Cold atmospheric plasma (CAP) is partially ionized gas near room temperature with previously reported antitumor effects. Despite extensive research and growing interest in this technol-ogy, active components and molecular mechanisms of CAP are not fully understood to date. We used Raman spectroscopy and colorimetric assays to determine elevated nitrite and nitrate levels after treatment with a MiniFlatPlaster CAP device. Previously, we demonstrated CAP-induced acidification. Cellular effects of nitrite and strong extracellular acidification were assessed using live-cell imaging of intracellular Ca2+ levels, cell viability analysis as well as quantification of p21 and DNA damage. We further characterized these observations by analyzing established molecular effects of CAP treatment. A synergistic effect of nitrite and acidification was found, leading to strong cytotoxicity in melanoma cells. Interestingly, protein nitration and membrane damage were absent after treatment with acidified nitrite, thereby challenging their contribution to CAP-induced cyto-toxicity. Further, phosphorylation of ERK1/2 was increased after treatment with both acidified ni-trite and indirect CAP. This study characterizes the impact of acidified nitrite on melanoma cells and supports the importance of RNS during CAP treatment. Further, it defines and evaluates im-portant molecular mechanisms that are involved in the cancer cell response to CAP.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Acidification; Acidified nitrite; Cold atmospheric plasma; Malignant melanoma; Membrane damage; Nitration; Nitrite

A comprehensive expression analysis of the MIA gene family in malignancies: MIA gene family members are novel, useful markers of esophageal, lung, and cervical squamous cell carcinoma - Sasahira, Tomonori; Kirita, Tadaaki; Nishiguchi, Yukiko; Kurihara, Miyako; Nakashima, Chie; Boßerhoff, Anja Katrin; Kuniyasu, Hiroki (Oncotarget, 2016)
Melanoma inhibitory activity (MIA) gene family members include MIA, MIA2, and Transport and Golgi organization protein 1 (TANGO). Although MIA gene family members have several tumor-related functions, their detailed roles in malignancies remain poorly elucidated. In this study, 477 tumor specimens were subjected to immunohistochemical screening to evaluate MIA gene family expression. For a validation analysis, we also examined the association between MIA gene family expression and clinicopathological factors in 66 cases of esophageal cancer, 145 cases of lung cancer, and 126 cases of cervical cancer. The frequency of MIA gene family expression was higher among squamous cell carcinomas than among other tumor types subjected to screening. In the validation analysis, MIA gene family staining was observed frequently in esophageal and lung cancers associated with nodal and/or distant metastasis. In cervical cancers, MIA and TANGO immunostaining also correlated with tumor progression and metastasis. Furthermore, MIA2 expression levels in invasive cervical cancer were upregulated relative to those in cervical intraepithelial neoplasia 3. A disease-free survival analysis revealed that MIA-, MIA2, or TANGO-positive patients had a significantly shorter disease-free survival than did those patients who were negative. Our results suggest that MIA, MIA2, and TANGO may be useful diagnostic and therapeutic molecular targets in human malignancies.
EVALuna2:4728

Activating enhancer binding protein 2 epsilon (AP-2?)-deficient mice exhibit increased matrix metalloproteinase 13 expression and progressive osteoarthritis development - Niebler, Stephan; Schubert, Thomas; Hunziker, Ernst B.; Boßerhoff, Anja Katrin (Arthritis Research & Therapy, 2015)
The transcription factor activating enhancer binding protein 2 epsilon (AP-2?) was recently shown to be expressed during chondrogenesis as well as in articular chondrocytes of humans and mice. Furthermore, expression of AP-2? was found to be upregulated in affected cartilage of patients with osteoarthritis (OA). Despite these findings, adult mice deficient for AP-2? (Tfap2e(-/-)) do not exhibit an obviously abnormal cartilaginous phenotype. We therefore analyzed embryogenesis of Tfap2e(-/-) mice to elucidate potential transient abnormalities that provide information on the influence of AP-2? on skeletal development. In a second part, we aimed to define potential influences of AP-2? on articular cartilage function and gene expression, as well as on OA progression, in adult mice.Murine embryonic development was accessed via in situ hybridization, measurement of skeletal parameters and micromass differentiation of mesenchymal cells. To reveal discrepancies in articular cartilage of adult wild-type (WT) and Tfap2e(-/-) mice, light and electron microscopy, in vitro culture of cartilage explants, and quantification of gene expression via real-time PCR were performed. OA was induced via surgical destabilization of the medial meniscus in both genotypes, and disease progression was monitored on histological and molecular levels.Only minor differences between WT and embryos deficient for AP-2? were observed, suggesting that redundancy mechanisms effectively compensate for the loss of AP-2? during skeletal development. Surprisingly, though, we found matrix metalloproteinase 13 (Mmp13), a major mediator of cartilage destruction, to be significantly upregulated in articular cartilage of adult Tfap2e(-/-) mice. This finding was further confirmed by increased Mmp13 activity and extracellular matrix degradation in Tfap2e(-/-) cartilage explants. OA progression was significantly enhanced in the Tfap2e(-/-) mice, which provided evidence for in vivo relevance. This finding is most likely attributable to the increased basal Mmp13 expression level in Tfap2e(-/-) articular chondrocytes that results in a significantly higher total Mmp13 expression rate during OA as compared with the WT.We reveal a novel role of AP-2? in the regulation of gene expression in articular chondrocytes, as well as in OA development, through modulation of Mmp13 expression and activity.
EVALuna2:4711

A fully human anti-BMP6 antibody reduces the need for erythropoietin in rodent models of the anemia of chronic disease - Petzer, Verena; Tymoszuk, Piotr; Asshoff, Malte; Carvalho, Joana; Papworth, Jonathan; Deantonio, Cecilia; Bayliss, Luke; Wake, Matthew Stephen; Seifert, Markus; Brigo, Natascha; Valente de Souza, Lara; Hilbe, Richard; et al. (Blood, 2020)
Recombinant erythropoietin (EPO) and iron substitution are a standard of care for treatment of anemias associated with chronic inflammation, including anemia of chronic kidney disease. A black box warning for EPO therapy and concerns about negative side effects related to high-dose iron supplementation as well as the significant proportion of patients becoming EPO resistant over time explains the medical need to define novel strategies to ameliorate anemia of chronic disease (ACD). As hepcidin is central to the iron-restrictive phenotype in ACD, therapeutic approaches targeting hepcidin were recently developed. We herein report the therapeutic effects of a fully human anti-BMP6 antibody (KY1070) either as monotherapy or in combination with Darbepoetin alfa on iron metabolism and anemia resolution in 2 different, well-established, and clinically relevant rodent models of ACD. In addition to counteracting hepcidin-driven iron limitation for erythropoiesis, we found that the combination of KY1070 and recombinant human EPO improved the erythroid response compared with either monotherapy in a qualitative and quantitative manner. Consequently, the combination of KY1070 and Darbepoetin alfa resulted in an EPO-sparing effect. Moreover, we found that suppression of hepcidin via KY1070 modulates ferroportin expression on erythroid precursor cells, thereby lowering potentially toxic-free intracellular iron levels and by accelerating erythroid output as reflected by increased maturation of erythrocyte progenitors. In summary, we conclude that treatment of ACD, as a highly complex disease, becomes more effective by a multifactorial therapeutic approach upon mobilization of endogenous iron deposits and stimulation of erythropoiesis.
CRIS-Team Scopus Importer:2020-09-11

Alginate-Dialdehyde-Based Reporter Ink Enabling Online Detection of Matrix Metalloproteinase Activity of Encapsulated Cells - Gantert, Benedikt; Karakaya, Emine; Hofmann, Florian; Jungst, Tomasz; Meinel, Lorenz; Boßerhoff, Anja Katrin; Detsch, Rainer; Lühmann, Tessa (ACS Biomaterials Science and Engineering, 2025)
Biofabrication and three-dimensional (3D) bioprinting enable precise spatial arrangement of cells within biomaterial scaffolds. We developed an alginate-based and Förster resonance energy transfer (FRET)-responsive “turn-on” reporter ink platform to enable real-time monitoring of matrix metalloproteinase (MMP) activity. Three distinct MMP-cleavable turn-on peptide reporters were synthesized and characterized for their cell-specific cleavage profiles using recombinant MMPs, cell-derived media, and different cell cultures (NIH3T3, HEK293, and MelHo). All turn-on reporters were covalently and site-specifically incorporated into alginate dialdehyde (ADA) to yield an MMP reporter ink. The ADA reporter ink with an MMP 13 turn-on reporter was responsive to all tested cell types over time within the cast bulk constructs. The ADA reporter ink material blended with gelatin had comparable print resolution and structural fidelity as observed for ADA. The extrusion-based bioprinted MelHo cell grids, measuring 2 × 2 cm2 and containing 1 × 106 cells/mL, exhibited MMP activity responses comparable to those of the casted reporter ink system, with a 3-fold increase observed at 24 h. This study introduces a versatile, FRET-based alginate bioink platform for the real-time monitoring of MMP activities, expanding the toolkit to understand cellular performance in bioprinted 3D constructs.
CRIS-Team Scopus Importer:2025-03-28
Keywords: biofabrication; bioprinting; FRET peptide sensor; hydrogel; MMP; turn-on reporter

Alpha-Synuclein and Its Role in Melanocytes - Rachinger, Nicole; Mittag, Nora; Böhme-Schäfer, Ines; Xiang, Wei; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2022)
Pigmentation is an important process in skin physiology and skin diseases and presumably also plays a role in Parkinson’s disease (PD). In PD, alpha-Synuclein (aSyn) has been shown to be involved in the pigmentation of neurons. The presynaptic protein is intensively investigated for its pathological role in PD, but its physiological function remains unknown. We hypothesized that aSyn is both involved in melanocytic differentiation and melanosome trafficking processes. We detected a strong expression of aSyn in human epidermal melanocytes (NHEMs) and observed its regulation in melanocytic differentiation via the microphthalmia-associated transcription factor (MITF), a central regulator of differentiation. Moreover, we investigated its role in pigmentation by performing siRNA experiments but found no effect on the total melanin content. We discovered a localization of aSyn to melanosomes, and further analysis of aSyn knockdown revealed an important role in melanocytic morphology and a reduction in melanosome release. Additionally, we found a reduction of transferred melanosomes in co-culture experiments of melanocytes and keratinocytes but no complete inhibition of melanosome transmission. In summary, this study highlights a novel physiological role of aSyn in melanocytic morphology and its so far unknown function in the pigment secretion in melanocytes.
CRIS-Team Scopus Importer:2022-07-15
Keywords: alpha-Synuclein; melanocytes; melanosomes; pigment transport; pigmentation

Alternative Wnt-signaling axis leads to a break of oncogene-induced senescence - Kluge, Viola; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Zimmermann, Tom; Pommer, Michaela; Kuphal, Silke; Boßerhoff, Anja Katrin (Cell Death & Disease, 2024)
Oncogene-induced senescence (OIS) is an important process that suppresses tumor development, but the molecular mechanisms of OIS are still under investigation. It is known that BRAFV600E-mutated melanocytes can overcome OIS and develop melanoma, but the underlying mechanism is largely unknown. Using an established OIS model of primary melanocytes transduced with BRAFV600E, YAP activity was shown to be induced in OIS as well as in melanoma cells compared to that in normal epidermal melanocytes. This led to the assumption that YAP activation itself is not a factor involved in the disruption of OIS. However, its role and interaction partners potentially change. As Wnt molecules are known to be important in melanoma progression, these molecules were the focus of subsequent studies. Interestingly, activation of Wnt signaling using AMBMP resulted in a disruption of OIS in BRAFV600E-transduced melanocytes. Furthermore, depletion of Wnt6, Wnt10b or β-catenin expression in melanoma cells resulted in the induction of senescence. Given that melanoma cells do not exhibit canonical Wnt/β-catenin activity, alternative β-catenin signaling pathways may disrupt OIS. Here, we discovered that β-catenin is an interaction partner of YAP on DNA in melanoma cells. Furthermore, the β-catenin–YAP interaction changed the gene expression pattern from senescence-stabilizing genes to tumor-supportive genes. This switch is caused by transcriptional coactivation via the LEF1/TEAD interaction. The target genes with binding sites for LEF1 and TEAD are involved in rRNA processing and are associated with poor prognosis in melanoma patients. This study revealed that an alternative YAP-Wnt signaling axis is an essential molecular mechanism leading to OIS disruption in melanocytes. (Figure presented.).
CRIS-Team Scopus Importer:2024-03-01

Amphiregulin Regulates Melanocytic Senescence - Pommer, Michaela; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2021)
Oncogene-induced senescence (OIS) is a decisive process to suppress tumor development, but the molecular details of OIS are still under investigation. Using an established OIS model of primary melanocytes transduced with BRAF V600E and compared to control cells, amphiregulin (AREG) was shown to be induced. In addition, AREG expression was observed in nevi, which by definition, are senescent cell clusters, compared to melanocytes. Interestingly, treatment of melanocytes with recombinant AREG did induce senescence. This led to the assumption that extracellular AREG has an important function in this process. Inhibition of the epidermal growth factor receptor (EGFR) using Gefitinib identified AREG as one of EGFR ligands responsible for senescence. Furthermore, depletion of AREG expression in senescent BRAF V600E melanocytes resulted in a significant reduction of senescent melanocytes. This study reveals AREG as an essential molecular component of signaling pathways leading to senescence in melanocytes.
CRIS-Team Scopus Importer:2021-03-05
Keywords: amphiregulin; AREG; normal human primary melanocytes; OIS; oncogene induced senescence

An AGO2 variant affects the function of miRNAs and influences the viability of melanoma cells - Linck-Paulus, L.; Kappelmann-Fenzl, M.; Meister, G.; Boßerhoff, Anja Katrin (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

An alginate-cellulose based bioink mimics the viscoelastic features of the melanoma microenvironment and its influence on cell cycle and invasion - Eckert, Carolin; Schmidt, Sonja; Faber, Jessica; Detsch, Rainer; Vielreicher, Martin; Lamberger, Zan; Stahlhut, Philipp; Sandor, Evelin; Karimi, Tannaz; Schmid, Rafael; Arkudas, Andreas; Friedrich, Oliver; et al. (Bioprinting, 2025)
Melanoma, an aggressive tumor from melanocytes, poses challenges despite recent therapeutic advances. Understanding molecular changes in its progression is crucial. Melanoma cells develop in the epidermis, then start spreading into the dermis– the first step of the invasive, progressive process. The dermis is composed of elastic (proteoglycans) and stabilizing (collagens) molecules. To overcome limitations of 2D-cell culture models, we established a 3D-bio-printed dermis model for the analysis of tumor cell features using a blend of alginate and microfibrillar cellulose. Testing different compositions in extrusion-based bioprinting confirmed good printability with high cell viability for AlgCell ink. Mechanical and optical analyses revealed dermis-like viscoelasticity and a pore size allowing nutrition supply and cell movement. We evaluated survival and proliferation of the cells and printed tumor spheroids and determined different migratory behavior comparing alginate to AlgCell. Interestingly, multiphoton microscopy revealed random cellulose fiber distribution around the spheroids after 7 days of cultivation with individual single cells, which had left the tumor spheroid and invaded into the microenvironment. Traditional 2D-models inadequately capture 3D mechanisms like invasion and migration. Our 3D-tumor model mimics the microenvironment, enabling in-depth analyses akin to in vivo conditions. This promises insights into tumor progression and testing of therapeutic interventions.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Bioink; Cell migration; Melanoma; Spheroid printing

Analysis of Glucose Concentration in Melanoma cells under physiological and nutrient-deficient Conditions - Herr, Felix; Schmidt, Sarah; Böhme, Ines; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

ANALYSIS OF MOLECULAR MECHANISMS OF 5-FLUOROURACIL INDUCED STEATOSIS AND INFLAMMATION IN VITRO AND IN MICE - Sommer, J.; Mahli, A.; Freese, K.; Thasler, W.; Kuecuekoktay, F.; Boßerhoff, Anja Katrin; Mueller, M.; Hellerbrand, C. (2016)
EVALuna2:33709

Analysis of molecular mechanisms of 5-fluorouracil-induced steatosis and inflammation in vitro and in mice - Sommer, Judith; Mahli, Abdo; Freese, Kim; Schiergens, Tobias S.; Kuecuekoktay, Fulya Suzan; Teufel, Andreas; Thasler, Wolfgang E.; Mueller, Martina; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Oncotarget, 2017)
Chemotherapy-associated steatohepatitis is attracting increasing attention because it heralds an increased risk of morbidity and mortality in patients undergoing surgery because of liver metastases. The aim of this study was to develop in vitro and in vivo models to analyze the pathogenesis of 5-fluorouracil (5-FU)-induced steatohepatitis.Therefore, primary human hepatocytes and HepG2 hepatoma cells were incubated with 5-FU at non-toxic concentrations up to 24 h. Furthermore, hepatic tissue of C57BL/6N mice was analyzed 24 h after application of a single 5-FU dose (200 mg/kg body weight). In vitro, incubation with 5-FU induced a significant increase of hepatocellular triglyceride levels. This was paralleled by an impairment of mitochondrial function and a dose- and time-dependently increased expression of fatty acid acyl-CoA oxidase 1 (ACOX1), which catalyzes the initial step for peroxisomal ?-oxidation. The latter is known to generate reactive oxygen species, and consequently, expression of the antioxidant enzyme heme oxygenase 1 (HMOX1) was significantly upregulated in 5-FU-treated cells, indicative for oxidative stress. Furthermore, 5-FU significantly induced c-Jun N-terminal kinase (JNK) activation and the expression of pro-inflammatory genes IL-8 and ICAM-1. Also in vivo, 5-FU significantly induced hepatic ACOX1 and HMOX1 expression as well as JNK-activation, pro-inflammatory gene expression and immune cell infiltration. In summary, we identified molecular mechanisms by which 5-FU induces hepatocellular lipid accumulation and inflammation. Our newly developed models can be used to gain further insight into the pathogenesis of 5-FU-induced steatohepatitis and to develop therapeutic strategies to inhibit its development and progression.
EVALuna2:4753

A New Printable Alginate/Hyaluronic Acid/Gelatin Hydrogel Suitable for Biofabrication of In Vitro and In Vivo Metastatic Melanoma Models - Schmid, Rafael; Schmidt, Sonja; Detsch, Rainer; Horder, Hannes; Blunk, Torsten; Schrüfer, Stefan; Schubert, Dirk W.; Fischer, Lena; Thievessen, Ingo; Heltmann-Meyer, Stefanie; Steiner, Dominik; Schneidereit, Dominik; et al. (Advanced Functional Materials, 2022)
Two-dimensional (2D) cancer models have been the standard for drug development over the past few years, but they frequently do not resemble in vivo properties adequately. 3D models are superior in many aspects and are, therefore, more similar to human pathophysiology. Over the past years, the emerging field of biofabrication has made significant advances, resulting in even more sophisticated 3D models. With this study, a hydrogel is created for biofabrication that is suitable for mimicking the tumor microenvironment in vitro and is further tested as a new vascularized melanoma model in vivo. The alginate/hyaluronic acid/gelatin bioink shows good shape-fidelity, high cell survival rates, and enables successful cultivation of melanoma cells and adipose-derived stem cells as well as cell differentiation in vitro. In vivo, in the arteriovenous loop model, it proves to be a unique method to study melanoma progression, tumor vascularization, and ultimately and reliably metastases in an isolated and controlled environment. These results show that this 3D model is very application-oriented for molecular research and therapy development.
CRIS-Team Scopus Importer:2021-10-22
Keywords: bioinks; metastasis; stem cells; tissue engineering; tumors

Annexin A5 is involved in migration and invasion of oral carcinoma - Wehder, Liane; Arndt, Stephanie; Murzik, Ulrike; Kob, Robert; Von Eggeling, Ferdinand; Melle, Christian; Bosserhoff, Anja Katrin (Cell Cycle, 2009)
Annexin A5 is a Ca(2+)-binding protein which is involved in membrane organization and dynamics. As recent data suggest a role of annexin A5 in cancer we aimed to gain more insight into the biological function of endogenous annexin A5 and assessed its possible influence on proliferation and invasion capacity. We downregulated annexin A5 by RNA interference in HaCaT keratinocytes, squamous carcinoma cell line A431 as well as in a primary cell culture of a human oral carcinoma. Hereby, we detected reduced migration and invasion capacity of HaCaT cells which was even stronger in the oral carcinoma. To determine target genes of annexin A5 we used a metastasis specific microarray. Thereby, genes implicated in cell motility including S100A4, TIMP-3 and RHOC were observed to be regulated. These deregulations were confirmed by RT-PCR or western blots, respectively. These observations suggest that the invasion capacity, a main characteristic of tumors, is at least partially regulated by annexin A5 in oral carcinoma.
Keywords: annexin A5; migration; invasion; proliferation; metastasis; oral carcinoma

A novel splice variant of Argonaut 2 affects microRNA target genes and cell viability of melanoma cells - Linck-Paulus, Lisa; Horn, Angelika; Matthies, Alexander Oliver; Fischer, S.; Meister, G.; Sticht, Heinrich; Kappelmann-Fenzl, M.; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

A previously unknown Argonaute 2 variant positively modulates the viability of melanoma cells - Linck-Paulus, Lisa; Meißgeier, Tina; Pieger, Katharina; Horn, Anselm; Matthies, Alexander Oliver; Fischer, Stefan; Meister, Gunter; Sticht, Heinrich; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin (Cellular and Molecular Life Sciences, 2022)
In malignant melanoma, a highly aggressive form of skin cancer, many microRNAs are aberrantly expressed contributing to tumorigenesis and progression. Further, deregulation of microRNA processing enzymes, like the miRNA-binding protein Argonaute 2, significantly impacts microRNA function. This study characterizes a novel splice variant of Argonaut 2, AGO2-ex1/3. AGO2-ex1/3 is substantially expressed in different melanoma cell lines and patient-derived tissue samples. It is a mature mRNA, which is translated into an N-terminally truncated Argonaute 2 protein form. Molecular dynamics simulations show that the PAZ, MID, and PIWI domain largely retain their structure in AGO2-ex1/3 and that the truncation of the N-terminus leads to an increased interdomain flexibility. Expression of AGO2-ex1/3 provides a survival advantage for melanoma cells while the knockdown causes significantly reduced proliferation and increases apoptosis. RNA-sequencing revealed that in cells lacking AGO2-ex1/3 expression many miRNA target genes are deregulated, implicating a considerable role of AGO2-ex1/3 for miRNA function. This study inaugurates insights into an important role of a so far unknown splice variant of Argonaute 2 for the miRNA pathway as well as the mechanisms which drive growth and survival of melanoma cells. This knowledge provides the basis for potential new promising therapeutic targets focusing on small RNA-mediated gene regulation in melanoma.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Alternative splicing; Argonaute 2; Melanoma; miRNAs

Argonaute Family Protein Expression in Normal Tissue and Cancer Entities - Voeller, Daniel; Linck, Lisa; Bruckmann, Astrid; Hauptmann, Judith; Deutzmann, Rainer; Meister, Gunter; Boßerhoff, Anja Katrin (PLoS ONE, 2016)
The members of the Argonaute (AGO) protein family are key players in miRNA-guided gene silencing. They enable the interaction between small RNAs and their respective target mRNA(s) and support the catalytic destruction of the gene transcript or recruit additional proteins for downstream gene silencing. The human AGO family consists of four AGO proteins (AGO1-AGO4), but only AGO2 harbors nuclease activity. In this study, we characterized the expression of the four AGO proteins in cancer cell lines and normal tissues with a new mass spectrometry approach called AGO-APP (AGO Affinity Purification by Peptides). In all analyzed normal tissues, AGO1 and AGO2 were most prominent, but marked tissue-specific differences were identified. Furthermore, considerable changes during development were observed by comparing fetal and adult tissues. We also identified decreased overall AGO expression in melanoma derived cell lines compared to other tumor cell lines and normal tissues, with the largest differences in AGO2 expression. The experiments described in this study suggest that reduced amounts of AGO proteins, as key players in miRNA processing, have impact on several cellular processes. Deregulated miRNA expression has been attributed to chromosomal aberrations, promoter regulation and it is known to have a major impact on tumor development and progression. Our findings will further increase our basic understanding of the molecular basis of miRNA processing and its relevance for disease.
EVALuna2:4734

A vascularized in vivo melanoma model suitable for metastasis research of different tumor stages using fundamentally different bioinks - Schmid, Rafael; Schmidt, Sonja; Schrüfer, Stefan; Schubert, Dirk W.; Heltmann-Meyer, Stefanie; Schicht, Martin; Paulsen, Friedrich; Horch, Raymund E.; Boßerhoff, Anja Katrin; Kengelbach-Weigand, Annika; Arkudas, Andreas (Materials Today Bio, 2024)
Although 2D cancer models have been the standard for drug development, they don't resemble in vivo properties adequately. 3D models can potentially overcome this. Bioprinting is a promising technique for more refined models to investigate central processes in tumor development such as proliferation, dormancy or metastasis. We aimed to analyze bioinks, which could mimic these different tumor stages in a cast vascularized arteriovenous loop melanoma model in vivo. It has the advantage to be a closed system with a defined microenvironment, supplied only with one vessel—ideal for metastasis research. Tested bioinks showed significant differences in composition, printability, stiffness and microscopic pore structure, which led to different tumor stages (Matrigel and Alg/HA/Gel for progression, Cellink Bioink for dormancy) and resulted in different primary tumor growth (Matrigel significantly higher than Cellink Bioink). Light-sheet fluorescence microscopy revealed differences in vascularization and hemorrhages with no additional vessels found in Cellink Bioink. Histologically, typical human melanoma with different stages was demonstrated. HMB-45-positive tumors in progression inks were infiltrated by macrophages (CD163), highly proliferative (Ki67) and metastatic (MITF/BRN2, ATX, MMP3). Stainings of lymph nodes revealed metastases even without significant primary tumor growth in Cellink Bioink. This model can be used to study tumor pathology and metastasis of different tumor stages and therapi
Keywords: Tissue engineering; Bioink; Melanoma; Tumor; Metastasis

BAP1 germline mutation in two first grade family members with uveal melanoma - Maerker, David A.; Zeschnigk, Michael; Nelles, Jasmin; Lohmann, Dietnnar R.; Worm, Karl; Krupar, Rosemarie; Jaegle, Herbert; Bosserhoff, Anja Katrin (British Journal of Ophthalmology, 2014)
Background Uveal melanoma (UM) is the most common primary cancer of the eye in adults. About half of the patients are at risk of developing metastatic disease resulting in a poor clinical prognosis. Metastatic progression is strongly associated with loss of one chromosome 3 in the tumour (monosomy 3). The tumour suppressor gene BAP1 was found to be recurrently mutated in UM with monosomy 3. Familial UM is rare and amounts to about 0.6-6% of all patients with melanoma. However, BAP1 germline mutations have been identified in rare hereditary tumour syndromes, including cases with UM. One may assume that UM may be part of these hereditary conditions with predisposition to malignant cancers. Methods The patients underwent complete ophthalmological workup and enucleation due to UM. Microsatellite analysis was performed to determine the chromosome 3 status of the tumours. Sanger sequencing of all coding exons of the BAP1 gene was performed in blood DNA of the patients. Results Here we report on two family members (mother and son) diagnosed with UM. In both patients, a cosegregating BAP1 germline mutation (c.299 T≥C) was found. The mutant BAP1 allele was retained in the tumour of the son showing monosomy 3. The son further developed urothelial carcinoma and liver metastasis, the mother was affected by the UM and cholangiocellular carcinoma. Conculsions We detected a cosegregating BAP1 germline mutation in two family members with UM. This suggests that, consistent with a classic tumour suppressor model, carriers of damaging mutations in BAP1 are predisposed to UM. However, as BAP1 germline mutations have been found to cause other cancer syndromes as well, there must be other factors that decide about the type of tumour emerging from BAP1 inactivation.
CRIS-Team Scopus Importer:2022-08-05

BMP6-induced modulation of the tumor micro-milieu - Stieglitz, David; Lamm, Susanne; Braig, Simone; Feuerer, Lena; Kuphal, Silke; Dietrich, Peter; Arndt, Stephanie; Echtenacher, Bernd; Hellerbrand, Claus; Karrer, Sigrid; Boßerhoff, Anja Katrin (Oncogene, 2019)
Melanoma is the deadliest form of skin cancer with rising incidence, creating a significant health problem. We discovered increased expression of bone morphogenetic protein 6 (BMP6) in melanoma cells and tissues, and observed that BMP6 deficiency caused significantly delayed tumor onset and decelerated tumor progression in a melanoma mouse model. Moreover, we determined that BMP6 inhibits dermal mast cell recruitment and found that mast cell-derived mediators significantly reduced melanoma growth in vitro. In line with this, mast cell deficiency accelerated tumor onset and progression in a melanoma mouse model. Analysis of human melanoma tissues revealed a strong negative correlation between melanoma proliferation and mast cell infiltration. This study elucidates a novel role of BMP6-induced modulation of the tumor microenvironment.
EVALuna2:106826

Bone Morphogenetic Protein 13 Has Protumorigenic Effects on Hepatocellular Carcinoma Cells In Vitro. - Kersten, Vanessa; Seitz, Tatjana; Sommer, Judith; Thasler, Wolfgang E.; Boßerhoff, Anja Katrin; Hellerbrand, Claus (International Journal of Molecular Sciences, 2023)
Activated hepatic stellate cells (HSCs) play a key role in hepatic fibrosis and, thus, build the "soil" for hepatocarcinogenesis. Furthermore, HSCs are known to promote the progression of hepatocellular carcinoma (HCC), but the molecular mechanisms are only incompletely understood. Recently, we newly described the expression of bone morphogenetic protein 13 (BMP13) by HSCs in fibrotic liver tissue. In addition, BMP13 has mostly been studied in the context of cartilage and bone repair, but not in liver disease or cancer. Thus, we aimed to analyze the expression and function of BMP13 in HCC. Expression analyses revealed high BMP13-expression in activated human HSCs, but not in human HCC-cell-lines. Furthermore, analysis of human HCC tissues showed a significant correlation between BMP13 and α-smooth muscle actin (α-SMA), and immunofluorescence staining confirmed the co-localization of BMP13 and α-SMA, indicating activated HSCs as the cellular source of BMP13 in HCC. Stimulation of HCC cells with recombinant BMP13 increased the expression of the inhibitors of differentiation 1 (ID1) and 2 (ID2), which are known targets of BMP-signaling and cell-cycle promotors. In line with this, BMP13-stimulation caused an induced SMAD 1/5/9 and extracellular signal-regulated kinase (ERK) phosphorylation, as well as reduced expression of cyclin-dependent kinase inhibitors 1A (CDKN1A) and 2A (CDKN2A). Furthermore, stimulation with recombinant BMP13 led to increased proliferation and colony size formation of HCC cells in clonogenicity assays. The protumorigenic effects of BMP13 on HCC cells were almost completely abrogated by the small molecule dorsomorphin 1 (DMH1), which selectively blocks the intracellular kinase domain of ALK2 and ALK3, indicating that BMP13 acts via these BMP type I receptors on HCC cells. In summary, this study newly identifies stroma-derived BMP13 as a potential new tumor promotor in HCC and indicates this secreted growth-factor as a possible novel therapeutic target in HCC.
EVALuna2:538506

Bone morphogenetic protein 13 in hepatic stellate cells and hepatic fibrosis - Peschl, Vanessa; Seitz, Tatjana; Sommer, Judith; Thasler, Wolfgang; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Journal of Cellular Biochemistry, 2022)
Hepatic fibrosis can be considered as a deregulated wound healing process in response to chronic liver injury. Bone morphogenetic protein 13 (BMP13) has been described to promote bone and tendon repair. In this study, we aimed to analyze the expression and function of BMP13 in hepatic fibrosis. We found increased BMP13 expression during the activation of hepatic stellate cells (HSCs), which is known as the key event of hepatic fibrosis. Fitting to this, BMP13 was elevated in murine models of hepatic fibrosis, and immunofluorescence staining showed colocalization of BMP13 and α-smooth muscle actin (α-SMA), a marker for activated HSC, in cirrhotic human liver tissue. BMP13 depletion in activated human HSC reduced the phosphorylation of smad1/5/9 and the expression of the transcription factor inhibitor of differentiation 1 (ID1), a known BMP target gene and profibrogenic factor. Furthermore, BMP13-depletion led to reduced proliferation and downregulation of collagen I α1 (COL1A1) and α-SMA, and, interestingly, also reduced phosphorylation of extracellular signal-regulated kinases (ERK). Conversely, stimulation with recombinant BMP13 induced the phosphorylation of smad1/5/9 and ERK, as well as the proliferation and the expression of ID1, COL1A1, and α-SMA in HSCs. These stimulatory effects were inhibited by dorsomorphin 1, a small-molecule inhibitor of the BMP-type I receptors activin receptor-like kinase-2 and -3, which are both expressed by HSC. In summary, these data indicate increased BMP13 expression in hepatic fibrosis as a profibrogenic factor. Thus, this soluble growth factor might have the potential as a new fibrosis marker and antifibrogenic therapeutic target in patients with chronic liver disease.
CRIS-Team Scopus Importer:2022-04-29
Keywords: BMP13; hepatic stellate cells; liver fibrosis

Bone Morphogenetic Protein-6 Inhibits Fibrogenesis in Scleroderma Offering Treatment Options for Fibrotic Skin Disease - Arndt, Stephanie; Karrer, Sigrid; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Journal of Investigative Dermatology, 2019)
BMP6 is known to be crucial for regulating embryonic skin development. This study assessed the role of BMP6 in dermal fibrosis. We detected that BMP6 is significantly increased in skin-derived fibroblasts of patients with localized scleroderma. Moreover, it was shown that BMP6 significantly impacts proliferation, migration, cytoskeletal organization, and collagen expression, as well as activity of the major pro-fibrogenic transcription factor AP-1 in dermal fibroblasts. The importance of BMP6 in dermal fibrosis was further confirmed in an in vivo model of dermal fibrosis in which BMP6-deficient mice showed significantly enhanced fibrosis compared with wild-type mice. Conversely, application of recombinant BMP6 significantly ameliorated dermal fibrosis in this preclinical bleomycin-induced sclerosis model, and herewith provided proof of concept for the successful treatment of this fibrotic skin disease.
CRIS-Team Scopus Importer:2019-05-17

Bone Morphogenetic Protein-8B Expression is Induced in Steatotic Hepatocytes and Promotes Hepatic Steatosis and Inflammation In Vitro - Mahli, Abdo; Seitz, Tatjana; Beckroege, Tobias; Freese, Kim; Thasler, Wolfgang Erwin; Benkert, Matthias; Dietrich, Peter; Weiskirchen, Ralf; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cells, 2019)
Non-alcoholic fatty liver disease (NAFLD) is considered to be the hepatic manifestation of the metabolic syndrome. The bone morphogenetic protein-8B (BMP8B) has been shown to be expressed in brown adipose tissues and the hypothalamus and to affect thermogenesis and susceptibility to diet-induced obesity. Here, we aimed to analyze BMP8B expression in NAFLD and to gain insight into BMP8B effects on pathophysiological steps of NAFLD progression. BMP8B mRNA and protein expression were dose-dependently induced in primary human hepatocytes in vitro upon incubation with fatty acids. Furthermore, hepatic BMP8B expression was significantly increased in a murine NAFLD model and in NAFLD patients compared with controls. Incubation with recombinant BMP8B further enhanced the fatty acid-induced cellular lipid accumulation as well as NFB activation and pro-inflammatory gene expression in hepatocytes, while siRNA-mediated BMP8B depletion ameliorated these fatty acid-induced effects. Analysis of the expression of key factors of hepatocellular lipid transport and metabolisms indicated that BMP8B effects on fatty acid uptake as well as de novo lipogenesis contributed to hepatocellular accumulation of fatty acids leading to increased storage in the form of triglycerides and enhanced combustion by beta oxidation. In conclusion, our data indicate that BMP8B enhances different pathophysiological steps of NAFLD progression and suggest BMP8B as a promising prognostic marker and therapeutic target for NAFLD and, potentially, also for other chronic liver diseases.
CRIS-Team WoS Importer:2019-06-28

Brief communication: Pitfalls in immunohistochemistry - A recent example - Riechers, Alexander; Bosserhoff, Anja Katrin (International Journal of Clinical and Experimental Pathology, 2012)
Immunohistochemistry is an important and valuable technique in many fields of research, although several common pitfalls can lead to wrong or misinterpreted results. A recently published study [1] claims that the protein MIA (melanoma inhibitory activity) is expressed in Purkinje cells in the cerebellum. Careful re-analysis resulted in negative results. Due to these results of our group we feel that this analysis could serve as example for the potential problems in immunohistochemistry caused by the combination of an unspecific antibody and the omission of evaluating control tissue samples.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Antibody; CD-RAP; Immunohistochemistry; Mia; Specificity

BRN2 is a transcriptional repressor of CDH13 (T-cadherin) in melanoma cells - Ellmann, Lisa; Joshi, Manjunath B.; Resink, Therese J.; Bosserhoff, Anja K.; Kuphal, Silke (Laboratory Investigation, 2012)
T-cadherin (cadherin 13, H-cadherin, gene name CDH13) has been proposed to act as a tumor-suppressor gene as its expression is significantly diminished in several types of carcinomas, including melanomas. Allelic loss and promoter hypermethylation have been proposed as mechanisms for silencing of CDH13. However, they do not account for loss of T-cadherin expression in all carcinomas, and other genetic or epigenetic alterations can be presumed. The present study investigated transcriptional regulation of CDH13 in melanoma. Bioinformatical analysis pointed to the presence of known BRN2 (also known as POU3F2 and N-Oct-3)-binding motifs in the CDH13 promoter sequence. We found an inverse correlation between BRN2 and T-cadherin protein and transcript expression. Reporter gene analysis and electrophoretic mobility shift assays in melanoma cells demonstrated that CDH13 is a direct target of BRN2 and that BRN2 is a functional transcriptional repressor of CDH13 promoter activity. The regulatory binding element of BRN2 was located-219 bp of the CDH13 promoter proximal to the start codon and was identified as 5′-CATGCAAAA-3′. Ectopic expression of BRN2 in BRN2-negative/T-cadherin-positive melanoma cells resulted in suppression of CDH13 promoter activity, whereas BRN2 knockdown in BRN2-positive/T-cadherin-negative melanoma cells resulted in re-expression of T-cadherin transcripts and protein. Transcriptional repression of CDH13 by BRN2 may participate in malignant transformation of melanoma by increasing invasion and migration potentials of melanoma cells. The study has identified CDH13 as a novel direct BRN2 transcriptional target gene and has advanced knowledge of mechanisms underlying loss of T-cadherin expression in melanoma. © 2012 USCAP, Inc All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: BRN2 (also known as POU3F2 and N-Oct-3); melanoma; promoter; T-cadherin (CDH13)

Brn3a expression is epigenetically controlled by HDAC2 in melanocytes and melanoma - Heppt, Markus; Wessely, A.; Hornig, E.; Kammerbauer, C.; Graf, S.; Besch, R.; French, L. E.; Kuphal, Silke; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin; Berking, Carola (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

Can checkpoint inhibitor therapy improve response to chemotherapy? - Boßerhoff, Anja Katrin; Schuler, Gerold; Heinzerling, Lucie; Schilling, Bastian; Haferrkamp, Sebastian; Kirchberger, MC (2017)
EVALuna2:4767

Can checkpoint inhibitor therapy improve response to chemotherapy? - Kirchberger, Michael Constantin; Schilling, Bastian; Haferkamp, Sebastian; Boßerhoff, Anja Katrin; Schuler, Gerold; Heinzerling, Lucie (Journal of Cancer Research and Clinical Oncology, 2018)
EVALuna2:34410

Characterization of glycolysis-related gene expression in malignant melanoma - Koch, Andreas; Ebert, Eva Vanessa; Seitz, Tatjana; Dietrich, Peter; Berneburg, Mark; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Pathology Research and Practice, 2020)
Malignant melanoma exhibits a distinct metabolic phenotype with high glycolytic activity. Previously, we have shown that glucose transporter isoform 1 (GLUT1) favors growth and metastasis of malignant melanoma. In this study, we investigated the expression of GLUT1 and the further glycolysis-related genes hexokinase 1 and 2 (HK1, HK2), lactate dehydrogenase A (LDH-A) and monocarboxylate transporters 1 and 4 (MCT1, MCT4) in eleven human melanoma cell lines under normoxic and hypoxic conditions. Furthermore, a set of 25 human malignant melanoma tissue samples was analyzed. Under hypoxic conditions, we could observe a significant upregulation of hypoxia-inducible factor 1 alpha (HIF-1a) target genes GLUT1, HK2 and LDH-A, but not MCT4. While under normoxic conditions the expression of glycolysis-related genes showed no correlation with origin or BRAF mutation status, GLUT1 expression was significantly elevated in metastatic and BRAF-V600E mutated melanoma cell lines under hypoxic conditions. Furthermore, GLUT1 expression in human melanoma tissue samples correlated significantly with HK1, LDH-A and MCT1 expression, confirming a glycolytic phenotype. Notably, Cyclin D1 expression, which is used as a prognostic marker for the outcome of melanoma patients, as it is associated with proliferation and invasiveness of melanoma, significantly correlated with GLUT1, HK1, LDH-A and MCT1 expression. In summary, our findings provide further evidence that enhanced glycolytic activity in melanoma favors disease progression and is an attractive therapeutic target for this highly aggressive tumor.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Cyclin D1; GLUT1; Glycolysis; HK1; HK2; LDH-A; MCT1; MCT4; Melanoma

Characterization of the Methylthioadenosine Phosphorylase Polymorphism rs7023954 - Incidence and Effects on Enzymatic Function in Malignant Melanoma - Limm, Katharina; Dettmer, Katja; Reinders, Joerg; Oefner, Peter J.; Boßerhoff, Anja Katrin (PLoS ONE, 2016)
Deficiency of methylthioadenosine phosphorylase (MTAP) supports melanoma development and progression through accumulation of its substrate 5'-methylthioadenosine (MTA), which leads amongst others to a constitutive inhibition of protein arginine methyltransferases (PRMTs) and activation of the transcription factor AP-1 via the receptor ADORA2B. Genetic association studies have also suggested that genetic polymorphism in MTAP may modulate the risk of melanoma. Here, we investigated the only globally common non-synonymous single nucleotide polymorphism (SNP) reported to date for MTAP. The SNP rs7023954 is located in exon 3 (c.166G>A), and leads to the conservative substitution of one branched-chain amino acid residue (valine) for another (isoleucine) at position 56 (p.Val56Ile). Whereas genotype frequencies in normal and primary melanoma tissues or cell lines were in Hardy-Weinberg equilibrium based on cDNA amplicon sequencing, a marked (P = 0.00019) deviation was observed in metastatic melanoma tissues and cell lines due to a deficit of heterozygotes. Enzyme assays conducted on the co-dominantly expressed alleles revealed no difference in the conversion rate of MTA to adenine and 5-methylthioribose-1-phosphate, indicating that this known enzymatic activity does not modulate the tumor suppressive function of MTAP.
EVALuna2:4733

Characterization of two different alginate-based bioinks and the influence of melanoma growth within - Schipka, Raphael; Heltmann-Meyer, Stefanie; Schneidereit, Dominik; Friedrich, Oliver; Röder, Jonas; Boccaccini, Aldo R.; Schrüfer, Stefan; Schubert, Dirk W.; Horch, Raymund E.; Boßerhoff, Anja Katrin; Arkudas, Andreas; Kengelbach-Weigand, Annika; et al. (Scientific Reports, 2024)
Extrusion-based bioprinting is an established method in biofabrication. Suitable bioinks have fundamentally different compositions and characteristics, which should be examined, in order to find a perfect model system. Here, we investigate the effect of two alginate-based, yet unalike 3D-printed bioinks, pre-crosslinked alginate-dialdehyde gelatin (ADA-GEL) and a mixture of alginate, hyaluronic acid, and gelatin (Alg/HA/Gel), on the melanoma cell line Mel Im and vice versa in terms of stiffness, shrinkage, cellular behavior and colony formation over 15 days. Rheological stiffness measurements revealed two soft gels with similar storage moduli. The cells did not have a significant impact on the overall stiffness, whereas ADA-GEL (2.5/2.5%) was significantly stiffer than Alg/HA/Gel (0.5/0.1/3%). Regarding the shrinkage of printed constructs, cells had a significant influence, especially in ADA-GEL, which has covalent bonds between the oxidized alginate and gelatin. Multi-photon microscopy exhibited proliferation, cell spreading and migration in ADA-GEL with cell–cell and cell–matrix interaction, dissimilarly to Alg/HA/Gel, in which cells formed spherical, encapsulated colonies. Scanning electron microscopy and histology showed degradation and multi-layered growth on ADA-GEL and fewer examples of escaped cells on Alg/HA/Gel. Both gels serve as proliferation bioink for melanoma with more necrosis in deeper Alg/HA/Gel colonies and differences in spreading and matrix interaction. These findings show the importance of proper characterization of the bioinks for different applications.
CRIS-Team Scopus Importer:2024-06-14
Keywords: 3D-printing; Alginate; Hydrogel; Melanoma; Stiffness

C-Jun drives melanoma progression in PTEN wild type melanoma cells - Kappelmann-Fenzl, Melanie; Gebhard, Claudia; Matthies, Alexander Oliver; Kuphal, Silke; Rehli, Michael; Boßerhoff, Anja Katrin (Cell Death & Disease, 2019)
Due to the critical impact of active AP-1 transcription factors in melanoma, it is important to define their target genes and to identify and ultimately inhibit oncogenic signals. Here we mapped the genome-wide occupancy of the AP-1 family member c-Jun in different melanoma cells and correlated AP-1 binding with transcriptome data to detect genes in melanoma regulated by c-Jun. Our analysis shows that c-Jun supports the malignant phenotype by deregulating genes in cancer-relevant signaling pathways, such as mitogen-activated protein kinase (MAPK) and phosphatidylinositol-3-kinase (PI3K) pathways. Moreover, we demonstrate that the importance of c-Jun depends on melanoma stage and mutation status of the tumor suppressor PTEN. Our study reveals that activation of c-Jun overrules the tumor suppressive effect of PTEN in early melanoma development. These findings help to understand the relevance of c-Jun within cancer pathways in different melanoma cell types, especially in relation to MAPK and PI3K pathways, which are commonly deregulated in melanomas. Consequently, targeting c-Jun in PTEN+ melanoma cells may represent a promising therapeutic strategy to inhibit survival of melanoma cells to prevent the development of a metastatic phenotype.
CRIS-Team Scopus Importer:2019-08-13

Clinicopathologic overview of melanoma - Boßerhoff, Anja Katrin; Strizzi, Luigi (Springer International Publishing, 2017)
Human melanoma is the most rapidly increasing malignant skin disease in Caucasians (Siegel et al. 2015). Once considered a rare disease, the lifetime risk for developing melanoma in the US has increased from approximately 1 in 1500 during the 1930s to its present risk of approximately 1 in 60 (Giblin and Thomas 2007). The American Cancer Society’s recent cancer report estimates that 76,380 new cases of melanoma will be diagnosed and 10,130 deaths will result from melanoma during 2016 in the United States (American Cancer Society 2016). Important risk factors for developing melanoma include increased number of melanocytic nevi, a family history of melanoma, or a history of previous melanoma (Seykora and Elder 1996; Psaty et al. 2010). Prolonged sun exposure associated with increased outdoor activity has been suggested to play an important role in the epidemiologic increase in the incidence of melanoma (Leiter and Garbe 2008; Moan et al. 2008). Acute exposure of the skin to ultraviolet radiation (UVR) can induce varying degrees of erythema, pigmentation, and impairment of immune function (Matsumura and Ananthaswamy 2004). Increased numbers of melanocytic nevi associated with sunburn and intermittent or “holiday” sun exposure has been suggested as a major risk factor for developing melanoma in different studies (Elwood and Jopson 1997; Newton-Bishop et al. 2010). In fact, the Clark model for melanoma suggests a stepwise progression from hyperplastic and dysplastic nevi to melanoma (Clark et al. 1984).
CRIS-Team Scopus Importer:2022-08-05

Cold atmospheric plasma, a new strategy to induce senescence in melanoma cells - Arndt, Stephanie; Wacker, Eva; Li, Yang-Fang; Shimizu, Tetsuji; Thomas, Hubertus M.; Morfill, Gregor E.; Karrer, Sigrid; Zimmermann, Julia L.; Bosserhoff, Anja Katrin (Experimental Dermatology, 2013)
Over the past few years, the application of cold atmospheric plasma (CAP) in medicine has developed into an innovative field of research of rapidly growing importance. One promising new medical application of CAP is cancer treatment. Different studies revealed that CAP may potentially affect the cell cycle and cause cell apoptosis or necrosis in tumor cells dependent on the CAP device and doses. In this study, we used a novel hand-held and battery-operated CAP device utilizing the Surface Micro Discharge (SMD) technology for plasma production in air and consequently analysed dose-dependent CAP treatment effects on melanoma cells. After 2 min of CAP treatment, we observed irreversible cell inactivation. Phospho-H2AX immunofluorescence staining and Flow cytometric analysis demonstrated that 2 min of CAP treatment induces DNA damage, promotes induction of Sub-G1 phase and strongly increases apoptosis. Further, protein array technology revealed induction of pro-apoptotic events like p53 and Rad17 phosphorylation of Cytochrome c release and activation of Caspase-3. Interestingly, using lower CAP doses with 1 min of treatment, almost no apoptosis was observed but long-term inhibition of proliferation. H3K9 immunofluorescence, SA-ß-Gal staining and p21 expression revealed that especially these low CAP doses induce senescence in melanoma cells. In summary, we observed differences in induction of apoptosis or senescence of tumor cells in respond to different CAP doses using a new CAP device. The mechanism of senescence with regard to plasma therapy was so far not described previously and is of great importance for therapeutic application of CAP. © 2013 John Wiley & Sons A/S.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Apoptosis; Melanoma cells; Plasma; Senescence

Cold atmospheric plasma (CAP) activates angiogenesis-related molecules in skin keratinocytes, fibroblasts and endothelial cells and improves wound angiogenesis in an autocrine and paracrine mode - Arndt, Stephanie; Unger, Petra; Berneburg, Mark; Boßerhoff, Anja Katrin; Karrer, Sigrid (Journal of Dermatological Science, 2017)
Cold atmospheric plasma (CAP) emerged as a novel therapeutic field with applications developed for bacterial sterilization, wound healing and cancer treatment. For clinical implementation it is important to know how CAP works and which molecular changes occur after the CAP treatment. Vascularization is an important step during wound healing, however, the effects of CAP on wound angiogenesis are not well examined so far. Furthermore, it has not been investigated, whether CAP primarily affects endothelial cells directly or via paracrine mechanisms to modulate the vasculature.This study concentrates on the influence of CAP on angiogenesis-related molecules in human epidermal keratinocytes, dermal fibroblasts and endothelial cells.CAP was generated by the MicroPlaSter ß® plasma torch system and CAP effects on angiogenesis were determined in vitro and in vivo.We observed that CAP significantly induces the expression of Artemin, EGF, EG-VEGF (PK1), Endothelin-1 (ET-1), FGF-2 (FGF basic), IL-8 (CXCL8) and uPA in keratinocytes and Angiogenin (ANG), Endostatin (Col18A1), MCP-1 (CCL2), MMP-9, TIMP-1, uPA and VEGF in fibroblasts. In addition, CAP activates the expression of Angiopoietin-2 (Ang-2), Angiostatin (PLG), Amphiregulin (AR), Endostatin, FGF-2 and angiogenic-involved receptor expression of FGF R1 and VEGF R1 in HUVEC endothelial cells. It was also demonstrated that supernatants collected from CAP activated fibroblasts and keratinocytes elevate tube formation by endothelial cells and FGF-2 appears to be an important pro-angiogenic factor that controls vascularization via paracrine mechanisms. Mouse experiments supplement that CAP promotes angiogenesis during wound healing in vivo.Taken together, these results suggest that CAP modulates angiogenesis-involved factors via autocrine and paracrine mechanisms and may be used to affect angiogenesis during wound healing.
EVALuna2:4777

Cold atmospheric plasma (CAP) changes gene expression of key molecules of the wound healing machinery and improves wound healing in vitro and in vivo - Arndt, Stephanie; Unger, Petra; Wacker, Eva; Shimizu, Tetsuji; Heinlin, Julia; Li, Yang-Fang; Thomas, Hubertus M.; Morfill, Gregor E.; Zimmermann, Julia L.; Karrer, Sigrid; Bosserhoff, Anja Katrin (PLoS ONE, 2013)
Cold atmospheric plasma (CAP) has the potential to interact with tissue or cells leading to fast, painless and efficient disinfection and furthermore has positive effects on wound healing and tissue regeneration. For clinical implementation it is necessary to examine how CAP improves wound healing and which molecular changes occur after the CAP treatment. In the present study we used the second generation MicroPlaSter β® in analogy to the current clinical standard (2 min treatment time) in order to determine molecular changes induced by CAP using in vitro cell culture studies with human fibroblasts and an in vivo mouse skin wound healing model. Our in vitro analysis revealed that the CAP treatment induces the expression of important key genes crucial for the wound healing response like IL-6, IL-8, MCP-1, TGF-β1, TGF-β2, and promotes the production of collagen type I and alpha-SMA. Scratch wound healing assays showed improved cell migration, whereas cell proliferation analyzed by XTT method, and the apoptotic machinery analyzed by protein array technology, was not altered by CAP in dermal fibroblasts. An in vivo wound healing model confirmed that the CAP treatment affects above mentioned genes involved in wound healing, tissue injury and repair. Additionally, we observed that the CAP treatment improves wound healing in mice, no relevant side effects were detected. We suggest that improved wound healing might be due to the activation of a specified panel of cytokines and growth factors by CAP. In summary, our in vitro human and in vivo animal data suggest that the 2 min treatment with the MicroPlaSter β® is an effective technique for activating wound healing relevant molecules in dermal fibroblasts leading to improved wound healing, whereas the mechanisms which contribute to these observed effects have to be further investigated. © 2013 Arndt et al.
CRIS-Team Scopus Importer:2022-08-05

Cold atmospheric plasma (CAP) for the selective control of tumor cells - Arndt, S.; Unger, P.; Schneider, C.; Boßerhoff, Anja Katrin; Karrer, S. (EXPERIMENTAL DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-14

Cold atmospheric plasma causes a calcium influx in melanoma cells triggering CAP-induced senescence - Schneider, Christin; Gebhardt, Lisa; Arndt, Stephanie; Karrer, Sigrid; Zimmermann, Julia L.; Fischer, Michael; Boßerhoff, Anja Katrin (Scientific Reports, 2018)
Cold atmospheric plasma (CAP) is a promising approach in anti-cancer therapy, eliminating cancer cells with high selectivity. However, the molecular mechanisms of CAP action are poorly understood. In this study, we investigated CAP effects on calcium homeostasis in melanoma cells. We observed increased cytoplasmic calcium after CAP treatment, which also occurred in the absence of extracellular calcium, indicating the majority of the calcium increase originates from intracellular stores. Application of previously CAP-exposed extracellular solutions also induced cytoplasmic calcium elevations. A substantial fraction of this effect remained when the application was delayed for one hour, indicating the chemical stability of the activating agent(s). Addition of ryanodine and cyclosporin A indicate the involvement of the endoplasmatic reticulum and the mitochondria. Inhibition of the cytoplasmic calcium elevation by the intracellular chelator BAPTA blocked CAP-induced senescence. This finding helps to understand the molecular influence and the mode of action of CAP on tumor cells.
EVALuna2:185219

Cold atmospheric plasma changes the amino acid composition of solutions and influences the anti‐tumor effect on melanoma cells - Arndt, Stephanie; Fadil, Fadi; Dettmer, Katja; Unger, Petra; Boskovic, Marko; Samol, Claudia; Boßerhoff, Anja Katrin; Zimmermann, Julia L.; Gruber, Michael; Gronwald, Wolfram; Karrer, Sigrid (International Journal of Molecular Sciences, 2021)
Cold Atmospheric Plasma (CAP) is an ionized gas near room temperature. Its anti‐tumor effect can be transmitted either by direct treatment or mediated by a plasma‐treated solution (PTS), such as treated standard cell culture medium, which contains different amino acids, inorganic salts, vitamins and other substances. Despite extensive research, the active components in PTS and its molecular or cellular mechanisms are not yet fully understood. The purpose of this study was the measurement of the reactive species in PTS and their effect on tumor cells using different plasma modes and treatment durations. The PTS analysis yielded mode‐ and dose‐dependent differences in the production of reactive oxygen and nitrogen species (RONS), and in the decomposition and modification of the amino acids Tyrosine (Tyr) and Tryptophan (Trp). The Trp metabolites Formylkynurenine (FKyn) and Kynurenine (Kyn) were produced in PTS with the 4 kHz (oxygen) mode, inducing apoptosis in Mel Im melanoma cells. Nitrated derivatives of Trp and Tyr were formed in the 8 kHz (nitrogen) mode, elevating the p16 mRNA expression and senescence-associated ß‐Galactosidase staining. In conclusion, the plasma mode has a strong impact on the composition of the active components in PTS and affects its anti‐tumor mechanism. These findings are of decisive importance for the development of plasma devices and the effectiveness of tumor treatment.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Amino acid; Anti‐tumor; Apoptosis; Cold atmospheric plasma (CAP); Melanoma; Plasma‐treated solution (PTS); Senescence

Cold Atmospheric Plasma Changes the Amino Acid Composition of Solutions and Influences the Anti-Tumor Effect on Melanoma Cells - Arndt, Stephanie; Fadil, Fadi; Dettmer, Katja; Unger, Petra; Boskovic, Marko; Samol, Claudia; Boßerhoff, Anja Katrin; Zimmermann, Julia L.; Gruber, Michael; Gronwald, Wolfram; Karrer, Sigrid (International Journal of Molecular Sciences, 2021)
Cold Atmospheric Plasma (CAP) is an ionized gas near room temperature. Its anti-tumor effect can be transmitted either by direct treatment or mediated by a plasma-treated solution (PTS), such as treated standard cell culture medium, which contains different amino acids, inorganic salts, vitamins and other substances. Despite extensive research, the active components in PTS and its molecular or cellular mechanisms are not yet fully understood. The purpose of this study was the measurement of the reactive species in PTS and their effect on tumor cells using different plasma modes and treatment durations. The PTS analysis yielded mode- and dose-dependent differences in the production of reactive oxygen and nitrogen species (RONS), and in the decomposition and modification of the amino acids Tyrosine (Tyr) and Tryptophan (Trp). The Trp metabolites Formylkynurenine (FKyn) and Kynurenine (Kyn) were produced in PTS with the 4 kHz (oxygen) mode, inducing apoptosis in Mel Im melanoma cells. Nitrated derivatives of Trp and Tyr were formed in the 8 kHz (nitrogen) mode, elevating the p16 mRNA expression and senescence-associated ß-Galactosidase staining. In conclusion, the plasma mode has a strong impact on the composition of the active components in PTS and affects its anti-tumor mechanism. These findings are of decisive importance for the development of plasma devices and the effectiveness of tumor treatment.

Cold atmospheric plasma promotes the immunoreactivity of granulocytes in vitro - Kupke, Laura S.; Arndt, Stephanie; Lenzer, Simon; Metz, Sophia; Unger, Petra; Zimmermann, Julia L.; Boßerhoff, Anja Katrin; Gruber, Michael; Karrer, Sigrid (Biomolecules, 2021)
Cold atmospheric plasma (CAP) reduces bacteria and interacts with tissues and cells, thus improving wound healing. The CAP-related induction of neutrophils was recently described in stained sections of wound tissue in mice. Consequently, this study aimed to examine the functionality of human polymorphonuclear cells (PMN)/granulocytes through either a plasma-treated solution (PTS) or the direct CAP treatment with different plasma modes and treatment durations. PTS analysis yielded mode-dependent differences in the production of reactive oxygen species (ROS) and reactive nitrogen species (RNS) after CAP treatment. Live-cell imaging did not show any chemo-attractive or NETosis-inducing effect on PMNs treated with PTS. The time to maximum ROS production (TmaxROS) in PMNs was reduced by PTS and direct CAP treatment. PMNs directly treated with CAP showed an altered cell migration dependent on the treatment duration as well as decreased TmaxROS without inducing apoptosis. Additionally, flow cytometry showed enhanced integrin and selectin expression, as a marker of activation, on PMN surfaces. In conclusion, the modification of PMN immunoreactivity may be a main supporting mechanism for CAP-induced improvement in wound healing.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Cold atmospheric plasma; Flow cytometry; Granulocytes; Live-cell imaging; NETosis; Wound treatment

Cold atmospheric plasma treatment inhibits growth in colorectal cancer cells - Schneider, Christin; Arndt, Stephanie; Zimmermann, Julia L.; Li, Yangfang; Karrer, Sigrid; Boßerhoff, Anja Katrin (Biological Chemistry, 2018)
Plasma oncology is a relatively new field of research. Recent developments have indicated that cold atmospheric plasma (CAP) technology is an interesting new therapeutic approach to cancer treatment. In this study, p53 wildtype (LoVo) and human p53 mutated (HT29 and SW480) colorectal cancer cells were treated with the miniFlatPlaSter - a device particularly developed for the treatment of tumor cells - that uses the Surface Micro Discharge (SMD) technology for plasma production in air. The present study analyzed the effects of plasma on colorectal cancer cells in vitro and on normal colon tissue ex vivo. Plasma treatment had strong effects on colon cancer cells, such as inhibition of cell proliferation, induction of cell death and modulation of p21 expression. In contrast, CAP treatment of murine colon tissue ex vivo for up to 2 min did not show any toxic effect on normal colon cells compared to H2O2 positive control. In summary, these results suggest that the miniFlatPlaSter plasma device is able to kill colorectal cancer cells independent of their p53 mutation status. Thus, this device presents a promising new approach in colon cancer therapy.
EVALuna2:202900

Cold Atmospheric Plasma Triggers Apoptosis via the Unfolded Protein Response in Melanoma Cells - Zimmermann, Tom; Stäbler, Sebastian; Taudte, R. Verena; Ünüvar, Sumeyya; Groesch, Sabine; Arndt, Stephanie; Karrer, Sigrid; Fromm, Martin; Boßerhoff, Anja Katrin (Cancers, 2023)
Cold atmospheric plasma (CAP) describes a partially ionized gas carrying large amounts of reactive oxygen (ROS) and nitrogen species (RNS). Numerous studies reported strong antitumor activity of CAP, thus rendering it a promising approach for tumor therapy. Although several cellular mechanisms of its cytotoxicity were identified in recent years, the exact molecular effects and contributing signaling pathways are yet to be discovered. We discovered a strong activation of unfolded protein response (UPR) after CAP treatment with increased C/EBP homologous protein (CHOP) expression, which was mainly caused by protein misfolding and calcium loss in the endoplasmic reticulum. In addition, both ceramide level and ceramide metabolism were reduced after CAP treatment, which was then linked to the UPR activation. Pharmacological inhibition of ceramide metabolism resulted in sensitization of melanoma cells for CAP both in vitro and ex vivo. This study identified a novel mechanism of CAP-induced apoptosis in melanoma cells and thereby contributes to its potential application in tumor therapy.
CRIS-Team Scopus Importer:2023-03-10
Keywords: apoptosis; ceramide; cold atmospheric plasma; melanoma; unfolded protein response

Combined de‐repression of chemoresistance associated mitogen‐activated protein kinase 14 and activating transcription factor 2 by loss of microrna‐622 in hepatocellular carcinoma - Fritz, Valerie; Malek, Lara; Gaza, Anne; Wormser, Laura; Appel, Majken; Kremer, Andreas; Thasler, Wolfgang E.; Neurath, Markus; Hellerbrand, Claus; Boßerhoff, Anja Katrin; Dietrich, Peter; Siebler, Jürgen (Cancers, 2021)
Chemoresistance is a major hallmark driving the progression and poor prognosis of hepatocellular carcinoma (HCC). Limited chemoresponse of HCC was demonstrated to be mediated by mitogen‐activated protein kinase 14 (MAPK14) and activating transcription factor 2 (ATF2). Recently, we have demonstrated loss of control of RAS‐RAF‐ERK‐signaling as a consequence of miR‐622 downregulation in HCC. However, the majority of target genes of this potent tumorsuppressive microRNA had remained elusive. The MAPK14‐ATF2‐axis represents a collateral pathway ensuring persisting ERK‐activation in the presence of sorafenib‐mediated RAF-inhibition. In contrast to the function of the MAPK14‐ATF2‐axis, both the expression and regulation of MAPK14 and ATF2 in human HCC remained to be clarified. We found combined overexpression of MAPK14 and ATF2 in human HCC cells, tissues and in sorafenib resistant cell lines. High expression of MAPK14 and ATF2 was associated with reduced overall survival in HCC patients. Deciphering the molecular mechanism promoting combined upregulation of MAPK14 and ATF2 in HCC, we revealed that miR‐622 directly targets both genes, resulting in combined de‐repression of the MAPK14‐ATF2‐axis. Together, miR‐622 represents a superior regulator of both RAS‐RAF‐ERK as well as MAPK14‐ATF2‐signaling pathways in liver cancer.
CRIS-Team Scopus Importer:2021-03-19
Keywords: HCC; Hepatocellular carcinoma; Liver cancer; MAPK14; MicroRNA; MiR‐622; RAS

Combined effects of PLK1 and RAS in hepatocellular carcinoma reveal rigosertib as promising novel therapeutic "dual-hit" option - Dietrich, Peter; Freese, Kim; Mahli, Abdo; Thasler, Wolfgang Erwin; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Oncotarget, 2018)
Inhibition of RAS-RAF-ERK-signaling is a major mechanism mediated by the multi-kinase inhibitors sorafenib and regorafenib, the only effective therapeutic approaches for advanced hepatocellular carcinoma (HCC). This underlines the importance of RAS-RAF-ERK-signaling in HCC. Most RAS isoforms were not yet described to play crucial roles in HCC. However, several studies indicate that the HRAS isoform can function as potent oncogene in HCC, but pharmacologic RAS inhibition has not yet been investigated. Moreover, the cell cycle promoting polo-like kinase 1 (PLK1) is an increasingly recognized therapeutic target in HCC that can be activated by RAS-RAF-signaling. A recently developed small molecule inhibitor, ON-01910 ("rigosertib", RGS), was shown to interfere with both RAS- and PLK1-signaling. The aim of this study was to analyze the effects of RGS in HCC and to assess PLK1 and HRAS expression in HCC. RGS treatment reduced cell proliferation and induced cell cycle arrest in human HCC cell lines in vitro. Moreover, RGS strongly inhibited both ERK- and AKT-activation in HCC cells, indicating disruption of RAS-signaling. Analysis of HCC patient data showed that PLK1 and HRAS expression levels are upregulated during HCC development and in advanced HCC, respectively. High expression levels of PLK1 significantly correlated with poor patient survival. Moreover, high expression of both PLK1 and HRAS revealed combined effects on patient outcome. This underscores the importance of these genes and associated pathways in HCC. We newly demonstrate the therapeutic potential of RGS in HCC by inhibition of both PLK1 activation and major RAS-pathways, revealing a novel therapeutic "dual-hit" approach for HCC.
EVALuna2:34067

Comparison of hydrogels for the development of well-defined 3d cancer models of breast cancer and melanoma - Schmid, Rafael; Schmidt, Sonja; Hazur, Jonas; Detsch, Rainer; Maurer, Evelyn; Boccaccini, Aldo R.; Hauptstein, Julia; Teßmar, Jörg; Blunk, Torsten; Schrüfer, Stefan; Schubert, Dirk W.; Horch, Raymund E.; et al. (Cancers, 2020)
Bioprinting offers the opportunity to fabricate precise 3D tumor models to study tumor pathophysiology and progression. However, the choice of the bioink used is important. In this study, cell behavior was studied in three mechanically and biologically different hydrogels (alginate, alginate dialdehyde crosslinked with gelatin (ADA–GEL), and thiol-modified hyaluronan (HA-SH crosslinked with PEGDA)) with cells from breast cancer (MDA-MB-231 and MCF-7) and melanoma (Mel Im and MV3), by analyzing survival, growth, and the amount of metabolically active, living cells via WST-8 labeling. Material characteristics were analyzed by dynamic mechanical analysis. Cell lines revealed significantly increased cell numbers in low-percentage alginate and HA-SH from day 1 to 14, while only Mel Im also revealed an increase in ADA–GEL. MCF-7 showed a preference for 1% alginate. Melanoma cells tended to proliferate better in ADA– GEL and HA-SH than mammary carcinoma cells. In 1% alginate, breast cancer cells showed equally good proliferation compared to melanoma cell lines. A smaller area was colonized in high-percentage alginate-based hydrogels. Moreover, 3% alginate was the stiffest material, and 2.5% ADA–GEL was the softest material. The other hydrogels were in the same range in between. Therefore, cellular responses were not only stiffness-dependent. With 1% alginate and HA-SH, we identified matrices that enable proliferation of all tested tumor cell lines while maintaining expected tumor heterogeneity. By adapting hydrogels, differences could be accentuated. This opens up the possibility of understanding and analyzing tumor heterogeneity by biofabrication.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Biofabrication; Breast cancer; Hydrogel; Melanoma; Tumor heterogeneity

Comparison of the Serum Tumor Markers S100 and Melanoma-inhibitory Activity (MIA) in the Monitoring of Patients with Metastatic Melanoma Receiving Vaccination Immunotherapy with Dendritic Cells - Uslu, Ugur; Schliep, Stefan; Schliep, Klaus; Erdmann, Michael; Koch, Hans-Uwe; Parsch, Hans; Rosenheinrich, Stina; Anzengruber, Doris; Boßerhoff, Anja Katrin; Schuler, Gerold; Schuler-Thurner, Beatrice (Anticancer Research, 2017)
In patients with melanoma, early dissemination via lymphatic and hematogenous routes is frequently seen. Thus, besides clinical follow-up examination and imaging, reliable melanoma-specific serological tumor markers are needed.We retrospectively compared two serum markers for melanoma, S100 and melanoma-inhibitory activity (MIA), for monitoring of patients with metastatic melanoma under either adjuvant or therapeutic vaccination immunotherapy with dendritic cells (DC). Serum was obtained from a total of 100 patients (28 patients in stage III and 72 patients in stage IV, according to the American Joint Committee on Cancer 2002) at regular intervals during therapy, accompanied by follow-up imaging.When relapse was detected, both markers often remained within normal range. In contrast, in patients with metastatic measurable disease receiving therapeutic and not adjuvant DC vaccination, an increase of both markers was a strong indicator for disease progression. When comparing both markers in the whole study population, MIA showed a superior sensitivity to detect disease progression.S100 and MIA are highly sensitive tumor markers for monitoring of patients with melanoma with current metastases, but less sensitive for monitoring of tumor-free patients. In the current study, MIA had a slightly superior sensitivity to detect progressive disease compared to S100 and seems to be more useful in monitoring of patients with metastatic melanoma receiving immunotherapy.
EVALuna2:4755

Complex formation with monomeric α-tubulin and importin 13 fosters c-jun protein stability and is required for c-jun’s nuclear translocation and activity - Kappelmann-Fenzl, Melanie; Kuphal, Silke; Krupar, Rosemarie; Schadendorf, Dirk; Umansky, Viktor; Vardimon, Lily; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Cancers, 2019)
Microtubules are highly dynamic structures, which consist of α-and β-tubulin heterodimers. They are essential for a number of cellular processes, including intracellular trafficking and mitosis. Tubulin-binding chemotherapeutics are used to treat different types of tumors, including malignant melanoma. The transcription factor c-Jun is a central driver of melanoma development and progression. Here, we identify the microtubule network as a main regulator of c-Jun activity. Monomeric α-tubulin fosters c-Jun protein stability by protein–protein interaction. In addition, this complex formation is necessary for c-Jun’s nuclear localization sequence binding to importin 13, and consequent nuclear import and activity of c-Jun. A reduction in monomeric α-tubulin levels by treatment with the chemotherapeutic paclitaxel resulted in a decline in the nuclear accumulation of c-Jun in melanoma cells in an experimental murine model and in patients’ tissues. These findings add important knowledge to the mechanism of the action of microtubule-targeting drugs and indicate the newly discovered regulation of c-Jun by the microtubule cytoskeleton as a novel therapeutic target for melanoma and potentially also other types of cancer.
CRIS-Team Scopus Importer:2019-11-29
Keywords: AP1; C-Jun; Importin; Transcription factor; Tubulin

CYLD - A potential Mediator of tissue-specific Melanoma Metastasis - Schott, Mandy; de Jel, Miriam Martha; Boßerhoff, Anja Katrin; Kuphal, Silke (2018)
EVALuna2:203600

CYLD controls c-MYC expression through the JNK-dependent signaling pathway in hepatocellular carcinoma - Pannem, Rajeswara Rao; Dorn, Christoph; Ahlqvist, Kristofer; Hellerbrand, Claus; Massoumi, Ramin; Bosserhoff, Anja Katrin (Carcinogenesis, 2014)
Posttranslational modification of different proteins via direct ubiquitin attachment is vital for mediating various cellular processes. Cylindromatosis (CYLD), a deubiquitination enzyme, is able to cleave the polyubiquitin chains from the substrate and to regulate different signaling pathways. Loss, or reduced expression, of CYLD is observed in different types of human cancer, such as hepatocellular carcinoma (HCC). However, the molecular mechanism by which CYLD affects cancerogenesis has to date not been unveiled. The aim of the present study was to examine how CYLD regulates cellular functions and signaling pathways during hepatocancerogenesis. We found that mice lacking CYLD were highly susceptible to chemically induced liver cancer. The mechanism behind proved to be an elevated proliferation rate of hepatocytes, owing to sustained c-Jun N-terminal kinase 1 (JNK1)-mediated signaling via ubiquitination of TNF receptor-associated factor 2 and expression of c-MYC. Overexpression of wild-type CYLD in HCC cell lines prevented cell proliferation, without affecting apoptosis, adhesion and migration. A combined immunohistochemical and tissue microarray analysis of 81 human HCC tissues revealed that CYLD expression is negatively correlated with expression of proliferation markers Ki-67 and c-MYC. To conclude, we found that downregulation of CYLD induces tumor cell proliferation, consequently contributing to the aggressive growth of HCC. Our findings suggest that CYLD holds potential to serve as a marker for HCC progression, and its link to c-MYC via JNK1 may provide the foundation for new therapeutic strategies for HCC patients. © The Author 2013. Published by Oxford University Press. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05

DCC is expressed in a CD166-positive subpopulation of chondrocytes in human osteoarthritic cartilage and modulates CRE activity - Bosserhoff, Anja Katrin; Hofmeister, Simone; Ruedel, Anke; Schubert, Thomas (International Journal of Clinical and Experimental Pathology, 2014)
Objective: In a recent study we determined a strong differential expression of DCC in OA compared to normal chondrocytes and a strong impact of the DCC receptor on cellular mobility triggered by its ligand Netrin-1. Migration of chondrocytes or their progenitor cells may play a role in remodeling of cartilage and pathological conditions. The purpose of this study is to identify subsets of chondrocytes expressing DCC and to understand signaling pathways used by DCC in chondrocytes. Methods: Immunofluorescent histology of human cartilage was used to determine the expression pattern of CD166, DCC and p-CREB. Cell culture of chondrocytes and SW1353, transient transfection, siRNA transfection, EMSA, luciferase assay, quantitative RT-PCR, ELISA, and Western Blotting were used to study signaling down-stream of DCC. Results: DCC expressing chondrocytes are mainly located in the surface layers of OA cartilage. These also express CD166 indicating that DCC expressing chondrocytes are progenitor cells. Interestingly, expression of DCC reduces cAMP levels, CREB DNA-binding activity and CRE activity in chondrocytes, whereas down-regulation of DCC results in induction of CRE signaling. Conclusion: In summary, DCC is up-regulated in CD166-positive chondrogenic progenitor cells in OA and induces down-regulation of CREB. These findings indicate that migration of CD166 positive progenitor cells to sites of cartilage damage may be directed by regulation of DCC signaling.
CRIS-Team Scopus Importer:2022-08-05
Keywords: CRE activity; CREB; DCC; Migration; Osteoarthritis; Repellent factors

Death inducer-obliterator 1 (Dido1) is a BMP target gene and promotes BMP-induced melanoma progression - Braig, S.; Bosserhoff, Anja Katrin (Oncogene, 2013)
Bone morphogenetic proteins (BMPs) are known to play an important role in melanoma development and progression. However, the downstream targets of BMPs have not been investigated thus far. Therefore, we treated melanoma cell lines with the Smad-specific BMP inhibitor Dorsomorphin and performed a cDNA microarray. We identified death inducer-obliterator 1 (Dido1) as a BMP-specific Smad-regulated target gene, which was confirmed by qRT-PCR, immunofluorescence staining and electrophoretic mobility shift assay experiments. An analysis of Dido1 expression revealed an upregulation of Dido1 levels in melanoma cell lines and tissues compared with normal melanocytes. Colony-formation assays showed that siDido1-transfected cells formed significantly smaller colonies when grown in soft agar compared with control cells. In addition, fluorescence-activated cell sorting and western blot experiments revealed that transfection of melanoma cells with Dido1 small interfering RNAs led to an upregulation of apoptosis. Furthermore, cell migratory and invasive potentials were strongly reduced in siDido1-transfected cells compared with control cells. Finally, we demonstrated that Dido1 induces the expression of Integrin αV, thereby promoting the attachment, migration, invasion and apoptosis resistance of melanoma cells. © 2013 Macmillan Publishers Limited All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: bone morphogenic protein; Dido1; integrin αV; invasion; malignant melanoma; migration

Deregulation of protein methylation in melanoma - Limm, Katharina; Ott, Corinna; Wallner, Susanne; Mueller, Daniel W.; Oefner, Peter; Hellerbrand, Claus; Bosserhoff, Anja Katrin (European Journal of Cancer, 2013)
Loss of methylthioadenosine phosphorylase (MTAP) expression and a concomitant accumulation of 5′-methyl-thioadenosine (MTA) characterise several tumour entities including malignant melanoma. MTA affects cellular signalling, proliferation and migration not only of cancer but also surrounding cells including lymphocytes and stromal fibroblasts. The mode of action of MTA is still not known. Interestingly, MTA is a known potent inhibitor of protein arginine methyltransferases (PRMTs) and is used as a tool in studying activity and impact of PRMTs. This study aimed at analysing PRMTs in melanoma and the potential impact of MTA on tumourigenesis. Our findings demonstrate that expression of PRMT4/CARM1 and PRMT6 is deregulated in melanoma, whereas expression of the remaining PRMTs stays unchanged. General PRMT activity and, consequently, symmetric and asymmetric protein methylation are reduced significantly in melanoma cells and tissues. This is due to a loss of MTAP expression and accumulation of MTA. Reduction of protein methylation by MTA affects cell signalling and leads, for example, to an activation of extracellular signal-regulated kinase (ERK) activity. The effects of endogeneous MTA on PRMTs as presented in this study can strongly support the migratory and invasive phenotype of melanoma cells. © 2012 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: MAPK/ERK signalling; Melanoma; Methylthioadenosine; PRMT; Protein arginine methylation

Design Aspects for Sensitive Metasurface-Based THz Biosensing in Aqueous Solutions - Richter, Merle; Weisenstein, Christian; Wigger, Anna K.; Boßerhoff, Anja Katrin; Bolivar, Peter Haring (2022 47TH INTERNATIONAL CONFERENCE ON INFRARED, MILLIMETER AND TERAHERTZ WAVES (IRMMW-THZ 2022), 2022)
CRIS-Team WoS Importer:2022-11-25

Detection and quantification of cellular senescence in human melanocytes and melanoma cell lines - Zimmermann, Tom; Pommer, Michaela; Kluge, Viola; Chiheb, Chafia; Mühlich, Susanne; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Detection of Cellular Senescence in Human Primary Melanocytes and Malignant Melanoma Cells In Vitro - Zimmermann, Tom; Pommer, Michaela; Kluge, Viola; Chiheb, Chafia; Mühlich, Susanne; Boßerhoff, Anja Katrin (Cells, 2022)
Detection and quantification of senescent cells remain difficult due to variable phenotypes and the absence of highly specific and reliable biomarkers. It is therefore widely accepted to use a combination of multiple markers and cellular characteristics to define senescent cells in vitro. The exact choice of these markers is a subject of ongoing discussion and usually depends on objective reasons such as cell type and treatment conditions, as well as subjective considerations including feasibility and personal experience. This study aims to provide a comprehensive comparison of biomarkers and cellular characteristics used to detect senescence in melanocytic systems. Each marker was assessed in primary human melanocytes that overexpress mutant BRAFV600E, as it is commonly found in melanocytic nevi, and melanoma cells after treatment with the chemotherapeutic agent etoposide. The combined use of these two experimental settings is thought to allow profound conclusions on the choice of senescence biomarkers when working with melanocytic systems. Further, this study supports the development of standardized senescence detection and quantification by providing a comparative analysis that might also be helpful for other cell types and experimental conditions.
CRIS-Team Scopus Importer:2022-05-13
Keywords: beta-galactosidase; melanocyte; melanoma; senescence

Detection of Human Tumor Markers with THz Metamaterials - Weisenstein, C.; Schaar, Dominik; Schmeck, M.; Wigger, A. K.; Boßerhoff, Anja Katrin; Bolivar, P. Haring (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2018)
THz bioanalytical techniques are already proven as a viable tool for the label-free detection of biomolecules. But still, significant improvement of THz sensing techniques is needed to reach application relevant sensitivity levels. We present the label-free THz sensing of human tumor markers using a highly sensitive metamaterial based THz biosensor. High affinity binding of the specific protein to DNA is utilized for localized functionalization to further enhance the detection sensitivity.
CRIS-Team Scopus Importer:2022-08-05

Development of a model system to analyze chondrogenic differentiation of mesenchymal stem cells - Ruede, Anke; Hofmeister, Simone; Bosserhoff, Anja Katrin (International Journal of Clinical and Experimental Pathology, 2013)
High-density cell culture is widely used for the analysis of cartilage development of human mesenchymal stem cells (HMSCs) in vitro. Several cell culture systems, as micromass, pellet culture and alginate culture, are applied by groups in the field to induce chondrogenic differentiation of HMSCs. A draw back of all model systems is the high amount of cells necessary for the experiments. Further, handling of large experimental approaches is difficult due to culturing e.g. in 15 ml tubes. Therefore, we aimed to develop a new model system based on "hanging drop" cultures using 10 to 100 fold less cells. Here, we demonstrate that differentiation of chondrogenic cells was induced as previously shown in other model systems. Real time RT-PCR analysis demonstrated that Collagen type II and MIA/CD-RAP were upregulated during culturing whereas for induction of hypertrophic markers like Collagen type X and AP-2 epsilon treatment with TGF beta was needed. To further test the system, siRNA against Sox9 was used and effects on chondrogenic gene expression were evaluated. In summary, the hanging drop culture system was determined to be a promising tool for in vitro chondrogenic studies.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Chondrogenic differentiation; Collagen; Hanging drop; Human mesenchymal stem cells

Dissimilar Appearances Are Deceptive-Common microRNAs and Therapeutic Strategies in Liver Cancer and Melanoma - Linck-Paulus, Lisa; Hellerbrand, Claus; Boßerhoff, Anja Katrin; Dietrich, Peter (Cells, 2020)
: In this review, we summarize the current knowledge on miRNAs as therapeutic targets in two cancer types that were frequently described to be driven by miRNAs-melanoma and hepatocellular carcinoma (HCC). By focusing on common microRNAs and associated pathways in these-at first sight-dissimilar cancer types, we aim at revealing similar molecular mechanisms that are evolved in microRNA-biology to drive cancer progression. Thereby, we also want to outlay potential novel therapeutic strategies. After providing a brief introduction to general miRNA biology and basic information about HCC and melanoma, this review depicts prominent examples of potent oncomiRs and tumor-suppressor miRNAs, which have been proven to drive diverse cancer types including melanoma and HCC. To develop and apply miRNA-based therapeutics for cancer treatment in the future, it is essential to understand how miRNA dysregulation evolves during malignant transformation. Therefore, we highlight important aspects such as genetic alterations, miRNA editing and transcriptional regulation based on concrete examples. Furthermore, we expand our illustration by focusing on miRNA-associated proteins as well as other regulators of miRNAs which could also provide therapeutic targets. Finally, design and delivery strategies of miRNA-associated therapeutic agents as well as potential drawbacks are discussed to address the question of how miRNAs might contribute to cancer therapy in the future.
EVALuna2:212285

DNMT targets MiRacle torching TORCh - Dietrich, Peter; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2016)
EVALuna2:4735

E-cadherin cell-cell communication in melanogenesis and during development of malignant melanoma - Kuphal, Silke; Bosserhoff, Anja Katrin (Archives of Biochemistry and Biophysics, 2012)
Cell-cell communication is necessary for the crosstalk between cells that constitute multicellular organisms and is essential for cells to coordinate their physiological behavior to create cohesive tissues. Cellular crosstalk is not only controlled by molecules, like growth factors, hormones, ions and G-proteins, etc. but also by cell-cell contacts. These contacts are essential for intercellular communication and are involved in survival, apoptosis, proliferation, differentiation and homeostasis of entire tissues. In polarized epithelia of vertebrates, the adherent junction is part of the tripartite junctional complex that is localized at the juxtaluminal region, which includes tight junctions (including claudins, occludins, and zonula occludens proteins), desmosomal junctions (including desmogleins), and adherent junctions. In focus of the manuscript are adherent molecules of the cadherin superfamily of the skin. In the normal epidermis, melanocytes and keratinocytes are mostly connected via E-cadherin, P-cadherin and H-cadherin [1-3]. Melanocytes that reside in the basal layer of the epidermis predominantly contain E-cadherin and H-cadherin, whereas those that reside in the hair follicles are rich in P-cadherin [2]. The regulation and role of E-cadherin during melanoma development will be the focus of this review. © 2012 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: AP1; Cadherins; Cell-cell contact; Melanoma; Signaling; Snail

Effect of melanoma cells on proliferation and migration of activated hepatic stellate cells in vitro - Meyer, Theresa; Koch, Andreas; Ebert, Eva-Vanessa; Czech, Barbara; Mueller, Martina; Boßerhoff, Anja Katrin; Lang, Sven Arke; Hellerbrand, Claus (Pathology Research and Practice, 2017)
Melanoma is a highly aggressive tumor of the skin. The clinical outcome is determined by the presence or absence of metastases, and the liver is a common site of distant metastases. Hepatic metastasis is causing activation of hepatic stellate cells (HSC), which form the stroma of hepatic metastases and are increasingly recognized as a crucial component of the pro- metastatic liver microenvironment. Most studies have focused on the effects of HSC on (metastasizing) tumor cells. Here, we aimed to analyze functional in vitro effects of conditioned medium (CM) of twelve different human melanoma cell lines on LX2 cells and HSC(htert) cells, two well established human activated HSC cell lines. CM from melanoma cells significantly induced HSC proliferation and acted as chemoattractant for HSC in Boyden chamber assays. The CM effects significantly varied between different HSC as well as melanoma cells. Interestingly, CM from melanoma cell lines derived from melanoma metastases (WM239A, WM9, WM1158, WM1232, 451Lu and 1205Lu) had a stronger effect on proliferation of HSC(htert) cells than CM derived from primary melanoma tumors (SbCl2, WM3211, WM35, WM278, WM1366 and WM793). Moreover, we observed a significant correlation between the chemoattractive effects of CM from the different melanoma cells on HSC(htert) and LX2 cells. In contrast, the melanoma CM effects on the proliferation of the two HSC lines did not show a significant correlation. In summary, our data indicate that melanoma cells metastasizing to the liver have the potential to attract HSC and to induce HSC proliferation, respectively. Still, it appears that melanoma effects on HSC migration and proliferation are mediated via different soluble factors indicating the complexity of melanoma-HSC interaction. Furthermore, the intensity of at least some functional effects varies between different human tumor cells and HSC which may point to mechanisms explaining diverse hepatic metastasis in melanoma patients.
EVALuna2:4750

Effects of Cold Atmospheric Plasma (CAP) on ß-Defensins, Inflammatory Cytokines, and Apoptosis-Related Molecules in Keratinocytes In Vitro and In Vivo - Arndt, Stephanie; Landthaler, Michael; Zimmermann, Julia L.; Unger, Petra; Wacker, Eva; Shimizu, Tetsuji; Li, Yang-Fang; Morfill, Gregor E.; Boßerhoff, Anja Katrin; Karrer, Sigrid (PLoS ONE, 2015)
Cold atmospheric plasma (CAP) has been gaining increasing interest as a new approach for the treatment of skin diseases or wounds. Although this approach has demonstrated promising antibacterial activity, its exact mechanism of action remains unclear. This study explored in vitro and in vivo whether CAP influences gene expression and molecular mechanisms in keratinocytes. Our results revealed that a 2 min CAP treatment using the MicroPlaSter ß in analogy to the performed clinical studies for wound treatment induces expression of IL-8, TGF-ß1, and TGF-ß2. In vitro and in vivo assays indicated that keratinocyte proliferation, migration, and apoptotic mechanisms were not affected by the CAP treatment under the applied conditions. Further, we observed that antimicrobial peptides of the ß-defensin family are upregulated after CAP treatment. In summary, our results suggest that a 2 min application of CAP induces gene expression of key regulators important for inflammation and wound healing without causing proliferation, migration or cell death in keratinocytes. The induction of ß-defensins in keratinocytes describes an absolutely new plasma strategy. Activation of antimicrobial peptides supports the well-known antibacterial effect of CAP treatment, whereas the mechanism of ß-defensin activation by CAP is not investigated so far.
EVALuna2:4706

Encapsulation of Rat Bone Marrow Derived Mesenchymal Stem Cells in Alginate Dialdehyde/Gelatin Microbeads with and without Nanoscaled Bioactive Glass for In Vivo Bone Tissue Engineering. - Rottensteiner-Brandl, Ulrike; Detsch, Rainer; Sarker, Bapi; Lingens, Lara; Köhn, Katrin; Kneser, Ulrich; Boßerhoff, Anja Katrin; Horch, Raymund E.; Boccaccini, Aldo R.; Arkudas, Andreas (Materials, 2018)
Alginate dialdehyde (ADA), gelatin, and nano-scaled bioactive glass (nBG) particles are being currently investigated for their potential use as three-dimensional scaffolding materials for bone tissue engineering. ADA and gelatin provide a three-dimensional scaffold with properties supporting cell adhesion and proliferation. Combined with nanocristalline BG, this composition closely mimics the mineral phase of bone. In the present study, rat bone marrow derived mesenchymal stem cells (MSCs), commonly used as an osteogenic cell source, were evaluated after encapsulation into ADA-gelatin hydrogel with and without nBG. High cell survival was found in vitro for up to 28 days with or without addition of nBG assessed by calcein staining, proving the cell-friendly encapsulation process. After subcutaneous implantation into rats, survival was assessed by DAPI/TUNEL fluorescence staining. Hematoxylin-eosin staining and immunohistochemical staining for the macrophage marker ED1 (CD68) and the endothelial cell marker lectin were used to evaluate immune reaction and vascularization. After in vivo implantation, high cell survival was found after 1 week, with a notable decrease after 4 weeks. Immune reaction was very mild, proving the biocompatibility of the material. Angiogenesis in implanted constructs was significantly improved by cell encapsulation, compared to cell-free beads, as the implanted MSCs were able to attract endothelial cells. Constructs with nBG showed higher numbers of vital MSCs and lectin positive endothelial cells, thus showing a higher degree of angiogenesis, although this difference was not significant. These results support the use of ADA/gelatin/nBG as a scaffold and of MSCs as a source of osteogenic cells for bone tissue engineering. Future studies should however improve long term cell survival and focus on differentiation potential of encapsulated cells in vivo.

Enhanced expression of BMP6 inhibits hepatic fibrosis in non-alcoholic fatty liver disease - Arndt, Stephanie; Wacker, Eva; Dorn, Christoph; Koch, Andreas; Saugspier, Michael; Thasler, Wolfgang E.; Hartmann, Arndt; Bosserhoff, Anja Katrin; Hellerbrand, Claus (Gut, 2015)
Bone morphogenetic protein 6 (BMP6) has been identified as crucial regulator of iron homeostasis. However, its further role in liver pathology including non-alcoholic fatty liver disease (NAFLD) and its advanced form non-alcoholic steatohepatitis (NASH) is elusive. The aim of this study was to investigate the expression and function of BMP6 in chronic liver disease.BMP6 was analysed in hepatic samples from murine models of chronic liver injury and patients with chronic liver diseases. Furthermore, a tissue microarray comprising 110 human liver tissues with different degree of steatosis and inflammation was assessed. BMP6-deficient (BMP6(-/-)) and wild-type mice were compared in two dietary NASH-models, that is, methionine choline-deficient (MCD) and high-fat (HF) diets.BMP6 was solely upregulated in NAFLD but not in other murine liver injury models or diseased human livers. In NAFLD, BMP6 expression correlated with hepatic steatosis but not with inflammation or hepatocellular damage. Also, in vitro cellular lipid accumulation in primary human hepatocytes induced increased BMP6 expression. MCD and HF diets caused more hepatic inflammation and fibrosis in BMP6(-/-) compared with wild-type mice. However, only in the MCD and not in the HF diet model BMP6(-/-) mice developed marked hepatic iron overload, suggesting that further mechanisms are responsible for protective BMP6 effect. In vitro analysis revealed that recombinant BMP6 inhibited the activation of hepatic stellate cells (HSCs) and reduced proinflammatory and profibrogenic gene expression in already activated HSCs.Steatosis-induced upregulation of BMP6 in NAFLD is hepatoprotective. Induction of BMP6-signalling may be a promising antifibrogenic strategy.
EVALuna2:4714

ERK activation and autophagy impairment are central mediators of irinotecan-induced steatohepatitis - Mahli, Abdo; Saugspier, Michael; Koch, Andreas; Sommer, Judith; Dietrich, Peter; Lee, Seren; Thasler, Reinhard; Schulze-Luehrmann, Jan; Lührmann, Anja; Thasler, Wolfgang Erwin; Müller, Martina; Boßerhoff, Anja Katrin; et al. (Gut, 2017)
Preoperative chemotherapy with irinotecan is associated with the development of steatohepatitis, which increases the risk of perioperative morbidity and mortality for liver surgery. The molecular mechanisms of this chemotherapeutic complication are widely unknown.Mechanisms of irinotecan-induced steatohepatitis were studied in primary human hepatocytes in vitro, in mice treated with irinotecan and in liver specimens from irinotecan-treated compared with control patients.Irinotecan dose-dependently induced lipid accumulation and pro-inflammatory gene expression in hepatocytes. This was accompanied by an impairment of mitochondrial function with reduced expression of carnitine palmitoyltransferase I and an induction of acyl-coenzyme A oxidase-1 (ACOX1), oxidative stress and extracellular signal-regulated kinase (ERK) activation. ERK inhibition prevented irinotecan-induced pro-inflammatory gene expression but had only a slight effect on lipid accumulation. However, irinotecan also induced an impairment of the autophagic flux mediated by alkalisation of lysosomal pH. Re-acidification of lysosomal pH abolished irinotecan-induced autophagy impairment and lipid accumulation. Also in mice, irinotecan treatment induced hepatic ACOX1 expression, ERK phosphorylation and inflammation, as well as impairment of autophagy and significant steatosis. Furthermore, irinotecan-treated patients revealed higher hepatic ERK activity, expression of pro-inflammatory genes and markers indicative for a shift to peroxisomal fatty acid oxidation and an impaired autophagic flux. Pretreatment with the multityrosine kinase inhibitor sorafenib did not affect autophagy impairment and steatosis but significantly reduced ERK phosphorylation and inflammatory response in irinotecan-treated hepatocytes and murine livers.Irinotecan induces hepatic steatosis via autophagy impairment and inflammation via ERK activation. Sorafenib appears as a novel therapeutic option for the prevention and treatment of irinotecan-induced inflammation.
EVALuna2:4748

ETS-1/RhoC signaling regulates the transcription factor c-Jun in melanoma - Spangler, Barbara; Kappelmann, Melanie; Schittek, Birgit; Meierjohann, Svenja; Vardimon, Lily; Bosserhoff, Anja Katrin; Kuphal, Silke (International Journal of Cancer, 2012)
Recently, we discovered that the loss of E-cadherin induces c-Jun protein expression, which is a member of the AP-1 transcription factor family and a key player in the processes of cell proliferation and tumor development and also found in elevated levels in melanomas. Notably, the mRNA level of c-Jun was not affected, suggesting that c-Jun is regulated at post-transcriptional level. Here, we present data that suggest that the dynamic cytoskeletal network, linked to E-cadherin, is involved in the regulation of the c-Jun protein and transcriptional activity. In a signaling cascade, the loss of E-cadherin activates the transcriptional regulator ETS-1 and consequently leads to the induction of RhoC expression that stabilizes c-Jun in melanoma. The link between RhoC and c-Jun seems to be indirect via the cytoskeleton. We conclude that the loss of E-cadherin mediated cell-adhesion induces c-Jun protein expression in a multistep process, offering several possibilities for therapeutic intervention. Copyright © 2011 UICC.
CRIS-Team Scopus Importer:2022-08-05
Keywords: c-Jun; cytoskeleton; ETS-1; melanoma; Rho

Expression and function of microRNA-188-5p in activated rheumatoid arthritis synovial fibroblasts - Ruedel, Anke; Dietrich, Peter; Schubert, Thomas; Hofmeister, Simone; Hellerbrand, Claus; Boßerhoff, Anja Katrin (International Journal of Clinical and Experimental Pathology, 2015)
Activated synovial fibroblasts in rheumatoid arthritis (RASF) play a critical role in the pathology of rheumatoid arthritis (RA). Recent studies suggested that deregulation of microRNAs (miRs) affects the development and progression of RA. Therefore, we aimed to identify de-regulated miRs in RASF and to identify target genes that may contribute to the aggressive phenotype of RASF. Quantitative real-time PCR revealed a marked downregulation of miR-188-5p in synovial tissue samples of RA patients as well as in RASF. Exposure to the cytokine interleukine-1? lead to a further downregulation of miR-188-5p expression levels compared to control cells. Re-expression of miR-188-5p in RASF by transient transfection significantly inhibited cell migration. However, miR-188-5p re-expression had no effects on glycosaminoglycan degradation or expression of repellent factors, which have been previously shown to affect the invasive behavior of RASF. In search for target genes of miR-188-5p in RASF we performed gene expression profiling in RASF and found a strong regulatory effect of miR-188-5p on the hyaluronan binding protein KIAA1199 as well as collagens COL1A1 and COL12A1, which was confirmed by qRT-PCR. In silico analysis revealed that KIAA1199 carries a 3'UTR binding site for miR-188-5p. COL1A1and COL12A1 showed no binding site in the mRNA region, suggesting an indirect regulation of these two genes by miR-188-5p. In summary, our study showed that miR-188-5p is down-regulated in RA in vitro and in vivo, most likely triggered by an inflammatory environment. MiR-188-5p expression is correlated to the activation state of RASF and inhibits migration of these cells. Furthermore, miR-188-5p is directly and indirectly regulating the expression of genes, which may play a role in extracellular matrix formation and destruction in RA. Herewith, this study identified potential novel therapeutic targets to inhibit the development and progression of RA.
EVALuna2:4744

Expression of Bone Morphogenetic Protein 14 in Liver Disease and Cancer - Sommer, Judith; Thasler, Wolfgang E.; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Livers, 2023)
The activation of hepatic stellate cells (HSCs) is the key event of hepatic fibrosis. Furthermore, activated HSCs also play an important role in the progression of hepatocellular cancer (HCC). Bone morphogenetic protein 14 (BMP14) is a member of the TGF-β/BMP superfamily. So far, most studies have analyzed BMP14 in the context of bone and cartilage formation and homeostasis. The aim of this study was to assess the expression and function of BMP14 in liver fibrosis and HCC. The BMP14 expression increased during the in vitro activation of primary human HSCs and also in mouse models of liver fibrosis. In human HCC, as well as non-tumorous liver tissues, there was a significant correlation between the expression of BMP14 and alpha-smooth-muscle actin (α-SMA), an established marker for HSC activation. RNAi-mediated BMP14 suppression in activated HSCs resulted in the reduced expression of the transcription factors inhibitor of differentiation 1 (ID1) and ID2, known targets of BMP signaling. Interestingly, α-SMA and collagen expression was also reduced in BMP14-depleted cells, while treatment with recombinant BMP14 induced ID1, ID2, α-SMA and collagen expression. In human HCC cell lines, treatment with recombinant BMP14 induced proliferation, migratory activity and colony formation. In summary, our data indicate activated HSCs as a major cellular source of enhanced BMP14 expression in fibrotic liver disease and HCC, and show that BMP14 exhibits pro-fibrogenic as well as pro-tumorigenic effects. Future analyses will reveal the potential of this soluble growth factor as a therapeutic target or prognostic marker for the progression of fibrosis and HCC in patients with chronic liver disease.
CRIS-Team Scopus Importer:2023-11-17
Keywords: BMP14; hepatic stellate cells; hepatocellular cancer; liver fibrosis

Extracellular Acidosis leads to the Development of a senescent-like Phenotype and molecular Reprogramming of human Melanoma Cells - Böhme, Ines; Boßerhoff, Anja Katrin (2018)
EVALuna2:203601

Extracellular acidosis leads to the formation of a senescence-like subpopulation in malignant melanoma - Chiheb, Chafia; Böhme-Schäfer, Ines; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Extracellular acidosis triggers a senescence-like phenotype in human melanoma cells - Böhme, Ines; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2019)
Acidosis of the tumor microenvironment is a characteristic of solid tumors such as malignant melanoma. Main causes of the extracellular acidification are metabolic alterations in cancer cells. While numerous studies showed that acidosis promotes tumor invasiveness, metastasis, and neoangiogenesis resulting in malignant progression, contrary data reported that acidosis induces cell apoptosis, inhibits cell proliferation, and mediates cell autophagy. Here, we show that low pH (pH 6.7) induces senescent/quiescent phenotype in melanoma cells after long-time treatment defined by induction of SA-beta-galactosidase, upregulation of p21, G(1)/G(0) cell cycle arrest, and reduction of proliferation. Moreover, we revealed that extracellular acidosis triggers the inhibition of eIF2 alpha and subsequently the activation of ATF4 expression, a key component of the integrated stress response (ISR), indicating an acid-mediated translation reprogramming. Interestingly, we also demonstrated that acidosis represses microphthalmia-associated transcription factor (MITF) and activates the expression of the receptor tyrosine kinase AXL. This MITFlow/AXL(high) phenotype is correlated with drug resistance and therapeutic outcome in melanoma. Our results suggest that acidosis is an important microenvironmental factor triggering phenotypic plasticity and promoting tumor progression.
CRIS-Team WoS Importer:2019-08-20

Fibroblast Growth Factor 9 is expressed by activated hepatic stellate cells and promotes progression of hepatocellular carcinoma - Seitz, Tatjana; Freese, Kim; Dietrich, Peter; Thasler, Wolfgang Erwin; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Scientific Reports, 2020)
Hepatocellular carcinoma (HCC) is closely associated with liver fibrosis. Hepatic stellate cells (HSC) and cancer-associated myofibroblasts are key players in liver fibrogenesis and hepatocarcinogenesis. Overexpression of fibroblast growth factor (FGF) receptors contributes to HCC development and progression. This study aimed to elucidate the role of FGFs in the HSC-HCC crosstalk. Analysis of the expression of the fifteen paracrine FGF-members revealed that FGF9 was only expressed by HSC but not by HCC cells. Also in human HCC tissues, HSC/stromal myofibroblasts were identified as cellular source of FGF9. High expression levels of FGF9 significantly correlated with poor patient survival. Stimulation with recombinant FGF9 induced ERK- and JNK-activation combined with significantly enhanced proliferation, clonogenicity, and migration of HCC cells. Moreover, FGF9 significantly reduced the sensitivity of HCC cells against sorafenib. Protumorigenic effects of FGF9 on HCC cells were almost completely abrogated by the FGFR1/2/3 inhibitor BGJ398, while the selective FGFR4 inhibitor BLU9931 had no significant effect. In conclusion, these data indicate that stroma-derived FGF9 promotes tumorigenicity and sorafenib resistance of HCC cells and FGF9 overexpression correlates with poor prognosis in HCC patients. Herewith, FGF9 appears as potential prognostic marker and novel therapeutic target in HCC.
CRIS-Team Scopus Importer:2020-03-27

Fibrosing connective tissue disorders of the skin: Molecular similarities and distinctions - Canady, Johanna; Karrer, Sigrid; Fleck, Martin; Bosserhoff, Anja Katrin (Journal of Dermatological Science, 2013)
A variety of fibrosing connective tissue disorders of the skin have been described. They all share a characteristic activation of fibroblasts resulting in excessive production and deposition of extracellular matrix whereas their etiologies, incidence rates and clinical appearances differ dramatically in part. As effective treatment options are still not on hand, the understanding of cutaneous fibrogenesis needs to be improved. This review focuses on the molecular differences and similarities of the major fibrosing skin disorders namely systemic sclerosis, localized scleroderma, keloid and hypertrophic scars, Eosinophilic fasciitis, Lichen sclerosus and graft-versus-host-disease. Abnormalities in ECM turnover and the impact of matrix-metalloproteases were closely examined. It could be concluded, that besides increased collagen synthesis, modified ECM degradation is an as important factor in cutaneous fibrogenesis. The influence of immune components such as HLA haplotypes and the production of auto-antibodies is crucial for some of the diseases, but not decisive for skin fibrosis in general. A great number of cytokines was reported to be differentially regulated in the respective disorders among whom the components of the gp130/STAT3 signaling pathway seem to be of pivotal importance. Furthermore, the role of miRNAs in the pathogenesis of fibrosing connective tissue diseases of the skin was analyzed according to the current state of knowledge.In summary, this review gives an explicit overview of the various molecular mechanisms leading to fibrosis in the skin and the underlying connective tissue and reveals the most promising targets for future therapeutic approaches. © 2013 Japanese Society for Investigative Dermatology.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Connective tissue; Fibrosis; MiRNA; Signaling

Four-And-A-Half LIM-Domain Protein 2 (FHL2) Deficiency Aggravates Cholestatic Liver Injury - Sommer, Judith; Dorn, Christoph; Gaebele, Erwin; Bataille, Frauke; Freese, Kim; Seitz, Tatjana; Thasler, Wolfgang E.; Buettner, Reinhard; Weiskirchen, Ralf; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cells, 2020)
Cholestasis occurs in different clinical circumstances and leads to severe hepatic disorders. The four-and-a-half LIM-domain protein 2 (FHL2) is a scaffolding protein that modulates multiple signal transduction pathways in a tissue- and cell context-specific manner. In this study, we aimed to gain insight into the function of FHL2 in cholestatic liver injury. FHL2 expression was significantly increased in the bile duct ligation (BDL) model in mice. In Fhl2-deficient (Fhl2-ko) mice, BDL caused a more severe portal and parenchymal inflammation, extended portal fibrosis, higher serum transaminase levels, and higher pro-inflammatory and pro-fibrogenic gene expression compared to wild type (wt) mice. FHL2 depletion in HepG2 cells with siRNA resulted in a higher expression of the bile acid transporter Na+-taurocholate cotransporting polypeptide (NTCP) gene. Furthermore, FHL2-depleted HepG2 cells showed higher expression of markers for oxidative stress, lower B-cell lymphoma 2 (Bcl2) expression, and higher Bcl2-associated X protein (BAX) expression after stimulation with deoxycholic acid (DCA). In hepatic stellate cells (HSCs), FHL2 depletion caused an increased expression of TGF-β and several pro-fibrogenic matrix metalloproteinases. In summary, our study shows that deficiency in FHL2 aggravates cholestatic liver injury and suggests FHL2-mediated effects on bile acid metabolisms and HSCs as potential mechanisms for pronounced hepatocellular injury and fibrosis.
EVALuna2:212289

Four-and-a-Half LIM-Domain Protein 2 (FHL2) Induces Neuropeptide Y (NPY) in Macrophages in Visceral Adipose Tissue and Promotes Diet-Induced Obesity - Sommer, Judith; Ehnis, Hanna; Seitz, Tatjana; Schneider, Julia; Wild, Andreas; Moceri, Sandra; Buechler, Christa; Bozec, Aline; Weber, Georg; Merkel, Susanne; Beckervordersandforth, Ruth; Steinkasserer, Alexander; et al. (International Journal of Molecular Sciences, 2023)
Obesity is characterized by the expansion of the adipose tissue, usually accompanied by inflammation, with a prominent role of macrophages infiltrating the visceral adipose tissue (VAT). This chronic inflammation is a major driver of obesity-associated comorbidities. Four-and-a-half LIM-domain protein 2 (FHL2) is a multifunctional adaptor protein that is involved in the regulation of various biological functions and the maintenance of the homeostasis of different tissues. In this study, we aimed to gain new insights into the expression and functional role of FHL2 in VAT in diet-induced obesity. We found enhanced FHL2 expression in the VAT of mice with Western-type diet (WTD)-induced obesity and obese humans and identified macrophages as the cellular source of enhanced FHL2 expression in VAT. In mice with FHL2 deficiency (FHL2KO), WTD feeding resulted in reduced body weight gain paralleled by enhanced energy expenditure and uncoupling protein 1 (UCP1) expression, indicative of activated thermogenesis. In human VAT, FHL2 was inversely correlated with UCP1 expression. Furthermore, macrophage infiltration and the expression of the chemokine MCP-1, a known promotor of macrophage accumulation, was significantly reduced in WTD-fed FHL2KO mice compared with wild-type (wt) littermates. While FHL2 depletion did not affect the differentiation or lipid metabolism of adipocytes in vitro, FHL2 depletion in macrophages resulted in reduced expressions of MCP-1 and the neuropeptide Y (NPY). Furthermore, WTD-fed FHL2KO mice showed reduced NPY expression in VAT compared with wt littermates, and NPY expression was enhanced in VAT resident macrophages of obese individuals. Stimulation with recombinant NPY induced not only UCP1 expression and lipid accumulation but also MCP-1 expression in adipocytes. Collectively, these findings indicate that FHL2 is a positive regulator of NPY and MCP-1 expression in macrophages and herewith closely linked to the mechanism of obesity-associated lipid accumulation and inflammation in VAT. Thus, FHL2 appears as a potential novel target to interfere with the macrophage–adipocyte crosstalk in VAT for treating obesity and related metabolic disorders.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adipocytes; FHL2; macrophages; MCP-1; NPY; obesity; thermogenesis

Fragments of SLIT3 inhibit cellular migration - Schubert, Thomas; Denk, Alexandra E.; Ruedel, Anke; Kaufmann, Simone; Hustert, Elisabeth; Bastone, Patrizia; Bosserhoff, Anja K. (International Journal of Molecular Medicine, 2012)
The repellent factor family of Slit molecules has been described as having a repulsive function in the developing nervous system on growing axons expressing the Roundabout (Robo) receptors. Recent studies determined the effects of Slit molecules on the migratory and invasive potential of several types of tumor cells but also on synovial fibroblasts (SFs) derived from rheumatoid arthritis (RA) patients. To optimize a potential therapeutic application we aimed at generating-fragments of Slit3 showing the same functional ability as the full-length molecule but having the advantage of a smaller size. Recombinant Slit3 proteins were expressed and analyzed by western blotting. Their activity was defined by functional assays such as migration assays with RASF and melanoma cells. Recombinant Slit3 containing only leucine rich repeat domain 2 (D2), the domain important for Robo binding and the minimal functional unit D2 dNC were both able to inhibit migration of RASFs as effectively as Slit3 with all 4 repeats. Collectively, our data showed that the ability of Slit3 to reduce the migratory activity of synovial cells from patients with RA and melanoma cells can be mimicked by small protein fragments derived from Slit3. Slit3 fragments may be helpful in therapeutic attempts; however, further studies are necessary in order to elucidate their activity in vivo.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Melanoma; Migration; Proliferation; Recombinant proteins; Repellent factor; Rheumatoid arthritis; Roundabout; Slit

Glucose transporter isoform 1 expression enhances metastasis of malignant melanoma cells - Koch, Andreas; Lang, Sven Arke; Wild, Peter Johannes; Gantner, Susanne; Mahli, Abdo; Spanier, Gerrit; Berneburg, Mark; Mueller, Martina; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Oncotarget, 2015)
The glucose transporter isoform 1 (GLUT1; SLC2A1) is a key rate-limiting factor in the transport of glucose into cancer cells. Enhanced GLUT1 expression and accelerated glycolysis have been found to promote aggressive growth in a range of tumor entities. However, it was unknown whether GLUT1 directly impacts metastasis. Here, we aimed at analyzing the expression and function of GLUT1 in malignant melanoma. Immunohistochemical analysis of 78 primary human melanomas on a tissue micro array showed that GLUT1 expression significantly correlated with the mitotic activity and a poor survival. To determine the functional role of GLUT1 in melanoma, we stably suppressed GLUT1 in the murine melanoma cell line B16 with shRNA. GLUT1 suppressed melanoma cells revealed significantly reduced proliferation, apoptosis resistance, migratory activity and matrix metalloproteinase 2 (MMP2) expression. In a syngeneic murine model of hepatic metastasis, GLUT1-suppressed cells formed significantly less metastases and showed increased apoptosis compared to metastases formed by control cells. Treatment of four different human melanoma cell lines with a pharmacological GLUT1 inhibitor caused a dose-dependent reduction of proliferation, apoptosis resistance, migratory activity and MMP2 expression. Analysis of MAPK signal pathways showed that GLUT1 inhibition significantly decreased JNK activation, which regulates a wide range of targets in the metastatic cascade. In summary, our study provides functional evidence that enhanced GLUT1 expression in melanoma cells favors their metastatic behavior. These findings specify GLUT1 as an attractive therapeutic target and prognostic marker for this highly aggressive tumor.
EVALuna2:4719

HDAC2 Is Involved in the Regulation of BRN3A in Melanocytes and Melanoma - Heppt, Markus; Wessely, Anja; Hornig, Eva; Kammerbauer, Claudia; Graf, Saskia A.; Besch, Robert; French, Lars E.; Matthies, Alexander Oliver; Kuphal, Silke; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin; Berking, Carola (International Journal of Molecular Sciences, 2022)
The neural crest transcription factor BRN3A is essential for the proliferation and survival of melanoma cells. It is frequently expressed in melanoma but not in normal melanocytes or benign nevi. The mechanisms underlying the aberrant expression of BRN3A are unknown. Here, we investigated the epigenetic regulation of BRN3A in melanocytes and melanoma cell lines treated with DNA methyltransferase (DNMT), histone acetyltransferase (HAT), and histone deacetylase (HDAC) inhibitors. DNMT and HAT inhibition did not significantly alter BRN3A expression levels, whereas panHDAC inhibition by trichostatin A led to increased expression. Treatment with the isoform-specific HDAC inhibitor mocetinostat, but not with PCI-34051, also increased BRN3A expression levels, suggesting that class I HDACs HDAC1, HDAC2, and HDAC3, and class IV HDAC11, were involved in the regulation of BRN3A expression. Transient silencing of HDACs 1, 2, 3, and 11 by siRNAs revealed that, specifically, HDAC2 inhibition was able to increase BRN3A expression. ChIP-Seq analysis uncovered that HDAC2 inhibition specifically increased H3K27ac levels at a distal enhancer region of the BRN3A gene. Altogether, our data suggest that HDAC2 is a key epigenetic regulator of BRN3A in melanocytes and melanoma cells. These results highlight the importance of epigenetic mechanisms in regulating melanoma oncogenes.
CRIS-Team Scopus Importer:2022-02-04
Keywords: BRN3A; ChIP-Seq; DNA methylation; Epigenetic regulation; HAT; HDAC; Melanoma

HDAC2 is involved in the regulation of Brn3a in melanocytes and melanoma - Heppt, Markus; Wessely, Anja; Hornig, E.; Kammerbauer, C.; Graf, S.; Besch, R.; French, L. E.; Kuphal, Silke; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin; Berking, Carola (EXPERIMENTAL DERMATOLOGY, 2023)
CRIS-Team WoS Importer:2023-06-02

High specificity THz metamaterial-based biosensor for label-free transcription factor detection in melanoma diagnostics - Richter, Merle; Loth, Yannik; Wigger, Anna Katharina; Nordhoff, Daniela; Rachinger, Nicole; Weisenstein, Christian; Boßerhoff, Anja Katrin; Bolívar, Peter Haring (Scientific Reports, 2023)
In this work, we present a promising diagnostic tool for melanoma diagnosis. With the proposed terahertz biosensor, it was possible to selectively and sensitively detect the early growth response protein 2, a transcription factor with an increased activity in melanoma cells, from a complex sample of cellular proteins. Fundamentally, the sensor belongs to the frequency selective surface type metamaterials and consists of a two-dimensional array of asymmetrically, doubly split ring resonator unit cells. The single elements are slits in a metallic layer and are complemented by an undercut etch. This allows a selective functionalization of the active area of the sensor and increases the sensitivity towards the target analyte. Hereby, specific detection of a defined transcription factor is feasible.
CRIS-Team Scopus Importer:2023-12-08

Histone deacetylase expressions in hepatocellular carcinoma and functional effects of histone deacetylase inhibitors on liver cancer cells in vitro - Freese, Kim; Seitz, Tatjana; Dietrich, Peter; Lee, Serene M.L.; Thasler, Wolfgang E.; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cancers, 2019)
Hepatocellular carcinoma (HCC) is a leading cause for deaths worldwide. Histone deacetylase (HDAC) inhibition (HDACi) is emerging as a promising therapeutic strategy. However, most pharmacological HDACi unselectively block different HDAC classes and their molecular mechanisms of action are only incompletely understood. The aim of this study was to systematically analyze expressions of different HDAC classes in HCC cells and tissues and to functionally analyze the effect of theHDACisuberanilohydroxamic acid (SAHA) and trichostatinA(TSA) on the tumorigenicity of HCC cells. The gene expression of all HDAC classes was significantly increased in human HCC cell lines (Hep3B, HepG2, PLC, HuH7) compared to primary human hepatocytes (PHH). The analysis of HCC patient data showed the increased expression of several HDACs in HCC tissues compared to non-tumorous liver. However, there was no unified picture of regulation in three different HCC patient datasets and we observed a strong variation in the gene expression of different HDACs in tumorous as well as non-tumorous liver. Still, there was a strong correlation in the expression of HDAC class IIa (HDAC4, 5, 7, 9) as well as HDAC2 and 8 (class I) and HDAC10 (class IIb) and HDAC11 (class IV) in HCC tissues of individual patients. This might indicate a common mechanism of the regulation of these HDACs in HCC. The Cancer Genome Atlas (TCGA) dataset analysis revealed that HDAC4, HDAC7 and HDAC9 as well as HDAC class I members HDAC1 and HDAC2 is significantly correlated with patient survival. Furthermore, we observed that SAHA and TSA reduced the proliferation, clonogenicity and migratory potential of HCC cells. SAHA but not TSA induced features of senescence in HCC cells. Additionally, HDACi enhanced the efficacy of sorafenib in killing sorafenib-susceptible cells. Moreover, HDACi reestablished sorafenib sensitivity in resistant HCC cells. In summary, HDACs are significantly but differently increased in HCC, which may be exploited to develop more targeted therapeutic approaches. HDACi affect different facets of the tumorigenicity of HCC cells and appears to be a promising therapeutic approach alone or in combination with sorafenib.
CRIS-Team Scopus Importer:2019-11-22
Keywords: Hepatocellular carcinoma; Histone deacetylase; Histone deacetylase inhibitor; Sorafenib

Hurdling senescence: hur breaks braf-induced senescence in melanocytes and supports melanoma growth - Liebig, Janika; Kuphal, Silke; Boßerhoff, Anja Katrin (Cancers, 2020)
In addition to genetic changes, post-transcriptional events strongly contribute to the progression of malignant tumors. The RNA-binding protein HuR (ELAVL1) is able to bind and stabilize a large group of target mRNAs, which contain AU-rich elements (ARE) in their 3′- untranslated region. We found HuR to be upregulated in malignant melanoma in vitro and in vivo, significantly correlating with progression in vivo. Additionally, we could show that miR-194-5p can regulate HuR expression level. HuR knockdown in melanoma cells led to the suppression of proliferation and the induction of cellular senescence. Interestingly, HuR overexpression was sufficient to inhibit senescence in BRAFV600E -expressing melanocytes and to force their growth. Here, MITF (Microphthalmia-associated transcription factor), a key player in suppressing senescence and an ARE containing transcript, is positively regulated by HuR. Our results show for the first time that the overexpression of HuR is an important part of the regulatory pathway in the development of malignant melanoma and functions as a switch to overcome oncogene-induced senescence and to support melanoma formation. These newly defined alterations may provide possibilities for innovative therapeutic approaches.
CRIS-Team Scopus Importer:2020-06-02
Keywords: HuR; Malignant melanoma; Microphthalmia-associated transcription factor; MITF; Oncogene induced senescence

Hypoferraemia during the early inflammatory response is dependent on tumour necrosis factor activity in a murine model of protracted peritonitis - Schubert, Thomas E. O.; Bosserhoff, Anja K.; Peyssonnaux, Carole; Echtenacher, Bernd; Knutson, Mitchell; Hofstaedter, Ferdinand; Maennel, Daniela N. (Molecular Medicine Reports, 2012)
On the grounds of clinical, in vitro and in vivo studies, tumour necrosis factor (TNF) is considered to be one of the inflammatory cytokines that contributes to to the generation of hypoferraemia and anaemia of inflammation (AI). We used a recently described murine model for AI and hypoferraemia, based on sublethal caecal ligation and puncture (CLP) with ensuing protracted peritonitis, to investigate the contribution of TNF to the generation of hypoferraemia. During the early inflammatory response to CLP, a marked decrease in serum iron concentration occurs within 8 h. To determine whether TNF contributes to the generation of hypoferraemia at this time point, we studied TNF-deficient mice and wild-type mice that underwent CLP. The serum iron concentration was decreased in wild-type mice whereas TNF-deficient mice maintained normal serum iron levels following CLP. Hypoferraemia in wild-type mice was accompanied by the downregulation of ferroportin 1 (Fp1) in macrophages. In the macrophages of TNF-deficient mice, Fp1 was not downregulated following CLP. The initial expression of hepcidin was detectable at the mRNA level but not at the protein level by immunohistochemistry in wild-type and TNF-deficient mice. Therefore, hepcidin does not appear to be involved in the regulation of early hypoferraemia. TNF appears to regulate the expression of Fp1 by transcriptional control. Our results demonstrate that TNF mediates hypoferraemia during the early inflammatory response by regulating the expression of Fp1 in macrophages.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Blood; Hypoferraemia; Mouse; Septic peritonitis; TNF

Hypoxia-Inducible Factor 1 Is an Inductor of Transcription Factor Activating Protein 2 Epsilon Expression during Chondrogenic Differentiation - Niebler, Stephan; Angele, Peter; Kujat, Richard; Boßerhoff, Anja Katrin (BioMed Research International, 2015)
The transcription factor AP-2? (activating enhancer-binding protein epsilon) is expressed in cartilage of humans and mice. However, knowledge about regulatory mechanisms influencing AP-2? expression is limited. Using quantitative real time PCR, we detected a significant increase in AP-2? mRNA expression comparing initial and late stages of chondrogenic differentiation processes in vitro and in vivo. Interestingly, in these samples the expression pattern of the prominent hypoxia marker gene angiopoietin-like 4 (Angptl4) strongly correlated with that of AP-2? suggesting that hypoxia might represent an external regulator of AP-2? expression in mammals. In order to show this, experiments directly targeting the activity of hypoxia-inducible factor-1 (HIF1), the complex mediating responses to oxygen deprivation, were performed. While the HIF1-activating compounds 2,2'-dipyridyl and desferrioxamine resulted in significantly enhanced mRNA concentration of AP-2?, siRNA against HIF1? led to a significantly reduced expression rate of AP-2?. Additionally, we detected a significant upregulation of the AP-2? mRNA level after oxygen deprivation. In sum, these different experimental approaches revealed a novel role for the HIF1 complex in the regulation of the AP-2? gene in cartilaginous cells and underlined the important role of hypoxia as an important external regulatory stimulus during chondrogenic differentiation modulating the expression of downstream transcription factors.
EVALuna2:4720

Identification of novel targets of miR-622 in hepatocellular carcinoma reveals common regulation of cooperating genes and outlines the oncogenic role of zinc finger CCHC-type containing 11 - Gaza, Anne; Fritz, Valerie; Malek, Lara; Wormser, Laura; Treiber, Nora; Danner, Johannes; Kremer, Andreas E.; Thasler, Wolfgang E.; Siebler, Jürgen; Meister, Gunter; Neurath, Markus F.; Hellerbrand, Claus; et al. (Neoplasia, 2021)
The poor prognosis of advanced hepatocellular carcinoma (HCC) is driven by diverse features including dysregulated microRNAs inducing drug resistance and stemness. Lin-28 homolog A (LIN28A) and its partner zinc finger CCHC-type containing 11 (ZCCHC11) cooperate in binding, oligouridylation and subsequent degradation of tumorsuppressive let-7 precursor microRNAs. Functionally, activation of LIN28A was recently shown to promote stemness and chemoresistance in HCC. However, the expression and regulation of LIN28A in HCC had been unclear. Moreover, the expression, regulation and function of ZCCHC11 in liver cancer remained elusive. In contrast to "one-microRNA-one-target" interactions, we identified common binding sites for miR-622 in both LIN28A and ZCCHC11, suggesting miR-622 to function as a superior pathway regulator. Applying comprehensive microRNA database screening, human hepatocytes and HCC cell lines, patient-derived tissue samples as well as "The Cancer Genome Atlas" (TCGA) patient cohorts, we demonstrated that loss of tumorsuppressive miR-622 mediates derepression and overexpression of LIN28A in HCC. Moreover, the cooperator of LIN28A, ZCCHC11, was newly identified as a prognostic and therapeutic target of miR-622 in liver cancer. Together, identification of novel miR-622 target genes revealed common regulation of cooperating genes and outlines the previously unknown oncogenic role of ZCCHC11 in liver cancer.
CRIS-Team Scopus Importer:2021-05-07
Keywords: drug resistance; HCC; Hepatocellular carcinoma; microRNA; ZCCHC11

Identification of oral squamous cell carcinoma markers MUC2 and SPRR1B downstream of TANGO - Sasahira, Tomonori; Kurihara-Shimomura, Miyako; Shimomura, Hiroyuki; Boßerhoff, Anja Katrin; Kirita, Tadaaki (Journal of Cancer Research and Clinical Oncology, 2021)
Purpose: Transport and Golgi organization protein 1 (TANGO) promotes angiogenesis and lymphangiogenesis in oral squamous cell carcinoma (OSCC). To elucidate the underlying mechanisms, this study aims to identify and characterize elements downstream of TANGO that mediate its involvement in OSCC. Methods: In this study, microarray analysis compared gene expression between control and TANGO-repressed HSC3 cells. Protein expression in 213 OSCC tissue samples was analyzed immunohistochemically. Results: TANGO repression decreased or increased expression of Mucin 20 (MUC20) and small proline-rich protein 1B (SPRR1B), respectively. MUC20 increased the growth and invasiveness of OSCC cells via altered matrix metalloproteinase (MMP)-2 and E-cadherin expression and c-met phosphorylation. MUC20 induced angiogenesis and lymphangiogenesis by activating vascular endothelial growth factors A and C. In well-differentiated OSCC, SPRR1B expression was high (P = 0.0091) and correlated with keratinization markers and promoted proliferation by inducing mitogen-activated protein kinase p38 phosphorylation. MUC20 expression correlated significantly with clinical stage (P = 0.0024), lymph node metastasis (P = 0.0036), and number of blood and lymph vessels (P < 0.0001). MUC20-expressing cases had a significantly worse prognosis than non-expressing cases (P < 0.0001). Conclusion: MUC20 and SPRR1B located downstream of TANGO may be useful molecular markers for OSCC.
CRIS-Team Scopus Importer:2021-03-12
Keywords: MUC20; Oral cancer; SPRR1B; TANGO

Immunologic and metabolic characteristics of HPV-negative and HPV-positive head and neck squamous cell carcinomas are strikingly different. - Krupar, Rosemarie; Robold, Katharina; Gaag, Doris; Spanier, Gerrit; Kreutz, Marina; Renner, Kathrin; Hellerbrand, Claus; Hofstaedter, Ferdinand; Bosserhoff, Anja Katrin (Virchows Archiv, 2014)
An HPV infection is involved in the etiology of about 25 % of head and neck squamous cell carcinomas (HNSCC). It has been postulated that a strong antitumoral immune response in HPV-positive tumors represents an important underlying mechanism for their good response to therapy. Recently, the Warburg phenomenon has returned to the center of attention because it affects antitumoral immune response and response to therapy. Accumulation of tumor cell-derived lactate inhibits cytotoxic T cells, as these, analogous to cancer cells, depend on glycolysis and lactate secretion for fulfillment of energy needs. Sparse information exists on the Warburg effect in HNSCC. This study aimed to characterize the metabolic and immunological features of HPV-negative and HPV-positive HNSCC. An immunohistochemical analysis of oropharyngeal carcinomas showed an enhanced antitumoral immune response (CD8/CD4 ratio) together with increased levels of proteins involved in transmembranous metabolite transportation (GLUT1 and CD147) and respiratory metabolism (COX5B) in HPV-positive tumors as compared to HPV-negative tumors. mRNA and Western blot analyses of an HPV-positive and HPV-negative HNSCC cell line revealed metabolic characteristics similar to the in vivo situation. Additionally, the HPV-negative cell line showed stronger extracellular lactate accumulation. In contrast, the HPV-positive cell line presented with better adaption to lactic acidosis suggesting an ability to metabolize lactate. Our results indicate that HPV-positive and HPV-negative carcinomas do not only differ in terms of tumor immune microenvironment, but also in terms of tumor metabolism, characterized by an increased glucose and respiratory metabolism together with decreased lactate accumulation in HPV-positive HNSCC. Therefore, targeting metabolic pathways could represent a promising adjunct in the therapy of HPV-positive HNSCC.
CRIS-Team Scopus Importer:2022-08-05

Immunometabolic Determinants of Chemoradiotherapy Response and Survival in Head and Neck Squamous Cell Carcinoma - Krupar, Rosemarie; Hautmann, Matthias G.; Pathak, Ravi R.; Varier, Indu; Mclaren, Cassandra; Gaag, Doris; Hellerbrand, Claus; Evert, Matthias; Laban, Simon; Idel, Christian; Sandulache, Vlad; Perner, Sven; et al. (American Journal of Pathology, 2017)
Tumor immune microenvironment and tumor metabolism are major determinants of chemoradiotherapy response. The interdependency and prognostic significance of specific immune and metabolic phenotypes in head and neck squamous cell carcinoma (HNSCC) were assessed and changes in reactive oxygen species were evaluated as a mechanism of treatment response in tumor spheroid/immunocyte co-cultures. Pretreatment tumor biopsies were immunohistochemically characterized in 73 HNSCC patients treated by definitive chemoradiotherapy and correlated with survival. The prognostic significance of CD8A, GLUT1, and COX5B gene expression was analyzed within The Cancer Genome Atlas database. HNSCC spheroids were co-cultured in vitro with peripheral blood mononuclear cells (PBMCs) in the presence of the glycolysis inhibitor 2-deoxyglucose and radiation treatment followed by PBMC chemotaxis determination via fluorescence microscopy. In the chemoradiotherapy-treated HNSCC cohort, mitochondrial-rich (COX5B) metabolism correlated with increased and glucose-dependent (GLUT1) metabolism with decreased intratumoral CD8/CD4 ratios. High CD8/CD4, together with mitochondrial-rich or glucose-independent metabolism, was associated with improved short-term survival. The Cancer Genome Atlas analysis confirmed that patients with a favorable immune and metabolic gene signature (high CD8A, high COX5B, low GLUT1) had improved short- and long-term survival. In vitro, 2-deoxyglucose and radiation synergistically up-regulated reactive oxygen species-dependent PBMC chemotaxis to HNSCC spheroids. These results suggest that glucose-independent tumor metabolism is associated with CD8-dominant antitumor immune infiltrate, and together, these contribute to improved chemoradiotherapy response in HNSCC.
EVALuna2:4758

Impact of CYLD on chromatin structure and histone methylation in malignant melanoma - Schott, Mandy; Kappelmann-Fenz, Melanie; Fischer, Stefan; Fernandez-Barrena, Maite G.; Pineda-Lucena, Antonio; Ávila, Matías A.; Kuphal, Silke; Boßerhoff, Anja Katrin (International Journal of Molecular Medicine, 2022)
The tumor suppressive role of CYLD lysine 63 deubiquitinase (CYLD) is known in melanoma. To the best of our knowledge, however, the precise mechanism under- lying the tumor suppressive function of CYLD has yet to be clarified. In the present study, a novel melanoma mouse model was generated, which revealed accelerated tumor growth in Cyld-knockout (Cyld-/-) compared with Cyld-wild-type (Cyld+/+) mice. To determine the underlying molecular mechanism, mutation analysis of primary tumor-derived cell lines from Cyld+/+and Cyld-/-mice was performed using RNA sequencing data. Variant calling revealed no common mutations in Cyld-/-compared with Cyld+/+cells. Thus, the epigenetic processes influencing development and progression of melanoma were investigated. Initial analysis of expres- sion pattern of known hypermethylated genes in melanoma (suppressor of cytokine signalling, methylthioadenosine phosphorylase, cadherin 1) in the presence or absence of 5'-Aza-deoxyctidine treatment revealed that CYLD does not play a key role in DNA methylation. Chromatin accessibility and histone H3 modification assay uncovered a role of CYLD in the formation of chromatin structure. Subsequent inhibitor experiments confirmed the effect of CYLD on H3K9me2 level associated with heterochromatin. Furthermore, enhanced H3K9 dimethylation in Cyld-/-melanoma cells was associated with upregulation of euchromatic histone lysine methyltrans- ferase 2 (EHMT2). Moreover, the specific inhibitor of EHMT2, CM272, resulted in decreased proliferation and relaxation of compact chromatin in Cyld-deficient melanoma cells. These results reveal a novel role of CYLD in histone methylation and chromatin packaging.
CRIS-Team Scopus Importer:2022-04-15
Keywords: chromatin accessibility; CYLD lysine 63 deubiquitinase; epigenetic; euchromatic histone lysine methyltransferase 2; H3K9me2; Melanoma

Impact of LIF (leukemia inhibitory factor) expression in malignant melanoma - Kuphal, Silke; Wallner, Susanne; Bosserhoff, Anja K. (Experimental and Molecular Pathology, 2013)
Leukemia inhibitory factor (LIF) signaling regulates cellular processes to maintain the self-renewal and pluripotency of embryonic stem (ES) cells. Independent of these capabilities, LIF was also identified to be responsible for cancer development and progression. However, its detailed cellular function in cancer remains unclear thus far. We found LIF to be expressed in melanoma cell lines of primary and metastatic origin and in melanoma tissue. We further elucidated stimuli that are responsible for the high expression levels of LIF. Interestingly, hypoxia, specifically through HIF-1α, is involved in regulating LIF.Furthermore, our data showed that the signaling of LIF was not mediated by the classically described pathway via STAT3, but rather through BMP4 and BMP7. We hypothesize that the co-expression of LIF and BMP is necessary for a de-differentiated cancer phenotype. Ancillary to BMP4 and BMP7, classical stem cell proteins, e.g., SOX2, NANOG, OCT3/4 and GBX2, are regulated by LIF. We therefore speculate that LIF can induce a typical "cancer stem cell"-like behavior, as the appropriate genes are regulated by LIF. Particularly, the expression of these genes has been proposed as a driving force for tumorigenesis and the initiation of metastasis. Notably, LIF has an important role not only for ES cells but also for cancer development. Melanoblast-related cells (MBrcs), which resemble the neural crest precursor cells of melanocytes, expressed LIF in minor amounts compared to normal human melanocytes. These data, along with the data that LIF is upregulated in melanoma cell lines compared to melanocytes, strongly indicate that LIF is important for the stabilization of the melanoma phenotype.To elucidate the role of LIF in cellular melanoma behavior, we analyzed proliferation, attachment, migration and colony formation after silencing LIF by siRNA, and found all four characteristics restricted. In summary, we can show that LIF is an important factor in melanoma progression. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: LIF; Melanoma; Stem cell marker

Importance of the Amino Acid Transporter SNAT1/SLC38A1 in malignant Melanoma - Lörentz, Sandra; Böhme-Schäfer, Ines; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Importance of the RNA Binding Protein Hu-antigen R in malignant Melanoma - Liebig, Janika; Boßerhoff, Anja Katrin (2018)
EVALuna2:203602

Increased KGF expression promotes fibroblast activation in a double paracrine manner resulting in cutaneous fibrosis - Canady, Johanna; Arndt, Stephanie; Karrer, Sigrid; Bosserhoff, Anja Katrin (Journal of Investigative Dermatology, 2013)
Fibrotic disorders of the skin share the characteristic features of increased production and deposition of extracellular matrix components by activated fibroblasts. Their clinical course ranges from benign with localized cutaneous involvement to a systemic, life-threatening disease. The molecular cause for fibroblast activation remains unknown, yet epithelial-mesenchymal interactions draw mounting attention in the research field of fibrogenesis. We examined keratinocyte growth factor (KGF), a crucial molecule in fibroblast-keratinocyte cross talk, exemplarily in keloid and scleroderma, and found its expression to be increased in disease-derived fibroblasts and tissues compared with healthy controls. This overexpression induces fibroblast activation through a double paracrine mode of action. Upon KGF stimulation, the keratinocytes produced and secreted OSM (oncostatin M). Fibroblasts were in turn activated by OSM reacting with the increased expression of collagen type I-α1, fibroblast activation protein, and enhanced migration. The observed increase in collagen expression and fibroblast migration can be traced back to OSM-regulated STAT3 phosphorylation, leading to enhanced urokinase plasminogen activator expression. Hence, we propose a causative loop in the pathogenesis of fibrosing disorders of the skin mediated by the overexpression of KGF in mesenchymal cells. © 2013 The Society for Investigative Dermatology.
CRIS-Team Scopus Importer:2022-08-05

Induction of exportin-5 expression during melanoma development supports the cellular behavior of human malignant melanoma cells - Ott, Corinna; Linck, Lisa; Kremmer, Elisabeth; Meister, Gunter; Boßerhoff, Anja Katrin (Oncotarget, 2016)
Regulation of gene expression via microRNAs is known to promote the development of many types of cancer. In melanoma, miRNAs are globally up-regulated, and alterations of miRNA-processing enzymes have already been identified. However, mis-regulation of miRNA transport has not been analyzed in melanoma yet. We hypothesized that alterations in miRNA transport disrupt miRNA processing. Therefore, we investigated whether the pre-miRNA transporter Exportin-5 (XPO5) was involved in altered miRNA maturation and functional consequences in melanoma. We found that XPO5 is significantly over-expressed in melanoma compared with melanocytes. We showed enhanced XPO5 mRNA stability in melanoma cell lines which likely contributes to up-regulated XPO5 protein expression. In addition, we identified MEK signaling as a regulator of XPO5 expression in melanoma. Knockdown of XPO5 expression in melanoma cells led to decreased mature miRNA levels and drastic functional changes. Our data revealed that aberrant XPO5 expression is important for the maturation of miRNAs and the malignant behavior of melanoma cells. We suggest that the high abundance of XPO5 in melanoma leads to enhanced survival, proliferation and metastasis and thereby supports the aggressiveness of melanoma.
EVALuna2:4732

Inhibition of peptidyl-prolyl isomerase (PIN1) and BRAF signaling to target melanoma - Braun, Christina; Schneider, Nadja; Pei, Dehua; Boßerhoff, Anja Katrin; Kuphal, Silke (American Journal of Translational Research, 2019)
PIN1 is a phosphorylation-dependent peptidyl-prolyl cis/trans isomerase, overexpressed in many cancers, including melanoma. Our immunohistochemistry data of melanoma patient tissue underline the up-regulation of PIN1 in metastases. Here, we demonstrate important functions of PIN1 and its selective and cell permeable inhibitor 37 for the treatment of melanoma. To analyze its possible role in oncogenesis and as a therapeutic target, we first suppressed PIN1 expression by a siRNA pool. PIN1 knockdown potently inhibited melanoma cell proliferation and vascular mimicry by influencing several cancer-relevant pathways. Furthermore, inhibitor 37 inhibited cell growth in melanoma and induced apoptosis. Normal healthy melanocytes, keratinocytes and fibroblasts are not affected by the PIN1 inhibitor 37. Combinatorial treatment of melanoma cells is with Vemurafenib as a common therapeutic option for BRAF-mutated melanoma and inhibitor 37 resulted in a strong, synergistic effect on apoptosis of melanoma cell lines. In summary, targeting PIN1 offers a promising therapeutic approach to simultaneously downregulate multiple cancer-driving pathways in cancer.
CRIS-Team WoS Importer:2019-08-09

Investigation of toxicity and mutagenicity of cold atmospheric argon plasma - Maisch, T.; Boßerhoff, Anja Katrin; Unger, P.; Heider, J.; Shimizu, T.; Zimmermann, J. L.; Morfill, G. E.; Landthaler, M.; Karrer, S. (ENVIRON MOL MUTAGEN, 2017)
Cold atmospheric argon plasma is recognized as a new contact free approach for the decrease of bacterial load on chronic wounds in patients. So far very limited data are available on its toxicity and mutagenicity on eukaryotic cells. Thus, the toxic/mutagenic potential of cold atmospheric argon plasma using the MicroPlaSter ?(®) , which has been used efficiently in humans treating chronic and acute wounds, was investigated using the XTT assay in keratinocytes and fibroblasts and the HGPRT (hypoxanthine guanine phosphoribosyl transferase) assay with V79 Chinese hamster cells. The tested clinical parameter of a 2 min cold atmospheric argon plasma treatment revealed no relevant toxicity on keratinocytes (viability: 76% ± 0.17%) and on fibroblasts (viability: 81.8 ± 0.10) after 72 hr as compared to the untreated controls. No mutagenicity was detected in the HGPRT assay with V79 cells even after repetitive CAP treatments of 2-10 min every 24 hr for up to 5 days. In contrast, UV-C irradiation of V79 cells, used as a positive control in the HGPRT test, led to DNA damage and mutagenic effects. Our findings indicate that cold atmospheric plasma using the MicroPlaSter ?(®) shows negligible effects on keratinocytes and fibroblasts but no mutagenic potential in the HGPRT assay, indicating a new contact free safe technology. Environ. Mol. Mutagen. 58:172-177, 2017. © 2017 Wiley Periodicals, Inc.
EVALuna2:4751

In Vitro Safety Study on the Use of Cold Atmospheric Plasma in the Upper Respiratory Tract - Karrer, Sigrid; Unger, Petra; Gruber, Michael; Gebhardt, Lisa; Schober, Robert; Berneburg, Mark; Boßerhoff, Anja Katrin; Arndt, Stephanie (Cells, 2024)
Cold atmospheric plasma (CAP) devices generate reactive oxygen and nitrogen species, have antimicrobial and antiviral properties, but also affect the molecular and cellular mechanisms of eukaryotic cells. The aim of this study is to investigate CAP treatment in the upper respiratory tract (URT) to reduce the incidence of ventilator-associated bacterial pneumonia (especially superinfections with multi-resistant pathogens) or viral infections (e.g., COVID-19). For this purpose, the surface-microdischarge-based plasma intensive care (PIC) device was developed by terraplasma medical GmbH. This study analyzes the safety aspects using in vitro assays and molecular characterization of human oral keratinocytes (hOK), human bronchial–tracheal epithelial cells (hBTE), and human lung fibroblasts (hLF). A 5 min CAP treatment with the PIC device at the “throat” and “subglottis” positions in the URT model did not show any significant differences from the untreated control (ctrl.) and the corresponding pressurized air (PA) treatment in terms of cell morphology, viability, apoptosis, DNA damage, and migration. However, pro-inflammatory cytokines (MCP-1, IL-6, and TNFα) were induced in hBTE and hOK cells and profibrotic molecules (collagen-I, FKBP10, and αSMA) in hLF at the mRNA level. The use of CAP in the oropharynx may make an important contribution to the recovery of intensive care patients. The results indicate that a 5 min CAP treatment in the URT with the PIC device does not cause any cell damage. The extent to which immune cell activation is induced and whether it has long-term effects on the organism need to be carefully examined in follow-up studies in vivo.
CRIS-Team Scopus Importer:2024-09-20
Keywords: cold atmospheric plasma (CAP); human bronchial–tracheal epithelial cells (hBTE); human lung fibroblasts (hLF); human oral keratinocytes (hOK); plasma intensive care (PIC); pressurized air (PA); upper respiratory tract (URT)

Iso-alpha acids from hops (Humulus lupulus) inhibit hepatic steatosis, inflammation, and fibrosis - Mahli, Abdo; Koch, Andreas; Fresse, Kim; Schiergens, Tobias; Thasler, Wolfgang Erwin; Schoenberger, Christina; Bergheim, Ina; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Laboratory Investigation, 2018)
Non-alcoholic fatty liver disease (NAFLD) is considered to be the hepatic manifestation of the metabolic syndrome. Iso-alpha acids (IAAs), hop-derived bitter compounds in beer, have been shown to beneficially affect different components of the metabolic syndrome such as insulin resistance and dyslipidemia. However, IAAs have not yet been studied in the context of chronic liver disease. Here we analyzed the effect of IAA on the pathogenesis of NAFLD. Once, we applied IAA to mice in combination with a NAFLD-inducing Western-type diet (WTD), and observed that IAA significantly inhibited WTD-induced body weight gain, glucose intolerance, and hepatic steatosis. Fitting to this, IAA dose-dependently inhibited cellular lipid accumulation in primary human hepatocytes (PHH) in vitro. Reduced expression of PPAR-gamma and key enzymes of lipid synthesis as well as increased expression of PPAR-alpha, indicative for increased lipid combustion, were identified as underlying mechanisms of reduced hepatocellular steatosis in vitro and in vivo. Analysis of hepatic HMOX1 expression indicated reduced oxidative stress in IAA-treated mice, which was paralleled by reduced activation of the JNK pathway and pro-inflammatory gene expression and immune cell infiltration. Furthermore, IAA reduced hepatic stellate cell (HSC) activation and pro-fibrogenic gene expression. Similarly, IAA also dose-dependently reduced oxidative stress and JNK activation in steatotic PHH, inhibited HSC activation, and reduced proliferation and pro-fibrogenic gene expression in already activated HSC in vitro. In conclusion, IAAs inhibit different pathophysiological steps of disease progression in NAFLD. Together with previous studies, which demonstrated the safety of even long-term application of IAA in humans, our data suggest IAA as promising therapeutic agent for the prevention and treatment of (non)alcoholic (fatty) liver disease.
EVALuna2:35807

Knockdown of Lamin B1 and the Corresponding Lamin B Receptor Leads to Changes in Heterochromatin State and Senescence Induction in Malignant Melanoma - Lämmerhirt, Lisa; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Pommer, Michaela; Zimmermann, Tom; Kluge, Viola; Matthies, Alexander Oliver; Kuphal, Silke; Boßerhoff, Anja Katrin (Cells, 2022)
Modifications in nuclear structures of cells are implicated in several diseases including cancer. They result in changes in nuclear activity, structural dynamics and cell signalling. However, the role of the nuclear lamina and related proteins in malignant melanoma is still unknown. Its molecular characterisation might lead to a deeper understanding and the development of new therapy approaches. In this study, we analysed the functional effects of dysregulated nuclear lamin B1 (LMNB1) and its nuclear receptor (LBR). According to their cellular localisation and function, we revealed that these genes are crucially involved in nuclear processes like chromatin organisation. RNA sequencing and differential gene expression analysis after knockdown of LMNB1 and LBR revealed their implication in important cellular processes driving ER stress leading to senescence and changes in chromatin state, which were also experimentally validated. We determined that melanoma cells need both molecules independently to prevent senescence. Hence, downregulation of both molecules in a BRAFV600E melanocytic senescence model as well as in etoposide-treated melanoma cells indicates both as potential senescence markers in melanoma. Our findings suggest that LMNB1 and LBR influence senescence and affect nuclear processes like chromatin condensation and thus are functionally relevant for melanoma progression.
CRIS-Team Scopus Importer:2022-08-05
Keywords: chromatin state; heterochromatin foci; LBR; LMNB1; melanoma; nuclear lamina; senescence

Lactate-modulated induction of THBS-1 activates Transforming growth factor (TGF)-beta2 and migration of glioma cells in vitro - Seliger, Corinna; Leukel, Petra; Moeckel, Sylvia; Jachnik, Birgit; Lottaz, Claudio; Kreutz, Marina; Brawanski, Alexander; Proescholdt, Martin; Bogdahn, Ulrich; Vollmann-Zwerenz, Arabel; Hau, Peter; Bosserhoff, Anja Katrin (PLoS ONE, 2013)
Background: An important phenomenon observed in glioma metabolism is increased aerobic glycolysis in tumor cells, which is generally referred to as the Warburg effect. Transforming growth factor (TGF)-beta2, which we previously showed to be induced by lactic acid, is a key pathophysiological factor in glioblastoma, leading to increased invasion and severe local immunosuppression after proteolytic cleavage from its latency associated peptide. In this study we tested the hypothesis, that lactate regulates TGF-beta2 expression and glioma cell migration via induction of Thrombospondin-1 (THBS-1), a TGF-beta activating protein. Methods: Lactate levels were reduced by knockdown of LDH-A using specific small interfering RNA (siRNA) and competitive inhibition of LDH-A by sodium oxamate. Knockdown of THBS-1 was performed using specific siRNA. Western Blot, qRT-PCR, and ELISA were used to investigate expression levels of LDH-A, LDH-B, TGF-beta2 and THBS-1. Migration of cells was examined by Spheroid, Scratch and Boyden Chamber assays. Results: Knockdown of LDH-A with subsequent decrease of lactate concentration leads to reduced levels of THBS-1 and TGF-beta2 in glioma cells. Lactate addition increases THBS-1 protein, leading to increased activation of TGF-beta2. Inhibition of THBS-1 reduces TGF-beta2 protein and migration of glioma cells. Addition of synthetic THBS-1 can rescue reduced TGF-beta2 protein levels and glioma cell migration in siLDH-A treated cells. Conclusion: We define a regulatory cascade between lactate, THBS-1 and TGF-beta2, leading to enhanced migration of glioma cells. Our results demonstrate a specific interaction between tumor metabolism and migration and provide a better understanding of the mechanisms underlying glioma cell invasion. © 2013 Seliger et al.
CRIS-Team Scopus Importer:2022-08-05

Learning from Embryogenesis-A Comparative Expression Analysis in Melanoblast Differentiation and Tumorigenesis Reveals miRNAs Driving Melanoma Development - Linck-Paulus, Lisa; Lämmerhirt, Lisa; Voeller, Daniel; Meyer, Katharina; Engelmann, Julia C.; Spang, Rainer; Eichner, Norbert; Meister, Gunter; Kuphal, Silke; Boßerhoff, Anja Katrin (Journal of Clinical Medicine, 2021)
Malignant melanoma is one of the most dangerous tumor types due to its high metastasis rates and a steadily increasing incidence. During tumorigenesis, the molecular processes of embryonic development, exemplified by epithelial-mesenchymal transition (EMT), are often reactivated. For melanoma development, the exact molecular differences between melanoblasts, melanocytes, and melanoma cells are not completely understood. In this study, we aimed to identify microRNAs (miRNAs) that promote melanoma tumorigenesis and progression, based on an in vitro model of normal human epidermal melanocyte (NHEM) de-differentiation into melanoblast-like cells (MBrCs). Using miRNA-sequencing and differential expression analysis, we demonstrated in this study that a majority of miRNAs have an almost equal expression level in NHEMs and MBrCs but are significantly differentially regulated in primary tumor- and metastasis-derived melanoma cell lines. Further, a target gene analysis of strongly regulated but functionally unknown miRNAs yielded the implication of those miRNAs in many important cellular pathways driving malignancy. We hypothesize that many of the miRNAs discovered in our study are key drivers of melanoma development as they account for the tumorigenic potential that differentiates melanoma cells from proliferating or migrating embryonic cells.
CRIS-Team WoS Importer:2021-06-25

Loss of CYLD accelerates melanoma development and progression in the Tg(Grm1) melanoma mouse model - de Jel, Miriam Martha; Schott, Mandy; Lamm, Susanne; Neuhuber, Winfried; Kuphal, Silke; Boßerhoff, Anja Katrin (Oncogenesis, 2019)
The deubiquitinase cylindromatosis (CYLD) is a well-known tumor suppressor, found to be down regulated in many cancer types including breast cancer, colon carcinoma and malignant melanoma. CYLD is suppressed in human melanoma cells by the transcriptional repressor SNAIL1 leading to an increase of their proliferative, invasive and migratory potential. To gain additional insights into the distinct function of this tumor suppressor gene a new mouse model Tg(Grm1)Cyld−/− was generated. Herewith, we demonstrate that Cyld-deficiency leads to earlier melanoma onset and accelerated tumor growth and metastasis in the GRM1 melanoma mouse model. First, RNA sequencing data revealed a potential role of CYLD in the regulation of genes involved in proliferation, migration and angiogenesis. Experiments using cell lines generated from both primary and metastatic melanoma tissue of Tg(Grm1) Cyld−/− and Tg(Grm1) Cyld+/+ mice confirmed that loss of CYLD enhances the proliferative and migratory potential, as well as the clonogenicity in vitro. Moreover, we could show that Cyld-knockout leads to increased vasculogenic mimicry and enhanced (lymph-) angiogenesis shown by tube formation assays, immunohistochemistry and mRNA expression analyses. In summary, our findings reveal new functional aspects of CYLD in the process of (lymph-) angiogenesis and demonstrate its importance in the early process of melanoma progression.
CRIS-Team Scopus Importer:2019-10-18

Loss of CYLD promotes melanoma progression - de Jel, Miriam Martha; Schiffner, S.; Kuphal, Silke; Boßerhoff, Anja Katrin (2016)
EVALuna2:4737

Loss of gene information: Discrepancies between rna sequencing, cdna microarray, and qrt-pcr - Rachinger, Nicole; Fischer, Stefan; Böhme, Ines; Linck-Paulus, Lisa; Kuphal, Silke; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin (International Journal of Molecular Sciences, 2021)
Molecular analyses of normal and diseased cells give insight into changes in gene expression and help in understanding the background of pathophysiological processes. Years after cDNA microarrays were established in research, RNA sequencing (RNA-seq) became a key method of quan-titatively measuring the transcriptome. In this study, we compared the detection of genes by each of the transcriptome analysis methods: cDNA array, quantitative RT-PCR, and RNA-seq. As expected, we found differences in the gene expression profiles of the aforementioned techniques. Here, we present selected genes that exemplarily demonstrate the observed differences and calculations to reveal that a strong RNA secondary structure, as well as sample preparation, can affect RNA-seq. In summary, this study addresses an important issue with a strong impact on gene expression analysis in general. Therefore, we suggest that these findings need to be considered when dealing with data from transcriptome analyses.
CRIS-Team Scopus Importer:2021-09-10
Keywords: CDNA microarray; Free energy of the RNA secondary structure; QRT-PCR; RNA sequencing; Secondary struc-ture; Transcriptome analysis

Loss of miR-101-3p in melanoma stabilizes genomic integrity, leading to cell death prevention - Lämmerhirt, Lisa; Kappelmann-Fenzl, Melanie; Fischer, Stefan; Meier, Paula; Stäbler, Sebastian; Kuphal, Silke; Boßerhoff, Anja Katrin (Cellular & Molecular Biology Letters, 2024)
Malignant melanoma remains the most lethal form of skin cancer, exhibiting poor prognosis after forming distant metastasis. Owing to their potential tumor-suppressive properties by regulating oncogenes and tumor suppressor genes, microRNAs are important player in melanoma development and progression. We defined the loss of miR-101-3p expression in melanoma cells compared with melanocytes and melanoblast-related cells as an early event in tumor development and aimed to understand the tumor suppressive role of miR-101-3p and its regulation of important cellular processes. Reexpression of miR-101-3p resulted in inhibition of proliferation, increase in DNA damage, and induction of apoptosis. We further determined the nuclear structure protein Lamin B1, which influences nuclear processes and heterochromatin structure, ATRX, CASP3, and PARP as an important direct target of miR-101-3p. RNA sequencing and differential gene expression analysis after miR-101-3p reexpression supported our findings and the importance of loss of mir-101-3p for melanoma progression. The validated functional effects are related to genomic instability, as recent studies suggest miRNAs plays a key role in mediating this cellular process. Therefore, we concluded that miR-101-3p reexpression increases the genomic instability, leading to irreversible DNA damage, which leads to apoptosis induction. Our findings suggest that the loss of miR-101-3p in melanoma serves as an early event in melanoma progression by influencing the genomic integrity to maintain the increased bioenergetic demand.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Apoptosis; DNA damage; Genomic integrity; Melanoma; miR-101-3p; miRNA; RNA-seq

Loss of T-cadherin (CDH-13) regulates AKT signaling and desensitizes cells to apoptosis in melanoma - Bosserhoff, Anja K.; Ellmann, Lisa; Quast, Annika S.; Eberle, Juergen; Boyle, Glen M.; Kuphal, Silke (Molecular Carcinogenesis, 2014)
An understanding of signaling pathways is a basic requirement for the treatment of melanoma. Currently, kinases are at the center of melanoma therapies. According to our research, additional alternative molecules are equally important for development of melanoma. In this regard, cancer progression is, among other factors, driven by an altered adhesion via cadherins. For instance, the de-regulated expression of the adhesion molecule T-cadherin is found in various cancer types, including melanoma, and influences migration and invasion. T-cadherin is thought to affect cellular function largely through its signaling and not its adhesion properties because the molecule is anchored into the cell membrane by a glycosylphosphatidylinositol (GPI) moiety. However, detailed knowledge about the consequences of the loss of T-cadherin in melanoma is currently lacking. For this reason, we were interested in assessing which signaling pathways are initiated by T-cadherin. The tumor growth of subcutaneously injected T-cadherin-positive melanoma cells was diminished compared with T-cadherin-negative cells in nude mice. The difference in tumor volume was not due to decreased proliferation but rather due to increased apoptosis. After the expression of T-cadherin was induced, we detected V-AKT murine thymoma viral oncogene homolog (AKT) and FoxO3a hypophosphorylation accompanied by the downregulation of the antiapoptotic molecules BCL-2, BCL-x and Clusterin. Furthermore, we detected a diminished transcriptional activity of CREB and AP-1. We demonstrated that T-cadherin functions as a pro-apoptotic tumor suppressor that antagonizes AKT/CREB/AP-1/FoxO3a signaling, whereas NFκB, TCF/LEF and mTOR are not part of the T-cadherin signaling pathway. Notably, we found that the restoration of T-cadherin in melanoma cells causes sensitization to apoptosis induced by CD95/Fas antibody CH-11. © 2013 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2022-08-05
Keywords: AKT; AP-1; Cell adhesion; CREB; FoxO3a

MAGOH and MAGOHB Knockdown in Melanoma Cells Decreases Nonsense-Mediated Decay Activity and Promotes Apoptosis via Upregulation of GADD45A - Söderberg, Agnes; Meißgeier, Tina; Boßerhoff, Anja Katrin; Linck-Paulus, Lisa (Cells, 2022)
Cutaneous malignant melanoma is a highly proliferative and aggressive skin cancer with a steadily increasing incidence and a low long-term survival rate after metastatic progression. The protein MAGOH and its highly identical homologue MAGOHB are core components of the exon junction complex (EJC), which regulates splicing, stability and translation of mRNAs. The EJC, and especially MAGOH, has been shown to be involved in the development and progression of several cancers. In melanoma, the expression and function of both homologues remain essentially unexplored. This study identifies high MAGOH and MAGOHB protein expression in cutaneous melanoma cell lines and patient derived tissue samples. An siRNA-mediated knockdown of MAGOH significantly inhibits melanoma cell proliferation. The loss of MAGOH does not affect cell cycle progression, but induces apoptosis, an effect that is enhanced by a simultaneous knockdown of MAGOH and MAGOHB. MAGOH and MAGOHB do not influence the expression of the pro-apoptotic protein Bcl-XS or exon skipping. However, the knockdown of MAGOH and MAGOHB strongly decreases nonsense-mediated decay (NMD) activity, leading to an upregulation of the pro-apoptotic protein GADD45A. In conclusion, simultaneous inhibition of MAGOH and MAGOHB expression substantially affects cell survival, indicating both MAGOH homologues as promising new targets for the treatment of melanoma.
CRIS-Team Scopus Importer:2022-12-23
Keywords: exon junction complex; GADD45A; MAGOH; melanoma; nonsense-mediated decay

Mast cell chymase promotes angiogenesis and lymphangiogenesis mediated by activation of melanoma inhibitory activity gene family members in oral squamous cell carcinoma - Kurihara–Shimomura, Miyako; Sasahira, Tomonori; Shimomura, Hiroyuki; Boßerhoff, Anja Katrin; Kirita, Tadaaki (International Journal of Oncology, 2020)
Mast cells (MCs) are present in the tumor stroma, and MCs that express the mast cell–specific proteases tryptase and chymase (MCTC) exhibit several tumor–related functions. It was previously reported that melanoma inhibitory activity (MIA) gene family members, including MIA, MIA2, and transport and Golgi organization protein 1 (TANGO), possess oncogenic functions in oral squamous cell carcinoma (OSCC). However, the relationships between MCTC, and clinicopathological characteristics and activation of the MIA gene family in OSCC remain unknown. In the present study, the functional roles of MCTC in patients with OSCC were investigated using immunohistochemistry and reverse transcription–quantitative PCR. In addition, the effects of extracellular chymase on oral cancer cells were examined. In patients with OSCC, MCTC density was significantly affected by tumor progression and nodal metastasis, and was correlated with vessel density. MCTC density was also correlated with MIA and MIA2 expression. In OSCC cells, extracellular chymase promoted the secretion of vascular endothelial growth factor family proteins, and the transmigration and adhesion of HSC3 cells to endothelial cells; knockdown of MIA, MIA2 and TANGO attenuated these effects. The present findings indicated that MCTC act as tumor–progressive factors in OSCC via the activation and secretion of MIA and MIA2, and the induction of angiogenesis and lymphangiogenesis.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Chymase; Mast cell; MIA gene family; Oral cancer

Melanoma development: Molecular biology, genetics and clinical application - Boßerhoff, Anja Katrin (Springer International Publishing, 2017)
This book focuses on malignant melanoma, discussing the current state of scientific knowledge and providing insights into the underlying basic mechanisms, the molecular changes, genetics and genomics. Human Melanoma is a dangerous type of skin cancer affecting an increasing population, and a better understanding of its development will help in finding sophisticated targeted therapies. The second revised edition features the latest research findings and offers updates on the latest advances and potential novel melanoma therapies. It is a valuable resource for researchers and clinicians working in the fields of melanoma, cancer research and therapy as well as dermatology.
CRIS-Team Scopus Importer:2022-08-05

Melanoma inhibitory activity in melanoma diagnostics and therapy - a small protein is looming large - Riechers, Alexander; Bosserhoff, Anja Katrin (Experimental Dermatology, 2014)
Malignant melanoma is a highly aggressive cancer with a very poor prognosis after the onset of metastasis. We have previously demonstrated that the protein melanoma inhibitory activity (MIA) is involved in the metastasis of and immunosuppression in malignant melanoma. Recently, we further established MIA as a therapeutic target to inhibit metastatic spread in malignant melanoma. We could show that an inhibition of MIA by a synthetic peptide decreased both the number of metastases as well as immunosuppression in a murine model of malignant melanoma. To control recurrence after surgical resection of a primary lesion, it is paramount to have diagnostic tools available that can detect a relapse due to the strong metastatic potential of melanoma. This follow-up is maintained with periodic re-examinations. Due to high cost and the associated radiation exposure, radiology examinations are avoided if possible. The analysis of prognostic markers in patient serum is therefore attractive. In this review, we focus on the quantitative analysis of the MIA protein as a prognostic tool because it has proven to be a useful serum marker for documenting disease progression of malignant melanoma. The MIA quantification assay itself is readily performed using an ELISA kit and common laboratory equipment. Because analysing MIA serum levels in combination with other established markers such as S100B improves their prognostic value, we feel that the quantification of MIA in the serum, among other markers, should be performed as a general standard of care in patients at risk of developing metastatic melanoma. © 2013 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.
CRIS-Team Scopus Importer:2022-08-05

Melanoma inhibitory activity promotes melanoma development through activation of YBX1 - Schmid, Rainer; Meyer, Katharina; Spang, Rainer; Schittek, Birgit; Bosserhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2013)
Summary: Melanoma inhibitory activity (MIA), a small soluble secreted protein, is functionally important for progression of malignant melanoma. We recently revealed that p54nrb acts as a mediator of MIA action. In this study, we characterize the transcriptional regulation of p54nrb by MIA to explain MIA's molecular action. We identified one highly conserved region in the p54nrb promoter that is necessary and sufficient for MIA-dependent activation. Functional promoter analysis identified the transcription factor YBX1 as the mediator of MIA activation of p54nrb transcription. We screened the genome for further potential MIA-regulated genes carrying the element in their promoter regions. Integrating our sequence data with expression data from human melanomas identified a list of 23 potential MIA-YBX1 targets in melanomas. In summary, we present for the first time effects of MIA on transcriptional regulation. Uncovering new potential downstream effectors working via activation of YBX1 supports the important role of MIA in melanoma. © 2013 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Melanoma progression; MIA; P54; Target gene prediction

Melanoma sponge on pigmentation gene to reduce tumour-suppressive microRNAs - Dietrich, Peter; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2017)
EVALuna2:4760

Membrane Transporters and Channels in Melanoma - Böhme-Schäfer, Ines; Schoenherr, Roland; Eberle, Juergen; Boßerhoff, Anja Katrin (Reviews of Physiology Biochemistry and Pharmacology, 2021)
Recent research has revealed that ion channels and transporters can be important players in tumor development, progression, and therapy resistance in melanoma. For example, members of the ABC family were shown to support cancer stemness-like features in melanoma cells, while several members of the TRP channel family were reported to act as tumor suppressors.
CRIS-Team WoS Importer:2022-03-18
Keywords: Apoptosis; Cell proliferation; Channels; Melanocyte; Melanoma; Metastasis; Mutation; Nevus; Prognosis; Transporters; Tumor development; Tumor progression

MIA - A new target protein for malignant melanoma therapy - Schmidt, Jennifer; Riechers, Alexander; Bosserhoff, Anja Katrin (Histology and Histopathology, 2013)
Malignant melanoma, a malignancy of pigment producing cells, causes the greatest number of skin cancer-related deaths worldwide. The tumor is characterized by its aggressive phenotype and can metastasize at very early stages of the disease. Since metastatic lesions are usually characterized by an intrinsic resistance to standard radiation and chemotherapy, the prognosis of this tumor remains very poor in advanced stages. Melanoma inhibitory activity (MIA), an 11 kDa protein expressed and secreted by melanoma cells after their malignant transformation, is known to play a key role in melanoma development, progression and tumor cell invasion. After its secretion, which is restricted to the rear pole of migrating cells, MIA protein directly interacts with cell adhesion receptors and extracellular matrix molecules. By this mechanism, MIA protein actively facilitates focal cell detachment from surrounding structures at the cell rear and strongly promotes tumor cell invasion and formation of metastases. It has further been demonstrated that MIA contributes to immunosuppression frequently seen in malignant melanomas by binding to integrin α4ß1 expressed by leukocytes and thus inhibiting cellular antitumor immune response. Analyses at the molecular level revealed that MIA protein reaches functional activity by self assembly. Functional inactivation of MIA protein by dodecapeptides that directly bind to the dimerization interface leads to a strongly reduced tumor cell invasion in an in vivo mouse melanoma model. The molecular understanding of the contribution of MIA protein to formation of metastases provides an excellent starting point for the development of a new strategy in malignant melanoma therapy.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Immunosuppression; Malignant melanoma; Metastasis; MIA; Peptide inhibitor

MIA/CD-RAP Regulates MMP13 and Is a Potential New Disease-Modifying Target for Osteoarthritis Therapy - Stäbler, Sebastian; Lichtblau, Adrian; Gurbiel, Slavyana; Schubert, Thomas; Riechers, Alexander; Rottensteiner-Brandl, Ulrike; Boßerhoff, Anja Katrin (Cells, 2023)
Melanoma inhibitory activity/cartilage-derived retinoicacid-sensitive protein (MIA/CD-RAP) is a protein expressed and secreted by chondrocytes and cartilaginous tissues. MIA/CD-RAP-deficient mice develop milder osteoarthritis than wildtype mice. In this study, we investigated MIA/CD-RAP downstream targets to explain this reduced disease development. As a possible mediator, we could detect matrix metalloproteinase 13 (MMP13), and the influence of MIA/CD-RAP on MMP13 regulation was analyzed in vitro using SW1353 chondrosarcoma cells and primary chondrocytes. The femoral head cartilage of WT and MIA/CD-RAP −/− mice were cultured ex vivo to further investigate MMP13 activity. Finally, osteoarthritis was surgically induced via DMM in C57BL/6 mice, and the animals were treated with an MIA/CD-RAP inhibitory peptide by subcutaneously implanted pellets. MMP13 was regulated by MIA/CD-RAP in SW1353 cells, and MIA/CD-RAP −/− murine chondrocytes showed less expression of MMP13. Further, IL-1β-treated MIA/CD-RAP −/− chondrocytes displayed less MMP13 expression and activity. Additionally, MIA/CD-RAP-deficient ex vivo cultured cartilage explants showed less MMP13 activity as well as reduced cartilage degradation. The mice treated with the MIA/CD-RAP inhibitory peptide showed less osteoarthritis development. Our findings revealed MIA/CD-RAP as a new regulator of MMP13 and highlighted its role as a potential new target for osteoarthritis therapy.
CRIS-Team Scopus Importer:2023-02-03
Keywords: MIA/CD-RAP; MMP13; osteoarthritis; signaling; therapeutic

MicroRNA-622 is a novel mediator of tumorigenicity in melanoma by targeting Kirsten rat sarcoma - Dietrich, Peter; Kuphal, Silke; Spruss, Thilo; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2018)
The network of molecular players is similar when comparing neural crest-derived, actively migrating melanoblasts to melanoma cells. However, melanoblasts are sensitive to differentiation-initiating signals at their target site (epidermis), while melanoma cells maintain migratory and undifferentiated features. We aimed at identifying downregulated genes in melanoma that are particularly upregulated in melanoblasts. Loss of such genes could contribute to stabilization of a dedifferentiated, malignant phenotype in melanoma. We determined that microRNA-622 (miR-622) expression was strongly downregulated in melanoma cells and tissues compared to melanocytes and melanoblast-related cells. miR-622 expression correlated with survival of patients with melanoma. miR-622 re-expression inhibited clonogenicity, proliferation, and migration in melanoma. Inhibition of miR-622 in melanocytes induced enhanced migration. Kirsten rat sarcoma (KRAS) was identified as a major functional target of miR-622 in melanoma. We conclude that miR-622 is a novel tumor suppressor in melanoma and identify the miR-622-KRAS axis as potential therapeutic target.
EVALuna2:34069

MicroRNA miR-125b controls melanoma progression by direct regulation of c-Jun protein expression - Kappelmann, M.; Kuphal, Silke; Meister, G.; Vardimon, L.; Bosserhoff, Anja Katrin (Oncogene, 2013)
A fundamental event in the development and progression of malignant melanoma is the deregulation of cancer-relevant transcription factors. We recently showed that c-Jun is a main regulator of tumor progression in melanoma and thus the most important member of the AP-1 transcription factor family for this disease. Interestingly, we revealed that c-Jun expression was regulated on the post-transcriptional level and therefore speculated that miRNAs could be involved in c-Jun regulation. We determined seed sequences for miR-125b and miR-527 in the coding region of c-Jun mRNA that hints at the direct involvement of miRNA-dependent regulation on the protein level. We found that the expression of miR-125b was significantly reduced in malignant melanoma cell lines and tissue samples compared with melanocytes, whereas miR-527 remained unchanged. In further functional experiments, treatment of melanoma cells with pre-miR-125b resulted in strong suppression of cellular proliferation and migration, supporting the role of miR-125b in melanoma. In addition, transfection of pre-miR-125b led to strong downregulation of c-Jun protein but not mRNA expression in melanoma cells. Luciferase assays using reporter plasmids containing the miR-125b seed sequence in the luciferase coding region confirmed the direct interaction with miR-125b. Furthermore, immunoprecipitation of Ago-2 revealed that c-Jun mRNA accumulated in the RNA-induced silencing complex after pre-miR-125b transfection in melanoma cells. In summary, we identified an important role for miR-125b in malignant melanoma. Moreover, we demonstrated post-transcriptional regulation of c-Jun by this miRNA and showed that c-Jun is a main mediator of the effects of miR-125b on melanoma cells. © 2013 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: c-Jun; malignant melanoma; migration; miRNA; post-transcriptionally; protein expression

MicroRNAs and signaling, complex interaction by feedback loops - Voeller, Daniel; Bosserhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2012)
CRIS-Team Scopus Importer:2022-08-05

MicroRNAS as biomarkers and therapeutic targets in melanoma - Mueller, Daniel W.; Bosserhoff, Anja Katrin (Springer New York, 2012)
CRIS-Team Scopus Importer:2022-08-05

MicroRNA-sequencing data analyzing melanoma development and progression - Linck, Lisa; Liebig, Janika; Voeller, Daniel; Eichner, Norbert; Lehmann, Gerhard; Meister, Gunter; Boßerhoff, Anja Katrin (Experimental and Molecular Pathology, 2018)
MicroRNAs (miRNAs) deregulated in melanoma are of growing importance in cancer research. We aimed to define the miRNAome of melanoma cell lines and primary melanocytes by RNA-Seq using identical cell lines as in a published miRNA expression study based on cDNA arrays. We identified 79 miRNAs, which are significantly deregulated during melanoma development. In addition, we could also determine 29 miRNAs being involved in melanoma progression. Interestingly, not all characterized miRNAs derived from cDNA array analyses of our and other groups could be found to be differentially expressed using RNA-Seq analyses, however, new miRNAs, formerly not associated with melanoma, were found to be strongly regulated.
EVALuna2:202902

MicroRNAs in melanocyte and melanoma biology - Mione, Marina; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2015)
The importance of microRNAs as key molecular components of cellular processes is now being recognized. Recent reports have shown that microRNAs regulate processes as diverse as protein expression and nuclear functions inside cells and are able to signal extracellularly, delivered via exosomes, to influence cell fate at a distance. The versatility of microRNAs as molecular tools inspires the design of novel strategies to control gene expression, protein stability, DNA repair and chromatin accessibility that may prove very useful for therapeutic approaches due to the extensive manageability of these small molecules. However, we still lack a comprehensive understanding of the microRNA network and its interactions with the other layers of regulatory elements in cellular and extracellular functions. This knowledge may be necessary before we exploit microRNA versatility in therapeutic settings. To identify rules of interactions between microRNAs and other regulatory systems, we begin by reviewing microRNA activities in a single cell type: the melanocyte, from development to disease.
EVALuna2:4707

miR-488-5p and its role in melanoma - Arnold, Jessica; Engelmann, Julia C.; Schneider, Nadja; Boßerhoff, Anja Katrin; Kuphal, Silke (Experimental and Molecular Pathology, 2019)
Due to their ability to regulate dozens to hundreds of target genes simultaneously and, therefore, influence several oncogenic pathways at the same time, microRNAs are a fascinating research object in melanoma. MicroRNAs have been identified as regulators of tumor proliferation, invasion and metastasis in melanoma. More precisely, it has been published that dysregulation of miR-488 contibutes to the progression of several cancer entities. However, the biological functions of miR-488, in special miR-488-5p in melanoma, remain unclear. This study showed the involvement of miR-488-5p in Wnt/β-catenin pathway and the function as a tumor suppressor. Transfection of miR-488-5p mimic led to inhibition of proliferation, migration, anchorage independent growth and led to induction of apoptosis. These data indicated that miR-488-5p acts as a tumor suppressor and is lost during melanoma development. The loss of miR-488-5p was confirmed in vivo by in situ hybridization on melanoma tissue.
EVALuna2:210373

miR-488-5p and its role in melanoma - Arnold, Jessica; Engelmann, Julia C.; Schneider, Nadja; Boßerhoff, Anja Katrin; Kuphal, Silke (Experimental and Molecular Pathology, 2020)
Due to their ability to regulate dozens to hundreds of target genes simultaneously and, therefore, influence several oncogenic pathways at the same time, microRNAs are a fascinating research object in melanoma. MicroRNAs have been identified as regulators of tumor proliferation, invasion and metastasis in melanoma. More precisely, it has been published that dysregulation of miR-488 contibutes to the progression of several cancer entities. However, the biological functions of miR-488, in special miR-488-5p in melanoma, remain unclear. This study showed the involvement of miR-488-5p in Wnt/β-catenin pathway and the function as a tumor suppressor. Transfection of miR-488-5p mimic led to inhibition of proliferation, migration, anchorage independent growth and led to induction of apoptosis. These data indicated that miR-488-5p acts as a tumor suppressor and is lost during melanoma development. The loss of miR-488-5p was confirmed in vivo by in situ hybridization on melanoma tissue.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Melanoma; microRNA; Wnt/β-catenin pathway

MiRNAs in malignant melanoma - Mione, Maria; Liebig, Janika; Munoz, Leonel; Boßerhoff, Anja Katrin (Springer International Publishing, 2017)
MicroRNAs (miRNAs) represent a class of small noncoding RNAs, first described in the nematode Caenorhabditis elegans. In 1993, the labs of Victor Ambros (Lee et al. Cell 75:843-854, 1993) and Gary Ruvkun (Wightman et al. Cell 75:855-862, 1993) discovered lin-4, the first member of the inexorably growing family of miRNAs. Interestingly, it was not until the year 2000 that Reinhart and colleagues detected a second miRNA species-let-7 (Reinhart et al. Nature 2000;403:901-906). The finding that the sequence of let-7 was conserved in a large variety of Metazoens from Drosophila to humans (in contrast to lin-4, which is exclusively expressed in Caenorhabditis; Pasquinelli et al. Nature 408:86-89, 2000; Slack et al. Mol Cell 2000;5:659-669, 2000) fueled miRNA research and revealed that this class of molecules is involved in the regulation of gene expression at a posttranscriptional level in presumably every multicellular organism. To date, more than 1800 distinct miRNA species have been identified in the human genome (www.miRNA.org Kozomara and Griffiths-Jones 42(Database issue):D68-73, 2014). Those are estimated to regulate the expression of as much as 60 % of all human transcripts (Friedman et al. Genome Res 2009;19:92-105, 2009). MiRNAs are demonstrably involved in the physiological regulation of multiple cellular processes, such as proliferation, apoptosis, and differentiation. As a consequence, abnormalities in miRNA activity were found to contribute to the pathogenesis and progression of various types of human cancers (reviewed by Mirnezami et al. Eur J Surg Oncol 35:339-347, 2009; Visone and Croce Am J Pathol 2009;174:1131-1138, 2009), including malignant melanoma (reviewed by Mione and Bosserhoff Pigment Cell Melanoma Res 2015;28:340-354).
CRIS-Team Scopus Importer:2022-08-05

miR networks in melanoma - more to come! - Kuphal, Silke; Bosserhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2013)
CRIS-Team Scopus Importer:2022-08-05

Modeling a mesenchymal cell state by bioprinting for the molecular analysis of dormancy in melanoma - Schmidt, Sonja; Fischer, Stefan; El Ahmad, Zubeir; Schmid, Rafael; Metzger, Eric; Schüle, Roland; Hellerbrand, Claus; Arkudas, Andreas; Kengelbach-Weigand, Annika; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin (Materials Today Bio, 2025)
Malignant melanoma is a highly aggressive tumor originating from the pigment producing cells, the melanocytes. It accounts for the majority of skin cancer related deaths worldwide. This is often due to the development of therapy resistance or tumor dormancy, eventually resulting in tumor relapse by yet undefined mechanisms. Tumor dormancy is thought to be mediated by the cellular microenvironment and models taking this factor into account are urgently needed. We 3D bioprinted melanoma cells in the hydrogels Cellink Bioink (CIB) or Matrigel (MG), each as a substitute of the extracellular matrix, and, thereby, induced a quiescent or a proliferative phenotype of the melanoma cell lines, respectively. RNA-Seq with subsequent comprehensive bioinformatical and molecular analyses assigned CIB-cultured cells to a predominantly mesenchymal and Matrigel-cultured cells to a more mitotic phenotype, emphasizing the CIB model as a suitable platform for the investigation of dormancy under consideration of the microenvironment. Melanoma cells in CIB 3D culture reflect a quiescent and migratory active cell state e.g. by revealing significant downregulation of genes associated with replication and cell cycle progression in this setting. Using this model system, we identified the mechanosensory gene FHL2 as one early sensor of changes in the ECM and suggest a FHL2-p21/AP-1 axis contributing to the dormant phenotype of melanoma cells in CIB.
CRIS-Team Scopus Importer:2025-04-01
Keywords: 3D cell culture; Bioinformatics; Cancer; Mechanosensation; Quiescence

Modifying microRNAs–another piece of the melanoma puzzle - Dietrich, Peter; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2015)
EVALuna2:4718

Modifying the Glycocalyx of Melanoma Cells via Metabolic Glycoengineering Using N-Acetyl-d-glucosamine Analogues - Harris, David; Groß, Marcel; Stäbler, Sebastian; Ebert, Regina; Seibel, Jürgen; Boßerhoff, Anja Katrin (Cells, 2024)
Tumor cells are decorated with aberrant glycan structures on cell surfaces. It is well known that the glycocalyx serves as a main cellular regulator, although its role in cancer is still not completely understood. Over recent decades, several non-natural monosaccharides carrying clickable groups have been introduced in melanoma cells. This technique, called Metabolic Glycoengineering (MGE), opens up the possibility of altering the cell’s glycocalyx via click chemistry using a two-step approach. This study expands the field of MGE by showing the successful metabolic incorporation of novel alternative artificial glucosamine derivatives. The latter were either deoxygenated or blocked by methyl ether in position 4 to generate deficient glycosylation patterns, while being extended by an alkyne to enable click chemistry as a one-step approach. As a result, we observed a reduced proliferation rate of melanoma cells. Furthermore, using a lectin array, the decrease in high mannose epitopes was observed. In summary, the successful use of alternative artificial glucosamine derivatives enabled a significant alteration in the glycocalyx, consequently influencing cell behavior.
CRIS-Team Scopus Importer:2024-12-06
Keywords: click chemistry; glycoproteins; melanoma cells; metabolic glycoengineering

Molecular analysis of tumor dormancy of the malignant 3D printed model of melanoma - Schmidt, Sarah; Fischer, S.; Schmid, R.; Arkudas, Andreas; Kengel-Bach-Weigand, A.; Kappelmann-Fenzl, M.; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Molecular changes induced in melanoma by cell culturing in 3D alginate hydrogels - Kappelmann-Fenzl, M.; Schmidt, Sonja; Fischer, Stefan; Schmid, Rafael; Lämmerhirt, Lisa; Fischer, Lena; Schrüfer, Stefan; Thievessen, Ingo; Schubert, Dirk W.; Matthies, Alexander Oliver; Detsch, Rainer; Boccaccini, Aldo R.; et al. (Cancers, 2021)
Alginate hydrogels have been used as a biomaterial for 3D culturing for several years. Here, gene expression patterns in melanoma cells cultivated in 3D alginate are compared to 2D cultures. It is well-known that 2D cell culture is not resembling the complex in vivo situation well. However, the use of very intricate 3D models does not allow performing high-throughput screening and analysis is highly complex. 3D cell culture strategies in hydrogels will better mimic the in vivo situation while they maintain feasibility for large-scale analysis. As alginate is an easy-to-use material and due to its favorable properties, it is commonly applied as a bioink component in the growing field of cell encapsulation and biofabrication. Yet, only a little information about the transcriptome in 3D cultures in hydrogels like alginate is available. In this study, changes in the transcriptome based on RNA-Seq data by cultivating melanoma cells in 3D alginate are analyzed and reveal marked changes compared to cells cultured on usual 2D tissue culture plastic. Deregulated genes represent valuable cues to signaling pathways and molecules affected by the culture method. Using this as a model system for tumor cell plasticity and heterogeneity, EGR1 is determined to play an important role in melanoma progression.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 3D cultivation; Biomaterials; EGR1; Melanoma; Whole transcriptome

Molecular cross-talk between Y5-receptor and neuropeptide Y drives liver cancer - Dietrich, Peter; Wormser, Laura; Fritz, Valerie; Seitz, Tatjana; de Maria, Monica; Schambony, Alexandra; Kremer, Andreas; Günther, Claudia; Itzel, Timo; Thasler, Wolfgang E.; Teufel, Andreas; Trebicka, Jonel; et al. (Journal of Clinical Investigation, 2020)
Hepatocellular carcinoma (HCC) is clearly age-related and represents one of the deadliest cancer types worldwide. Due to globally increasing risk factors including metabolic disorders, the incidence rates of HCC are still rising. However, the molecular hallmarks of HCC remain poorly understood. Neuropeptide Y (NPY) and NPY-receptors represent a highly conserved, stress-activated system which is involved in diverse cancer-related hallmarks including aging and metabolic alterations, but its impact on liver cancer had been unclear. Here, we observed increased NPY5-receptor (Y5R) expression in HCC which correlated with tumor growth and survival. Furthermore, we found that its ligand NPY was secreted by peri-tumorous hepatocytes. Hepatocyte-derived NPY promoted HCC progression by Y5R-activation. Transforming growth factor beta 1 (TGFβ1) was identified as a regulator of NPY in hepatocytes and induced Y5R in invasive cancer cells. Moreover, NPY-conversion by dipeptidylpeptidase 4 (DPP4) augmented Y5R-activation and function in liver cancer. The TGFβ-NPY-Y5R-axis and DPP4 represent attractive therapeutic targets for controlling liver cancer progression.
EVALuna2:212290
Keywords: Aging; Cancer; Hepatology

Molecular mechanisms of OIS breakdown in the context of melanoma formation - Kluge, Viola; Zimmermann, Tom; Pommer, Michaela; Kuphal, Silke; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

Multifrequency Investigation of Single-and Double-Stranded DNA with Scalable Metamaterial-Based THz Biosensors - Weisenstein, Christian; Richter, Merle; Wigger, Anna Katharina; Boßerhoff, Anja Katrin; Bolivar, Peter Haring (Biosensors, 2022)
Due to the occurrence of THz-excited vibrational modes in biomacromolecules, the THz frequency range has been identified as particularly suitable for developing and applying new bio-analytical methods. We present a scalable THz metamaterial-based biosensor being utilized for the multifrequency investigation of single-and double-stranded DNA (ssDNA and dsDNA) samples. It is demonstrated that the metamaterial resonance frequency shift by the DNA’s presence depends on frequency. Our experiments with the scalable THz biosensors demonstrate a major change in the degree of the power function for dsDNA by 1.53 ± 0.06 and, in comparison, 0.34 ± 0.11 for ssDNA as a function of metamaterial resonance frequency. Thus, there is a significant advantage for dsDNA detection that can be used for increased sensitivity of biomolecular detection at higher frequencies. This work represents a first step for application-specific biosensors with potential advantages in sensitivity, specificity, and robustness.
CRIS-Team Scopus Importer:2022-08-05
Keywords: biomolecular; biomolecules; biosensor; DNA; FSS; metamaterial; sensitivity; sensor; terahertz; THz

N-cadherin promoter polymorphisms and risk of osteoarthritis - Ruedel, Anke; Stark, Klaus; Kaufmann, Simone; Bauer, Richard; Reinders, Joerg; Rovensky, Jozef; Blazickova, Stanislava; Oefner, Peter J.; Bosserhoff, Anja K. (The FASEB Journal, 2014)
Osteoarthritis (OA) is the most common form of arthritis. It is characterized by cartilage destruction and bone remodeling, mediated in part by synovial fibroblasts (SFs). Given the functional significance of cadherins in these cells, we aimed at determining the role of genetic variants of N-cadherin (CDH2) in OA of the knee and hip. Six single-nucleotide polymorphisms in the genomic region of the CDH2 gene were genotyped in 312 patients with OA and 259 healthy control subjects. Gene expression of CDH2 was analyzed by qRT-PCR. Liquid chromatography-mass spectrometry was used to identify a transcription factor isolated by DNA pulldown. Its potential for binding to gene variants was examined by electrophoretic mobility shift assay, enzyme-linked immunosorbent assay, and chromatin immunoprecipitation. Genetic analysis identified a polymorphism located in the CDH2 promoter region to be associated with risk of OA. The minor allele of rs11564299 had a protective effect against OA. Compared to carriers of the major allele, carriers of the minor allele of rs11564299 displayed increased Ncadherin levels in SFs. Based on in silico analysis, the minor allele was predicted to generate a novel transcription factor binding site, Direct-binding assays and mass spectrometric analysis identified hnRNP K as binding selectively to the minor allele. In summary, a CDH2 promoter polymorphism influences the risk of OA, and hnRNP K was found to be involved in the regulation of elevated N-cadherin expression in patients with OA carrying the minor allele of rs11564299. © FASEB.
CRIS-Team Scopus Importer:2022-08-05
Keywords: CDH2; Genetic association study; HnRNP K; Rs11564299

Neuroblastoma RAS Viral Oncogene Homolog (NRAS) Is a Novel Prognostic Marker and Contributes to Sorafenib Resistance in Hepatocellular Carcinoma - Dietrich, Peter; Gaza, Anne; Wormser, Laura; Fritz, Valerie; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Neoplasia, 2019)
Inhibition of the RAS-RAF-ERK-pathway using sorafenib as a first-line and regorafenib as a second-line treatment approach is the only effective therapeutic strategy for advanced hepatocellular carcinoma (HCC). Recent studies suggest that wild-type KRAS and HRAS isoforms could majorly contribute to HCC progression and sorafenib resistance. In contrast, the role of neuroblastoma RAS viral oncogene homolog (NRAS) in HCC remained elusive. In this study, wild-type NRAS was found to be overexpressed in HCC cell lines, preclinical HCC models, and human HCC tissues. Moreover, NRAS overexpression correlated with poor survival and proliferation in vivo. However, siRNA-pool-mediated NRAS knockdown showed only slight effects on HCC proliferation, clonogenicity, and AKT activity. We determined that KRAS upregulation served as a functional compensatory mechanism in the absence of NRAS, which was overcome by combined inhibition of NRAS and KRAS in HCC cells. Furthermore, NRAS expression was elevated in sorafenib-resistant compared to nonresistant HCC cells, and NRAS knockdown enhanced sorafenib efficacy in resistant cells. In summary, NRAS appears to be a prognostic marker in HCC and contributes to sorafenib resistance. Regarding potential therapeutic strategies, NRAS inhibition in HCC should be combined with KRAS inhibition to prevent KRAS-mediated rescue effects.
CRIS-Team WoS Importer:2019-03-20

Next Generation Sequencing (NGS): What Can Be Sequenced? - Boßerhoff, Anja Katrin; Kappelmann-Fenzl, Melanie (Next Generation Sequencing and Data Analysis, 2021)

Novel Bioimaging Techniques of Metals by Laser Ablation Inductively Coupled Plasma Mass Spectrometry for Diagnosis Of Fibrotic and Cirrhotic Liver Disorders - Pornwilard, M-M; Weiskirchen, Ralf; Gassler, Nikolaus; Bosserhoff, Anja Katrin; Becker, J. Sabine (PLoS ONE, 2013)
Background and Aims: Hereditary disorders associated with metal overload or unwanted toxic accumulation of heavy metals can lead to morbidity and mortality. Patients with hereditary hemochromatosis or Wilson disease for example may develop severe hepatic pathology including fibrosis, cirrhosis or hepatocellular carcinoma. While relevant disease genes are identified and genetic testing is applicable, liver biopsy in combination with metal detecting techniques such as energy-dispersive X-ray spectroscopy (EDX) is still applied for accurate diagnosis of metals. Vice versa, several metals are needed in trace amounts for carrying out vital functions and their deficiency due to rapid growth, pregnancy, excessive blood loss, and insufficient nutritional or digestive uptake results in organic and systemic shortcomings. Established in situ techniques, such as EDX-ray spectroscopy, are not sensitive enough to analyze trace metal distribution and the quantification of metal images is difficult. Methods: In this study, we developed a quantitative biometal imaging technique of human liver tissue by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) in order to compare the distribution of selected metals in cryo-sections of healthy and fibrotic/cirrhotic livers. Results: Most of the metals are homogeneous distributed within the normal tissue, while they are redirected within fibrotic livers resulting in significant metal deposits. Moreover, total iron and copper concentrations in diseased liver were found about 3-5 times higher than in normal liver samples. Conclusions: Biometal imaging via LA-ICP-MS is a sensitive innovative diagnostic tool that will impact clinical practice in identification and evaluation of hepatic metal disorders and to detect subtle metal variations during ongoing hepatic fibrogenesis. © 2013 M-M et al.
CRIS-Team Scopus Importer:2022-08-05

NRN1 interacts with Notch to increase oncogenic STAT3 signaling in melanoma - Devitt, Lucia; Westphal, Dana; Pieger, Katharina; Schneider, Nadja; Boßerhoff, Anja Katrin; Kuphal, Silke (Cell Communication and Signaling, 2024)
Background: Melanoma is a highly heterogeneous cancer, in which frequent changes in activation of signaling pathways lead to a high adaptability to ever changing tumor microenvironments. The elucidation of cancer specific signaling pathways is of great importance, as demonstrated by the inhibitor of the common BrafV600E mutation PLX4032 in melanoma treatment. We therefore investigated signaling pathways that were influenced by neurotrophin NRN1, which has been shown to be upregulated in melanoma. Methods: Using a cell culture model system with an NRN1 overexpression, we investigated the influence of NRN1 on melanoma cells’ functionality and signaling. We employed real time cell analysis and spheroid formation assays, while for investigation of molecular mechanisms we used a kinase phosphorylation kit as well as promotor activity analysis followed by mRNA and protein analysis. Results: We revealed that NRN1 interacts directly with the cleaved intracellular domain (NICD) of Notch1 and Notch3, causing a potential retention of NICD in the cytoplasm and thereby reducing the expression of its direct downstream target Hes1. This leads to decreased sequestration of JAK and STAT3 in a Hes1-driven phosphorylation complex. Consequently, our data shows less phosphorylation of STAT3 while presenting an accumulation of total protein levels of STAT3 in association with NRN1 overexpression. The potential of the STAT3 signaling pathway to act in both a tumor suppressive and oncogenic manner led us to investigate specific downstream targets – namely Vegf A, Mdr1, cMet - which were found to be upregulated under oncogenic levels of NRN1. Conclusions: In summary, we were able to show that NRN1 links oncogenic signaling events between Notch and STAT3 in melanoma. We also suggest that in future research more attention should be payed to cellular regulation of signaling molecules outside of the classically known phosphorylation events. Graphical Abstract: (Figure presented.).
CRIS-Team Scopus Importer:2024-05-10
Keywords: Melanoma; Notch; NRN1; STAT3

Nuclear AREG affects a low-proliferative phenotype and contributes to drug resistance of melanoma - Seefried, Felix; Haller, Lucia; Fukuda, Shinji; Thongmao, Aranya; Schneider, Nadja; Utikal, Jochen; Higashiyama, Shigeki; Boßerhoff, Anja Katrin; Kuphal, Silke (International Journal of Cancer, 2022)
AMPHIREGULIN (AREG) is a multifaceted molecule, which acts not only as an extracellular ligand for EGF receptor (EGFR), but also as an intracellular signaling molecule. It remains elusive, however, whether AREG has a tumor suppressive or oncogenic role in melanoma. Here, we found that several melanoma cell lines express AREG, but the expression does not correlate with that of EGFR. Recombinant AREG and the neutralizing antibody experiments showed that intracellular AREG plays an important role in melanoma, implying a divergent function of AREG in addition to the role as a ligand for EGFR. Further investigation of this mechanism revealed that particularly nuclear-localized AREG regulates IGF-1R, P21 (Cip1/Waf1), TP53 and JARID1B protein accumulation in the nucleus. Furthermore, manipulation of nuclear AREG levels has influence on heterochromatin condensation (HP1beta, SETDB1) and trimethylation of histones H3K9 and H3K4. As these molecules correspond to previously identified markers for slow-cycling drug resistant cells, we speculate that nuclear AREG predisposes cells to resistance to therapy. According to the hypothesis, we detected the accumulation of AREG in the nucleus of SK-Mel-28-VR, which was cultured under Vemurafenib (VR) selection pressure, and this correlates with JARID1B expression. Here, knockdown of AREG makes the previously resistant cells more sensitive to VR treatment, resulting in inhibited proliferation. Taken together, we suggest that nuclear AREG affects a slow-cycling phenotype and increases resistance to VR, raising a possibility that AREG might be a potential therapeutic target for resistance in melanoma.
CRIS-Team WoS Importer:2022-09-16

Nucleosome Remodeler SNF2L Suppresses Cell Proliferation and Migration and Attenuates Wnt Signaling - Eckey, Maren; Kuphal, Silke; Straub, Tobias; Ruemmele, Petra; Kremmer, Elisabeth; Bosserhoff, Anja K.; Becker, Peter B. (Molecular and Cellular Biology, 2012)
ISWI is an evolutionarily conserved ATPase that catalyzes nucleosome remodeling in different macromolecular complexes. Two mammalian ISWI orthologs, SNF2H and SNF2L, are thought to have specialized functions despite their high sequence similarity. To date, the function of SNF2L in human cells has not been a focus of research. Newly established specific monoclonal antibodies and selective RNA interference protocols have now enabled a comprehensive characterization of loss-of-function phenotypes in human cells. In contrast to earlier results, we found SNF2L to be broadly expressed in primary human tissues. Depletion of SNF2L in HeLa cells led to enhanced proliferation and increased migration. These phenomena were explained by transcriptome profiling, which identified SNF2L as a modulator of the Wnt signaling network. The cumulative effects of SNF2L depletion on gene expression portray the cell in a state of activated Wnt signaling characterized by increased proliferation and chemotactic locomotion. Accordingly, high levels of SNF2L expression in normal melanocytes contrast with undetectable expression in malignant melanoma. In summary, our data document an inverse relationship between SNF2L expression and features characteristic of malignant cells. © 2012, American Society for Microbiology.
CRIS-Team Scopus Importer:2022-08-05

Optimization of the Treatment of Squamous Cell Carcinoma Cells by Combining Photodynamic Therapy with Cold Atmospheric Plasma - Karrer, Sigrid; Unger, Petra; Spindler, Nina; Szeimies, Rolf Markus; Boßerhoff, Anja Katrin; Berneburg, Mark; Arndt, Stephanie (International Journal of Molecular Sciences, 2024)
Actinic keratosis (AK) is characterized by a reddish or occasionally skin-toned rough patch on sun-damaged skin, and it is regarded as a precursor to squamous cell carcinoma (SCC). Photodynamic therapy (PDT), utilizing 5-aminolevulinic acid (ALA) along with red light, is a recognized treatment option for AK that is limited by the penetration depth of light and the distribution of the photosensitizer into the skin. Cold atmospheric plasma (CAP) is a partially ionized gas with permeability-enhancing and anti-cancer properties. This study analyzed, in vitro, whether a combined treatment of CAP and ALA-PDT may improve the efficacy of the treatment. In addition, the effect of the application sequence of ALA and CAP was investigated using in vitro assays and the molecular characterization of human oral SCC cell lines (SCC-9, SCC-15, SCC-111), human cutaneous SCC cell lines (SCL-1, SCL-2, A431), and normal human epidermal keratinocytes (HEKn). The anti-tumor effect was determined by migration, invasion, and apoptosis assays and supported the improved efficacy of ALA-PDT in combination with CAP. However, the application sequence ALA-CAP–red light seems to be more efficacious than CAP-ALA–red light, which is probably due to increased intracellular ROS levels when ALA is applied first, followed by CAP and red light treatment. Furthermore, the expression of apoptosis- and senescence-related molecules (caspase-3, -6, -9, p16INK4a, p21CIP1) was increased, and different genes of the junctional network (ZO-1, CX31, CLDN1, CTNNB1) were induced after the combined treatment of CAP plus ALA-PDT. HEKn, however, were much less affected than SCC cells. Overall, the results show that CAP may improve the anti-tumor effects of conventional ALA-PDT on SCC cells. Whether this combined application is successful in treating AK in vivo has to be carefully examined in follow-up studies.
CRIS-Team Scopus Importer:2024-10-25
Keywords: 5-aminolaevulinic acid (ALA); actinic keratosis (AK); cold atmospheric plasma (CAP); photodynamic therapy (PDT); squamous cell carcinoma (SCC)

Phototherapy-induced elevation of serum level of melanoma inhibitory activity - Datz, Elisabeth; Zeman, Florian; Koller, Michael; Szeimies, Rolf Markus; Berneburg, Mark; Landthaler, Michael; Boßerhoff, Anja Katrin; Karrer, Sigrid (Photodermatology Photoimmunology & Photomedicine, 2019)
Background: Phototherapy is a frequently used treatment modality for a variety of dermatologic diseases. UV radiation has different effects on the skin, for example increased production and release of cytokines and other proteins, and is involved in the initiation and progression of skin cancer. Objective of this clinical trial was to investigate potential systemic effects of UV phototherapy on cytokine profiles in blood. Methods: In a prospective, mono-centric, one-armed study, the serum levels of the melanoma tumour marker “melanoma inhibitory activity” (MIA), Il-1α, Il-4, Il-6, Il-10, TNF-α and IFN-γ of 115 patients with different skin diseases were compared before and 24-48 hours as well as 2-4 weeks after the first phototherapy with PUVA (psoralen and ultraviolet A), UVA or UVB, or both. Data were analysed using linear mixed models. Results: Estimated marginal means of MIA levels were 6.05 ng/mL (95%-CI: 5.37-6.72, range: 2.83-14.49) before the first treatment, which had significantly increased to 6.79 ng/mL 2-4 weeks after the first phototherapy (CI 95%: 6.12-7.47, range: 3.09-15.45; P = 0.0042). MIA levels 2-4 weeks after the first phototherapy were significantly higher than 24-48 hours after the first phototherapy (P = 0.0083). 2-4 weeks after the first treatment, TNF-α levels had decreased significantly (P = 0.033) more in patients with psoriasis who had responded well to phototherapy than in patients unresponsive to treatment. Serum levels of the other cytokines had not changed significantly. Conclusions: Short-term phototherapy significantly increased the serum levels of the melanoma tumour marker MIA. The potential clinical relevance of these findings (ie an increased risk of melanoma) is unclear and should be further investigated.
CRIS-Team Scopus Importer:2019-07-30
Keywords: melanoma; melanoma inhibitory activity; phototherapy; psoriasis; skin diseases; study; UV therapy

Pirin is a prognostic marker of human melanoma that dampens the proliferation of malignant cells by downregulating JARID1B/KDM5B expression - Penas, Cristina; Arroyo-Berdugo, Yoana; Apraiz, Aintzane; Rasero, Javier; Muñoa-Hoyos, Iraia; Andollo, Noelia; Cancho-Galán, Goikoane; Izu, Rosa; Gardeazabal, Jesús; Ezkurra, Pilar A.; Subiran, Nerea; Alvarez-Dominguez, Carmen; et al. (Scientific Reports, 2023)
Originally considered to act as a transcriptional co-factor, Pirin has recently been reported to play a role in tumorigenesis and the malignant progression of many tumors. Here, we have analyzed the diagnostic and prognostic value of Pirin expression in the early stages of melanoma, and its role in the biology of melanocytic cells. Pirin expression was analyzed in a total of 314 melanoma biopsies, correlating this feature with the patient’s clinical course. Moreover, PIR downregulated primary melanocytes were analyzed by RNA sequencing, and the data obtained were validated in human melanoma cell lines overexpressing PIR by functional assays. The immunohistochemistry multivariate analysis revealed that early melanomas with stronger Pirin expression were more than twice as likely to develop metastases during the follow-up. Transcriptome analysis of PIR downregulated melanocytes showed a dampening of genes involved in the G1/S transition, cell proliferation, and cell migration. In addition, an in silico approach predicted that JARID1B as a potential transcriptional regulator that lies between PIR and its downstream modulated genes, which was corroborated by co-transfection experiments and functional analysis. Together, the data obtained indicated that Pirin could be a useful marker for the metastatic progression of melanoma and that it participates in the proliferation of melanoma cells by regulating the slow-cycling JARID1B gene.
CRIS-Team Scopus Importer:2023-06-30

Post-transcriptional regulation of Argonaute2 in malignant melanoma - Linck-Paulus, L.; Voeller, D.; Meister, G.; Boßerhoff, Anja Katrin (EXPERIMENTAL DERMATOLOGY, 2019)
CRIS-Team WoS Importer:2019-03-26

Protumoral roles of melanoma inhibitory activity 2 in oral squamous cell carcinoma - Kurihara, M.; Kirita, T.; Sasahira, T.; Ohmori, H.; Matsushima, S.; Yamamoto, K.; Kuniyasu, H.; Bosserhoff, Anja Katrin (British Journal of Cancer, 2013)
Background:The role of melanoma inhibitory activity 2 (MIA2) was examined in human oral squamous cell carcinoma (OSCC).Methods:MIA2 role was examined by immunohistochemistry of human OSCCs and knockdown studies using human 3 OSCC cell lines with MIA2 expression.Results:MIA2 expression was observed in 62 (66.7%) of 93 OSCCs and was associated with tumour expansion and nodal metastasis. Melanoma inhibitory activity 2 expression was inversely correlated with intratumoral infiltration of lymphocytes. Invasion and anti-apoptotic survival were reduced by MIA2 knockdown in HSC3 cells. MOLT-3 lymphocytes infiltrating the HSC3 cell layer was enhanced by MIA2 knockdown or MIA2 depletion with the antibody. In HSC3 cells, MIA2 knockdown decreased the expressions of vascular endothelial growth factor (VEGF), VEGF-C, and VEGF-D. The downregulation of VEGF-C and-D was caused by inhibition of p38 and extracellular signal-regulated kinase (ERK)1/2, respectively. Melanoma inhibitory activity 2 was co-precipitated with integrin α4 andα5 in HSC3 cells. Integrin α4 knockdown decreased p38 phosphorylation and increased apoptosis, whereas integrin α5 knockdown decreased c-Jun N-terminal kinase (JNK) phosphorylation and apoptosis. Inhibition of JNK decreased apoptosis in the HSC3 cells.Conclusion:These findings suggest that the roles of MIA2 might be based on the variety of the integrins and the subtypes of mitogen-activated protein kinase. © 2013 Cancer Research UK. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05

Quantification of dsDNA functionalization efficiency in THz biosensors - Weisenstein, C.; Schmeck, M.; Schaar, Dominik; Wigger, A. K.; Boßerhoff, Anja Katrin; Bolivar, P. Haring (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2019)
In the past, THz bioanalytical techniques have been proven to be viable tools for label-free detection of biomolecules. However, significant improvements in the detection limit are needed to apply THz biosensors in biomedical diagnosis. To determine detection limits of the biosensor and the absolute amount of sample volume, quantitative measurements are required. We present label-free THz sensing of dsDNA and implement an approach based on reference investigations to quantify the dsDNA functionalization density. Defined functionalization densities are vital to maximize the adsorption of a dsDNA groove-binding protein, which acts as a tumor marker for malignant melanoma.
CRIS-Team Scopus Importer:2019-11-19

Quantitative detection of disseminated melanoma cells by trp-1 transcript analysis reveals stochastic distribution of pulmonary metastases - Kyjacova, Lenka; Saup, Rafael; Rothley, Melanie; Schmaus, Anja; Wagner, Tabea; Boßerhoff, Anja Katrin; Garvalov, Boyan K.; Thiele, Wilko; Sleeman, Jonathan P. (Journal of Clinical Medicine, 2021)
A better understanding of the process of melanoma metastasis is required to underpin the development of novel therapies that will improve patient outcomes. The use of appropriate animal models is indispensable for investigating the mechanisms of melanoma metastasis. However, reliable and practicable quantification of metastases in experimental mice remains a challenge, particularly if the metastatic burden is low. Here, we describe a qRT-PCR-based protocol that employs the melanocytic marker Trp-1 for the sensitive quantification of melanoma metastases in the murine lung. Using this protocol, we were able to detect the presence of as few as 100 disseminated melanoma cells in lung tissue. This allowed us to quantify metastatic burden in a spontaneous syngeneic B16-F10 metastasis model, even in the absence of visible metastases, as well as in the autochthonous Tg(Grm1)/Cyld−/− melanoma model. Importantly, we also observed an uneven distribution of disseminated melanoma cells amongst the five lobes of the murine lung, which varied considerably from animal to animal. Together, our findings demonstrate that the qRT-PCR-based detection of Trp-1 allows the quantification of low pulmonary metastatic burden in both transplantable and autochthonous murine melanoma models, and show that the analysis of lung metastasis in such models needs to take into account the stochastic distribution of metastatic lesions amongst the lung lobes.
CRIS-Team Scopus Importer:2021-12-03
Keywords: Animal models; Lung; Melanoma; Metastasis; Mice; Trp-1

Redundancy in regulation of chondrogenesis in MIA/CD-RAP-deficient mice - Schmid, Rainer; Bosserhoff, Anja Katrin (Mechanisms of Development, 2014)
Recent in vitro analysis of MIA/CD-RAP-deficient (MIA-/-) mesenchymal stem cells revealed altered chondrogenic differentiation, characterised by enhanced proliferation and delayed differentiation. However, adult MIA-/- mice develop normally and show only ultrastructural defects of the cartilage but no major abnormalities. We therefore focused, in this study, on chondrogenesis in vivo in MIA-/- mouse embryos to reveal potential molecular changes during embryogenesis and possible redundant mechanisms, which explain the almost normal phenotype despite MIA/CD-RAP loss. In situ hybridisation analysis revealed larger expression areas of Col2a1 and Sox9 positive, proliferating chondrocytes at day 15.5 and 16.5 of embryogenesis in MIA-/- mice. The initially diminished zone of Col10a1-expressing hypertrophic chondrocytes at day 15.5 was compensated at day 16.5 in MIA-/- embryos. Supported by in vitro studies using mesenchymal stem cells, we discovered that chondrogenesis in MIA-/- mice is modified by enhanced Sox9, Sox6 and AP-2α expression. Finally, we identified reduced AP1 and CRE activity, analysed by reporter gene- and electrophoretic mobility shift assays, important for redundancy mechanism which rescued delayed hypertrophic differentiation and allows normal development of MIA-/- mice. In summary, as observed in other knockout models of molecules important for cartilage development and differentiation, viability and functional integrity is reached by remarkable molecular redundancy in MIA/CD-RAP knockout mice. © 2013 Elsevier Ireland Ltd.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Cell signalling; Chondrogenesis; Differentiation; MIA-knockout mouse; MIA/CD-RAP; Sox9

Regulation and function of the atypical cadherin FAT1 in hepatocellular carcinoma - Valletta, Daniela; Czech, Barbara; Spruss, Thilo; Ikenberg, Kristian; Wild, Peter; Hartmann, Arndt; Weiss, Thomas S.; Oefner, Peter J.; Mueller, Martina; Hellerbrand, Claus; Bosserhoff, Anja Katrin (Carcinogenesis, 2014)
In human cancers, giant cadherin FAT1 may function both, as an oncogene and a tumor suppressor. Here, we investigated the expression and function of FAT1 in hepatocellular carcinoma (HCC). FAT1 expression was increased in human HCC cell lines and tissues compared with primary human hepatocytes and non-tumorous liver tissue as assessed by quantitative PCR and western blot analysis. Combined immunohistochemical and tissue microarray analysis showed a significant correlation of FAT1 expression with tumor stage and proliferation. Suppression of FAT1 expression by short hairpin RNA impaired proliferation and migration as well as apoptosis resistance of HCC cells in vitro. In nude mice, tumors formed by FAT1-suppressed HCC cells showed a delayed onset and more apoptosis compared with tumors of control cells. Both hepatocyte growth factor and hypoxia-mediated hypoxia-inducible factor 1 alpha activation were identified as strong inducers of FAT1 in HCC. Moreover, demethylating agents induced FAT1 expression in HCC cells. Hypoxia lead to reduced levels of the methyl group donor S-adenosyl-L-methionine (SAM) and hypoxia-induced FAT1 expression was inhibited by SAM supplementation in HCC cells. Together, these findings indicate that FAT1 expression in HCC is regulated via promotor methylation. FAT1 appears as relevant mediator of hypoxia and growth receptor signaling to critical tumorigenic pathways in HCC. This knowledge may facilitate the rational design of novel therapeutics against this highly aggressive malignancy.
EVALuna2:6668

Response-predictive gene expression profiling of glioma progenitor cells in vitro - Moeckel, Sylvia; Meyer, Katharina; Leukel, Petra; Heudorfer, Fabian; Seliger, Corinna; Stangl, Christina; Bogdahn, Ulrich; Proescholdt, Martin; Brawanski, Alexander; Vollmann-Zwerenz, Arabel; Riemenschneider, Markus J.; Spang, Rainer; et al. (PLoS ONE, 2014)
Background: High-grade gliomas are amongst the most deadly human tumors. Treatment results are disappointing. Still, In several trials around 20% of patients respond to therapy. To date, diagnostic strategies to identify patients that will profit from a specific therapy do not exist. Copyright:
CRIS-Team Scopus Importer:2022-08-05

RKIP regulates differentiation-related features in melanocytic cells - Penas, Cristina; Apraiz, Aintzane; Muñoa, Iraia; Arroyo-Berdugo, Yoana; Rasero, Javier; Ezkurra, Pilar A.; Velasco, Veronica; Subiran, Nerea; Boßerhoff, Anja Katrin; Alonso, Santos; Asumendi, Aintzane; Boyano, Maria D. (Cancers, 2020)
Raf Kinase Inhibitor Protein (RKIP) has been extensively reported as an inhibitor of key signaling pathways involved in the aggressive tumor phenotype and shows decreased expression in several types of cancers. However, little is known about RKIP in melanoma or regarding its function in normal cells. We examined the role of RKIP in both primary melanocytes and malignant melanoma cells and evaluated its diagnostic and prognostic value. IHC analysis revealed a significantly higher expression of RKIP in nevi compared with early-stage (stage I–II, AJCC 8th) melanoma biopsies. Proliferation, wound healing, and collagen-coated transwell assays uncovered the implication of RKIP on the motility but not on the proliferative capacity of melanoma cells as RKIP protein levels were inversely correlated with the migration capacity of both primary and metastatic melanoma cells but did not alter other parameters. As shown by RNA sequencing, endogenous RKIP knockdown in primary melanocytes triggered the deregulation of cellular differentiation-related processes, including genes (i.e., ZEB1, THY-1) closely related to the EMT. Interestingly, NANOG was identified as a putative transcriptional regulator of many of the deregulated genes, and RKIP was able to decrease the activation of the NANOG promoter. As a whole, our data support the utility of RKIP as a diagnostic marker for early-stage melanomas. In addition, these findings indicate its participation in the maintenance of a differentiated state of melanocytic cells by modulating genes intimately linked to the cellular motility and explain the progressive decrease of RKIP often described in tumors.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Biomarker; Cell motility; Differentiation; Melanocytes; Melanoma; RKIP; Transcriptome analysis

RNA-seq analysis identifies different transcriptomic types and developmental trajectories of primary melanomas - Kunz, Manfred; Loeffler-Wirth, Henry; Dannemann, Michael; Willscher, Edith; Doose, Gero; Kelso, Janet; Kottek, Tina; Nickel, Birgit; Hopp, Lydia; Landsberg, Jenny; Hoffmann, Steve; Tueting, Thomas; et al. (Oncogene, 2018)
Recent studies revealed trajectories of mutational events in early melanomagenesis, but the accompanying changes in gene expression are far less understood. Therefore, we performed a comprehensive RNA-seq analysis of laser-microdissected melanocytic nevi (n = 23) and primary melanoma samples (n = 57) and characterized the molecular mechanisms of early melanoma development. Using self-organizing maps, unsupervised clustering, and analysis of pseudotime (PT) dynamics to identify evolutionary trajectories, we describe here two transcriptomic types of melanocytic nevi (N1 and N2) and primary melanomas (M1 and M2). N1/M1 lesions are characterized by pigmentation-type and MITF gene signatures, and a high prevalence of NRAS mutations in M1 melanomas. N2/M2 lesions are characterized by inflammatory-type and AXL gene signatures with an equal distribution of wild-type and mutated BRAF and low prevalence of NRAS mutations in M2 melanomas. Interestingly, N1 nevi and M1 melanomas and N2 nevi and M2 melanomas, respectively, cluster together, but there is no clustering in a stage-dependent manner. Transcriptional signatures of M1 melanomas harbor signatures of BRAF/MEK inhibitor resistance and M2 melanomas harbor signatures of anti-PD-1 antibody treatment resistance. Pseudotime dynamics of nevus and melanoma samples are suggestive for a switch-like immune-escape mechanism in melanoma development with downregulation of immune genes paralleled by an increasing expression of a cell cycle signature in late-stage melanomas. Taken together, the transcriptome analysis identifies gene signatures and mechanisms underlying development of melanoma in early and late stages with relevance for diagnostics and therapy.
EVALuna2:196749

Robo3A and Robo3B expression is regulated via alternative promoters and mRNA stability - Ruedel, Anke; Schott, Mandy; Schubert, Thomas; Boßerhoff, Anja Katrin (Cancer Cell International, 2016)
Background: The transmembrane receptor family Roundabout (Robo) was described to have an essential role in the developing nervous system. Recent studies demonstrated that Robo3 shows an altered expression in rheumatoid arthritis as well as in melanoma. Context and purpose of the study: Until today no detailed studies of the two Robo3 isoforms (Robo3A and Robo3B) and their roles in rheumatoid arthritis synovial fibroblasts, respectively malignant melanoma are available. To get a better understanding regarding the role of Robo3A and Robo3B in the molecular process of rheumatoid arthritis and melanoma the exact characterization of expression and regulation is object of this study. Results: mRNA and protein expression of the transcriptional variants were analyzed by quantitative RT-PCR respectively western blotting and revealed particularly enhanced expression of Robo3B in rheumatoid arthritis and melanoma. Promoter assays and inhibitor studies also disclosed that there is apparently a cell- and isoform-specific regulation of the Robo3 expression. Finally, dissimilar mRNA stabilities of Robo3A and Robo3B are identified as decisive posttranscriptional gene expression control. Conclusion: In summary, this study supported an isotype specific role of Robo3B in disease hinting to different functional roles of each isoform.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Malignant melanoma; Repellent factor; Rheumatoid arthritis; Robo

Role of Amino Acid Transporter SNAT1/SLC38A1 in Human Melanoma - Böhme-Schäfer, Ines; Lörentz, Sandra; Boßerhoff, Anja Katrin (Cancers, 2022)
The tumor metabolism is an important driver of cancer cell survival and growth, as rapidly dividing tumor cells exhibit a high demand for energetic sources and must adapt to microenviron-mental changes. Therefore, metabolic reprogramming of cancer cells and the associated deregulation of nutrient transporters are a hallmark of cancer cells. Amino acids are essential for cancer cells to synthesize the necessary amount of protein, DNA, and RNA. Although cancer cells can synthesize glutamine de novo, most cancer cells show an increased uptake of glutamine from the tumor microen-vironment. Especially SNAT1/SLC38A1, a member of the sodium neutral amino acid transporter (SNAT) family, plays an essential role during major net import of glutamine. In this study, we revealed a significant upregulation of SNAT1 expression in human melanoma tissue in comparison to healthy epidermis and an increased SNAT1 expression level in human melanoma cell lines when compared to normal human melanocytes (NHEMs). We demonstrated that functional inhibition of SNAT1 with α-(methylamino) isobutyric acid (MeAIB), as well as siRNA-mediated downregulation reduces cancer cell growth, cellular migration, invasion, and leads to induction of senescence in melanoma cells. Consequently, these results demonstrate that the amino acid transporter SNAT1 is essential for cancer growth, and indicates a potential target for cancer chemotherapy.
CRIS-Team Scopus Importer:2022-05-06
Keywords: amino acid transporter; melanoma; tumor metabolism

Role of Fibroblast Growth Factors in the Crosstalk of Hepatic Stellate Cells and Uveal Melanoma Cells in the Liver Metastatic Niche - Seitz, Tatjana; John, Nora; Sommer, Judith; Dietrich, Peter; Thasler, Wolfgang E.; Hartmann, Arndt; Evert, Katja; Lang, Sven A.; Boßerhoff, Anja Katrin; Hellerbrand, Claus (International Journal of Molecular Sciences, 2022)
Hepatic metastasis is the critical factor determining tumor-associated mortality in different types of cancer. This is particularly true for uveal melanoma (UM), which almost exclusively metastasizes to the liver. Hepatic stellate cells (HSCs) are the precursors of tumor-associated fibroblasts and support the growth of metastases. However, the underlying mechanisms are widely unknown. Fibroblast growth factor (FGF) signaling is dysregulated in many types of cancer. The aim of this study was to analyze the pro-tumorigenic effects of HSCs on UM cells and the role of FGFs in this crosstalk. Conditioned medium (CM) from activated human HSCs significantly induced proliferation together with enhanced ERK and JNK activation in UM cells. An in silico database analysis revealed that there are almost no mutations of FGF receptors (FGFR) in UM. However, a high FGFR expression was found to be associated with poor survival for UM patients. In vitro, the pro-tumorigenic effects of HSC-CM on UM cells were abrogated by a pharmacological inhibitor (BGJ398) of FGFR1/2/3. The expression analysis revealed that the majority of paracrine FGFs are expressed by HSCs, but not by UM cells, including FGF9. Furthermore, the immunofluorescence analysis indicated HSCs as a cellular source of FGF9 in hepatic metastases of UM patients. Treatment with recombinant FGF9 significantly enhanced the proliferation of UM cells, and this effect was efficiently blocked by the FGFR1/2/3 inhibitor BGJ398. Our study indicates that FGF9 released by HSCs promotes the tumorigenicity of UM cells, and thus suggests FGF9 as a promising therapeutic target in hepatic metastasis.
CRIS-Team Scopus Importer:2022-10-28
Keywords: fibroblast growth factor 9; fibroblast growth factors; hepatic metastasis; hepatic stellate cells; uveal melanoma

Role of melanoma inhibitory activity in melanocyte senescence - Feuerer, Lena; Lamm, Susanne; Henz, Ingmar; Kappelmann-Fenzl, Melanie; Haferkamp, Sebastian; Meierjohann, Svenja; Hellerbrand, Claus; Kuphal, Silke; Boßerhoff, Anja Katrin (Pigment Cell & Melanoma Research, 2019)
The protein melanoma inhibitory activity (MIA) is known to be expressed in melanoma and to support melanoma progression. Interestingly, previous studies also observed the expression of MIA in nevi. Concentrating on these findings, we revealed that MIA expression is correlated with a senescent state in melanocytes. Induction of replicative or oncogene-induced senescence resulted in increased MIA expression in vitro. Notably, MIA knockdown in senescent melanocytes reduced the percentage of senescence-associated beta-Gal-positive cells and enhanced proliferation. Using the melanoma mouse model Tg(Grm1), MIA-deficient mice supported the impact of MIA on senescence by showing a significantly earlier tumor onset compared to controls. In melanocytes, MIA knockdown led to a downregulation of the cell cycle inhibitor p21 in vitro and in vivo. In contrast, after induction of hTERT in human melanoma cells, p21 regulation by MIA was lost. In summary, our data show for the first time that MIA is a regulator of cellular senescence in human and murine melanocytes.
CRIS-Team Scopus Importer:2019-07-02
Keywords: melanocyte; melanoma inhibitory activity; oncogene-induced senescence; p21; senescence; telomerase

Selective Biodetection Platform for Melanoma Diagnosis Using Functionalized THz Metamaterials - Richter, Merle; Loth, Yannik; Wigger, Anna K.; Rachinger, Nicole; Nordhoff, Daniela; Stock, Daniel; Boßerhoff, Anja Katrin; Bolivar, Peter Haring (International Conference on Infrared, Millimeter, and Terahertz Waves, IRMMW-THz, 2023)
In this contribution, we propose a promising diagnostic platform for various biosensing tasks. More precisely, we demonstrate its capabability of selective and sensitive detection of the early growth response protein 2 (EGR2). This protein is a transcription factor, which is found in increased activities in melanoma cells. The analysis was performed with the proposed THz biosensor on a complex sample of nucleus proteins. Categorically, the sensor belongs to the frequency selective surface type metamaterials and is composed of an array unit cells, each containing an asymmetric double split ring resonator. The single resonator elements are slits in a metallic layer and are enhanced by an undercut etch. This enables the active area of the sensor to be functionalized selectively. On one sensor chip, multiple query fields containing the metamaterial array are located, thereby enabling internal referencing and multiple analyses to take place in one measurement sequence.
CRIS-Team Scopus Importer:2023-12-08

Selenium-binding protein 1 is down-regulated in malignant melanoma - Schott, Mandy; de Jel, Miriam Martha; Engelmann, Julia C.; Renner, Philipp; Geissler, Edward K.; Boßerhoff, Anja Katrin; Kuphal, Silke (Oncotarget, 2018)
Selenium-binding protein 1 (SELENBP1) expression is reduced in various epithelial cancer entities compared to corresponding normal tissue and has already been described as a tumor suppressor involved in the regulation of cell proliferation, senescence, migration and apoptosis. We identified SELENBP1 to be down-regulated in cutaneous melanoma, a malignant cancer of pigment-producing melanocytes in the skin, which leads to the assumption that SELENBP1 also functions as tumor suppressor in the skin, as shown by others e.g. for prostate or lung carcinoma. However, in vitro analyses indicate that SELENBP1 re-expression in human melanoma cell lines has no impact on cell proliferation, migration or tube formation of the tumor cells themselves when compared to control-transfected cells. Interestingly, supernatant taken from melanoma cell lines transfected with a SELENBP1 re-expression plasmid led to suppression of vessel formation of HMEC cells. Furthermore, SELENBP1 re-expression alters the sensitivity of melanoma cells for Vemurafenib treatment. The data also hint to a functional interaction of SELENBP1 with GPX1 (Glutathione peroxidase 1). Low SELENBP1 mRNA levels correlate inversely with GPX1 expression in melanoma. The re-expression of SELENBP1 combined with down-regulation of GPX1 expression led to reduction of the proliferation of melanoma cells. In summary, SELENBP1 influences the tumor microenvironment and SELENBP1 action is functionally influenced by GPX1.
EVALuna2:34070

SiRNA-Knockdown einer neuen Argonaute2 Spleißvariante verringert die tumorigenen Eigenschaften von Melanomzellen. - Linck, Lisa; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2018)
EVALuna2:203603

SOX10 promotes melanoma cell invasion by regulating melanoma inhibitory activity - Graf, Saskia A.; Busch, Christian; Besch, Robert; Berking, Carola; Bosserhoff, Anja Katrin (Journal of Investigative Dermatology, 2014)
The transcription factor SOX10 (SRY (sex determining region Y)-box 10) has a key role in the embryonic development of melanocytes. Recently, it has been suggested that SOX10 is highly relevant for melanoma development and survival. However, the distinct functions and downstream targets of SOX10 in melanoma remain widely unknown. In this study, we inhibited SOX10 via RNA interference in different human melanoma cell lines and found a significantly reduced invasion capacity in vitro and in the chick embryo model. At later time points, SOX10 inhibition reduced proliferation and induced cell death. We identified melanoma inhibitory activity (MIA) as a direct target gene of SOX10, which is an essential protein for melanoma cell migration and invasion. Expression levels of SOX10 and MIA strictly correlated in melanoma cell lines, and SOX10 inhibition reduced MIA expression and promoter activity. Direct binding of SOX10 to the MIA promoter was demonstrated by electrophoretic mobility shift assay and chromatin immunoprecipitation. Ectopic expression of MIA in SOX10-inhibited melanoma cells restored the invasion capacity, supporting the hypothesis that MIA is responsible for SOX10-mediated melanoma cell invasion. Our data provide evidence for a critical role of SOX10 in melanoma cell invasion through the regulation of MIA and highlight its role as a therapeutic target in melanoma. © 2014 The Society for Investigative Darmatology.
CRIS-Team Scopus Importer:2022-08-05

Sox21-transcriptional Regulation in malignant Melanoma - Rachinger, N.; Boßerhoff, Anja Katrin; Kuphal, Silke (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

Sox9 modulates cell survival and adipogenic differentiation of multipotent adult rat mesenchymal stem cells - Stoeckl, Sabine; Bauer, Richard J.; Goettl, Claudia; Grifka, Joachim; Graessel, Susanne; Bosserhoff, Anja Katrin (Journal of cell science, 2013)
Sox9 is a key transcription factor in early chondrogenesis with distinct roles in differentiation processes and during embryonic development. Here, we report that Sox9 modulates cell survival and contributes to the commitment of mesenchymal stem cells (MSC) to adipogenic or osteogenic differentiation lineages. We found that the Sox9 activity level affects the expression of the key transcription factor in adipogenic differentiation, C/EBPp and that cyclin D1 mediates the expression of the osteogenic marker osteocalcin in undifferentiated adult bone-marrow-derived rat MSC. Introducing a stable Sox9 knockdown into undifferentiated rat MSC resulted in a marked decrease in proliferation rate and an increase in apoptotic activity. This was linked to a profound upregulation of p21 and cyclin D1 gene and protein expression accompanied by an induction of caspase 3/7 activity and an inhibition of Bcl-2. We observed that Sox9 silencing provoked a delayed S-phase progression and an increased nuclear localization of p21. The protein stability of cyclin D1 was induced in the absence of Sox9 presumably as a function of altered p38 signalling. In addition, the major transcription factor for adipogenic differentiation, C/EBPp was repressed after silencing Sox9. The nearly complete absence of C/EBPb protein as a result of increased destabilization of the C/EBPb mRNA and the impact on osteocalcin gene expression and protein synthesis, suggests that a delicate balance of Sox9 level is not only imperative for proper chondrogenic differentiation of progenitor cells, but also affects the adipogenic and probably osteogenic differentiation pathways of MSC. Our results identified Sox9 as an important link between differentiation, proliferation and apoptosis in undifferentiated adult rat mesenchymal stem cells, emphasizing the importance of the delicate balance of a precisely regulated Sox9 activity in MSC not only for proper skeletal development during embryogenesis but probably also for successful repair and regeneration of tissues and organs in adults. © 2013 Published by The Company of Biologists Ltd.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Adipogenic differentiation; Adult msc; Cell cycle; Proliferation; Signalling; Sox9

Sox9 regulates melanocytic fate decision of adult hair follicle stem cells - Stüfchen, Isabel; Beyer, Felix; Stäbler, Sebastian; Fischer, Stefan; Kappelmann, Melanie; Beckervordersandforth, Ruth; Boßerhoff, Anja Katrin (iScience, 2023)
The bulge of hair follicles harbors Nestin+ (neural crest like) stem cells, which exhibit the potential to generate various cell types including melanocytes. In this study, we aimed to determine the role of Sox9, an important regulator during neural crest development, in melanocytic differentiation of those adult Nestin+ cells. Immunohistochemical analysis after conditional Sox9 deletion in Nestin+ cells of adult mice revealed that Sox9 is crucial for melanocytic differentiation of these cells and that Sox9 acts as a fate determinant between melanocytic and glial fate. A deeper understanding of factors that regulate fate decision, proliferation and differentiation of these stem cells provides new aspects to melanoma research as melanoma cells share many similarities with neural crest cells. In summary, we here show the important role of Sox9 in melanocytic versus glial fate decision of Nestin+ stem cells in the skin of adult mice.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Cell biology; Developmental biology; Molecular biology

Specific c-Jun target genes in malignant melanoma - Schummer, Patrick; Kuphal, Silke; Vardimon, Lily; Boßerhoff, Anja Katrin; Kappelmann, Melanie (Cancer Biology & Therapy, 2016)
A fundamental event in the development and progression of malignant melanoma is the de-regulation of cancer-relevant transcription factors. We recently showed that c-Jun is a main regulator of melanoma progression and, thus, is the most important member of the AP-1 transcription factor family in this disease. Surprisingly, no cancer-related specific c-Jun target genes in melanoma were described in the literature, so far. Therefore, we focused on pre-existing ChIP-Seq data (Encyclopedia of DNA Elements) of 3 different non-melanoma cell lines to screen direct c-Jun target genes. Here, a specific c-Jun antibody to immunoprecipitate the associated promoter DNA was used. Consequently, we identified 44 direct c-Jun targets and a detailed analysis of 6 selected genes confirmed their deregulation in malignant melanoma. The identified genes were differentially regulated comparing 4 melanoma cell lines and normal human melanocytes and we confirmed their c-Jun dependency. Direct interaction between c-Jun and the promoter/enhancer regions of the identified genes was confirmed by us via ChIP experiments. Interestingly, we revealed that the direct regulation of target gene expression via c-Jun can be independent of the existence of the classical AP-1 (5´-TGA(C/G)TCA-3´) consensus sequence allowing for the subsequent down- or up-regulation of the expression of these cancer-relevant genes. In summary, the results of this study indicate that c-Jun plays a crucial role in the development and progression of malignant melanoma via direct regulation of cancer-relevant target genes and that inhibition of direct c-Jun targets through inhibition of c-Jun is a potential novel therapeutic option for treatment of malignant melanoma.
EVALuna2:4713

Splicing control by PHF5A is crucial for melanoma cell survival - Meißgeier, Tina; Kappelmann-Fenzl, Melanie; Stäbler, Sebastian; Ahari, Ata Jadid; Mertes, Christian; Gagneur, Julien; Linck-Paulus, Lisa; Boßerhoff, Anja Katrin (Cell Proliferation, 2024)
Abnormalities in alternative splicing are a hallmark of cancer formation. In this study, we investigated the role of the splicing factor PHD finger protein 5A (PHF5A) in melanoma. Malignant melanoma is the deadliest form of skin cancer, and patients with a high PHF5A expression show poor overall survival. Our data revealed that an siRNA-mediated downregulation of PHF5A in different melanoma cell lines leads to massive splicing defects of different tumour-relevant genes. The loss of PHF5A results in an increased rate of apoptosis by triggering Fas- and unfolded protein response (UPR)-mediated apoptosis pathways in melanoma cells. These findings are tumour-specific because we did not observe this regulation in fibroblasts. Our study identifies a crucial role of PHF5A as driver for melanoma malignancy and the described underlying splicing network provides an interesting basis for the development of new therapeutic targets for this aggressive form of skin cancer.
CRIS-Team Scopus Importer:2024-09-13

Storkhead box 2 and melanoma inhibitory activity promote oral squamous cell carcinoma progression - Sasahira, Tomonori; Nishiguchi, Yukiko; Fujiwara, Rina; Kurihara, Miyako; Kirita, Tadaaki; Boßerhoff, Anja Katrin; Kuniyasu, Hiroki (Oncotarget, 2016)
Storkhead box protein 2 (STOX2) is a transcriptional factor associated with pre-eclampsia with fetal growth restriction. We recently reported that melanoma inhibitory activity (MIA) promotes oral squamous cell carcinoma (OSCC) progression. However, the relationship between STOX2 and MIA remains unknown in malignancies.We used immunohistochemistry and PCR to investigate MIA and STOX2 expression in OSCC. We also performed functional analysis in human OSCC cells.MIA and STOX2 mRNA levels were higher in OSCCs than in normal oral epithelial cells, and upregulation of STOX2 was significantly correlated with overexpression of MIA. Immunostaining for STOX2 was associated with nodal metastasis (P = 0.0002) and MIA expression (P < 0.0001). Furthermore, MIA expression (P = 0.0035) and STOX2 expression (P = 0.0061) were associated with poor outcome in OSCCs. In vitro analysis using OSCC cells revealed that MIA increased expression of STOX2 by paracrine manner. Moreover, STOX2 accelerated OSCC cell growth, invasion, suppressed apoptosis, and enhanced resistance to paclitaxel, cisplatin, and 5-FU.Our results suggest that MIA-STOX2 signaling may be a useful diagnostic and therapeutic target in OSCCs.
EVALuna2:4731

Strong reduction of AGO2 expression in melanoma and cellular consequences - Voeller, D.; Reinders, Joerg; Meister, G.; Bosserhoff, Anja Katrin (British Journal of Cancer, 2013)
Background:Processing of microRNAs (miRNAs) is a highly controlled process. Deregulation of miRNA expression was observed in several types of cancer but changes in the miRNA-processing enzymes have not been analysed until today. In this study, we analysed Argonaute2 (AGO2, EIF2C2), as one main factor of the miRNA processing ensemble, in the context of cancer development, especially in melanoma.Methods:We determined the AGO2 expression level in melanoma, as well as in other cancers, with biochemical approaches (qRT-PCR, western blot and immunofluorescence studies) and analysed the cell behaviour in migration assays.Results:Specifically in melanoma, we revealed a strong reduction of AGO2 expression compared with primary melanocytes. The reduction of AGO2 expression was only found on protein level, whereas the mRNA level stayed unchanged hinting to post-transcriptional regulation. We could show that re-expression of AGO2 in melanoma leads to a strong improvement of regulatory effects due to increased functionality of small-interfering RNAs and short hairpin RNAs.Conclusion:We identified melanoma-specific downregulation of AGO2 and corresponding reduced RNAi efficiency. These findings will help to understand the molecular basis of malignant melanoma and can potentially lead to an improvement of therapeutic strategies. © 2013 Cancer Research UK.
CRIS-Team Scopus Importer:2022-08-05

Substrate-integrated microfluidics for sensitive biosensing with complementary THz metamaterials in water - Weisenstein, Christian; Richter, Merle; Wigger, Anna Katharina; Boßerhoff, Anja Katrin; Haring Bolivar, Peter (Applied Physics Letters, 2022)
Metamaterials can be utilized for a variety of applications and have emerged as a valuable tool in THz technologies. Used as THz biosensors, metasurfaces can significantly improve the sensitivity in the detection of biomolecules, but the high THz absorption of water represents a major challenge for the realization of a sensor for measurements in liquids. In this article, we propose an approach where the resonance feature of complementary asymmetric split ring resonators (CASRR) is maintained even for measurements in water, allowing highly sensitive detection of biomolecules in strongly absorbing liquids. This is enabled by the introduction of substrate-integrated microfluidics, which are shown to have a minimal effect on the transmission properties of the metamaterial. Due to this approach, the metamaterial structure design is independent from the microfluidic channels. Our simulations also show that the sensitivity of CASRR changes only marginally for lossless and highly absorbing materials. At the same time, the presented concept is easy to fabricate by standard lithography methods and can be applied to other metamaterial structures as well. (C) 2022 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).
CRIS-Team WoS Importer:2022-02-11

Suppressive effects of tumor cell-derived 5'-deoxy-5'-methylthioadenosine on human T cells - Henrich, Frederik; Singer, Katrin; Poller, Kerstin; Bernhardt, Luise; Strobl, Carolin; Limm, Katharina; Ritter, Axel P.; Gottfried, Eva; Voelkl, Simon; Jacobs, Benedikt; Peter, Katrin; Mougiakakos, Dimitrios; et al. (OncoImmunology, 2016)
The immunosuppressive tumor microenvironment represents one of the main obstacles for immunotherapy of cancer. The tumor milieu is among others shaped by tumor metabolites such as 5'-deoxy-5'-methylthioadenosine (MTA). Increased intratumoral MTA levels result from a lack of the MTA-catabolizing enzyme methylthioadenosine phosphorylase (MTAP) in tumor cells and are found in various tumor entities. Here, we demonstrate that MTA suppresses proliferation, activation, differentiation, and effector function of antigen-specific T cells without eliciting cell death. Conversely, if MTA is added to highly activated T cells, MTA exerts cytotoxic effects on T cells. We identified the Akt pathway, a critical signal pathway for T cell activation, as a target of MTA, while, for example, p38 remained unaffected. Next, we provide evidence that MTA exerts its immunosuppressive effects by interfering with protein methylation in T cells. To confirm the relevance of the suppressive effects of exogenously added MTA on human T cells, we used an MTAP-deficient tumor cell-line that was stably transfected with the MTAP-coding sequence. We observed that T cells stimulated with MTAP-transfected tumor cells revealed a higher proliferative capacity compared to T cells stimulated with Mock-transfected cells. In conclusion, our findings reveal a novel immune evasion strategy of human tumor cells that could be of interest for therapeutic targeting.
EVALuna2:4745

Systematic Investigation of CMTM Family Genes Suggests Relevance to Glioblastoma Pathogenesis and CMTM1 and CMTM3 as Priority Targets - Delic, Sabit; Thuy, Andreas; Schulze, Markus; Proescholdt, Martin A.; Dietrich, Peter; Boßerhoff, Anja Katrin; Riemenschneider, Markus J. (Genes Chromosomes & Cancer, 2015)
The novel CKLF-like Marvel Transmembrane Domain-containing gene family (CMTM) consists of 8 members (CMTM1-8). As little is known about the oncogenic impact of these genes, we aimed to systematically investigate the relevance of CMTMs to glioblastoma pathogenesis. We performed mRNA expression analyses and survival correlations in glioblastoma patients. Moreover, we analyzed the impact of RNAi-based silencing and overexpression of CMTM family genes on tumor cell proliferation and invasion in vitro. CMTMs appeared to be widely regulated in the group of glioblastomas relative to non-neoplastic brain (NB) tissue (significant upregulation for CMTM2, 3, and 6 and significant downregulation for CMTM 4 and 8). For CMTM1, 5 and 7, we found aberrant expression levels in individual tumors. Functionally, CMTM1, 3, and 7 promoted tumor cell invasion, while CMTM1 additionally enhanced cell proliferation. In a large clinically annotated dataset, higher CMTM1 and 3 expression was significantly correlated with shorter overall survival. Our data thus suggest CMTM1 and 3 as priority targets in glioblastomas. Using a human phosphokinase protein expression profiling assay, we can provide first insights into signalling of these two genes that might be conveyed by growth factor receptor, Src family kinase and WNT activation.
CRIS-Team Scopus Importer:2022-08-05

Targeted Therapy-Resistant Melanoma Cells Acquire Transcriptomic Similarities with Human Melanoblasts - Larribere, Lionel; Kuphal, Silke; Sachpekidis, Christos; Hueser, Laura; Boßerhoff, Anja Katrin; Utikal, Jochen (Cancers, 2018)
The mechanisms of adaptive and acquired drug resistance in tumors are not completely understood. So far, gene amplifications or mutations, leading to the reactivation of the MAPK or PI3K pathways have been described. In this study, we used two different methods to generate human melanoblasts: (1) via differentiation from induced pluripotent stem cells (iPSCs) and (2) via dedifferentiation from melanocytes. The melanoblast transcriptomes were then compared to the transcriptome of MAPK inhibitor-resistant melanoma cells. We observed that the expression of genes associated with cell cycle control, DNA damage control, metabolism, and cancer was altered in both melanoblast populations and in both adaptive and acquired resistant melanoma samples, compared to drug-sensitive samples. However, genes involved in antigen presentation and cellular movement were only regulated in the melanoblast populations and in the acquired resistant melanoma samples, compared to the drug-sensitive samples. Moreover, melanocyte-derived melanoblasts and adaptive resistant melanoma samples were characterized by different expression levels of certain transcription factors or genes involved in the CDK5 pathway. In conclusion, we show here that in vitro models of human melanoblasts are very important tools to comprehend the expression profiles of drug-resistant melanoma.
EVALuna2:202903

Targeting melanoma metastasis and immunosuppression with a new mode of melanoma inhibitory activity (MIA) protein inhibition - Schmidt, Jennifer; Riechers, Alexander; Stoll, Raphael; Amann, Thomas; Fink, Florian; Spruss, Thilo; Gronwald, Wolfram; Koenig, Burkhard; Hellerbrand, Claus; Bosserhoff, Anja Katrin (PLoS ONE, 2012)
Melanoma is the most aggressive form of skin cancer, with fast progression and early dissemination mediated by the melanoma inhibitory activity (MIA) protein. Here, we discovered that dimerization of MIA is required for functional activity through mutagenesis of MIA which showed the correlation between dimerization and functional activity. We subsequently identified the dodecapeptide AR71, which prevents MIA dimerization and thereby acts as a MIA inhibitor. Two-dimensional nuclear magnetic resonance (NMR) spectroscopy demonstrated the binding of AR71 to the MIA dimerization domain, in agreement with in vitro and in vivo data revealing reduced cell migration, reduced formation of metastases and increased immune response after AR71 treatment. We believe AR71 is a lead structure for MIA inhibitors. More generally, inhibiting MIA dimerization is a novel therapeutic concept in melanoma therapy. © 2012 Schmidt et al.
CRIS-Team Scopus Importer:2022-08-05

Testing Suitability of Cell Cultures for SILAC-Experiments Using SWATH-Mass Spectrometry - Reinders, Yvonne; Voeller, Daniel; Boßerhoff, Anja Katrin; Oefner, Peter J.; Reinders, Joerg (Methods in Molecular Biology, 2016)
Precise quantification is a major issue in contemporary proteomics. Both stable-isotope-labeling and label-free methods have been established for differential protein quantification and both approaches have different advantages and disadvantages. The present protocol uses the superior precision of label-free SWATH-mass spectrometry to test for suitability of cell lines for a SILAC-labeling approach as systematic regulations may be introduced upon incorporation of the "heavy" amino acids. The SILAC-labeled cell cultures can afterwards be used for further analyses where stable-isotope-labeling is mandatory or has substantial advantages over label-free approaches such as pulse-chase-experiments and differential protein interaction analyses based on co-immunoprecipitation. As SWATH-mass spectrometry avoids the missing-value-problem typically caused by undersampling in highly complex samples and shows superior precision for the quantification, it is better suited for the detection of systematic changes caused by the SILAC-labeling and thus, can serve as a useful tool to test cell lines for changes upon SILAC-labeling.
EVALuna2:4730

Tg(Grm1) transgenic mice: A murine model that mimics spontaneous uveal melanoma in humans? - Schiffner, Susanne; Braunger, Barbara M.; De Jel, Miriam M.; Coupland, Sarah E.; Tamm, Ernst R.; Bosserhoff, Anja Katrin (Experimental Eye Research, 2014)
Although rare, uveal melanoma (UM) is the most common primary intraocular tumor in adults. About half of UM patients develop metastatic disease typically in the liver and die within a short period, due to ineffective systemic therapies. UM has unique and distinct genetic features predictive of metastasis. Animal models are required to improve our understanding of therapeutic options in disseminated UM. Since spontaneous murine UM models are lacking, our aim was to analyze the suitability of the established transgenic melanoma mouse model Tg(Grm1) as a new UM model system. We demonstrated that adult Grm1 transgenic mice develop choroidal thickening and uveal melanocytic neoplasia with expression of the melanocytic markers S100B and MelanA. Further, we showed that GRM1 is expressed in human UM, similar to skin melanoma. This study presents a new mouse model for spontaneous UM and suggests that the glutamate signaling pathway is a possible target for UM therapy. © 2014 Elsevier Ltd.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Grm1; Melanoma; Metabotropic glutamate receptor; Mouse model; Uveal melanoma

The anti-fibrotic effect of cold atmospheric plasma on localized scleroderma in vitro and in vivo - Arndt, Stephanie; Unger, Petra; Boßerhoff, Anja Katrin; Berneburg, Mark; Karrer, Sigrid (Biomedicines, 2021)
Cold Atmospheric Plasma (CAP) has shown promising results in the treatment of various skin diseases. The therapeutic effect of CAP on localized scleroderma (LS), however, has not yet been evaluated. We investigated the effects of CAP on LS by comparing human normal fibroblasts (hNF), human TGF-β-activated fibroblasts (hAF), and human localized scleroderma-derived fibroblasts (hLSF) after direct CAP treatment, co-cultured with plasma-treated human epidermal keratinocytes (hEK) and with an experimental murine model of scleroderma. In hAF and hLSF, 2 min CAP treatment with the MicroPlaSterβ® plasma torch did not affect pro-fibrotic gene expression of alpha smooth muscle actin, fibroblast activating protein, and collagen type I, however, it promoted re-expression of matrix metalloproteinase 1. Functionally, CAP treatment reduced cell migration and stress fiber formation in hAF and hLSF. The relevance of CAP treatment was confirmed in an in vivo model of bleomycin-induced dermal fibrosis. In this model, CAP-treated mice showed significantly reduced dermal thickness and collagen deposition as well as a decrease in both alpha smooth muscle actin-positive myofibroblasts and CD68-positive macrophages in the affected skin in comparison to untreated fibrotic tissue. In conclusion, this study provides the first evidence for the successful use of CAP for treating LS and may be the basis for clinical trials including patients with LS.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Anti-fibrosis; Bleomycin-induced fibrosis; Cold atmospheric plasma; Localized scleroderma

The anti-fibrotic effect of cold atmospheric plasma on localized scleroderma in vitro and in vivo - Arndt, Stephanie; Unger, Petra; Boßerhoff, Anja Katrin; Berneburg, Mark; Karrer, Sigrid (EXPERIMENTAL DERMATOLOGY, 2022)
Cold Atmospheric Plasma (CAP) has shown promising results in the treatment of various skin diseases. The therapeutic effect of CAP on localized scleroderma (LS), however, has not yet been evaluated. We investigated the effects of CAP on LS by comparing human normal fibroblasts (hNF), human TGF-β-activated fibroblasts (hAF), and human localized scleroderma-derived fibroblasts (hLSF) after direct CAP treatment, co-cultured with plasma-treated human epidermal keratinocytes (hEK) and with an experimental murine model of scleroderma. In hAF and hLSF, 2 min CAP treatment with the MicroPlaSterβ® plasma torch did not affect pro-fibrotic gene expression of alpha smooth muscle actin, fibroblast activating protein, and collagen type I, however, it promoted re-expression of matrix metalloproteinase 1. Functionally, CAP treatment reduced cell migration and stress fiber formation in hAF and hLSF. The relevance of CAP treatment was confirmed in an in vivo model of bleomycin-induced dermal fibrosis. In this model, CAP-treated mice showed significantly reduced dermal thickness and collagen deposition as well as a decrease in both alpha smooth muscle actin-positive myofibroblasts and CD68-positive macrophages in the affected skin in comparison to untreated fibrotic tissue. In conclusion, this study provides the first evidence for the successful use of CAP for treating LS and may be the basis for clinical trials including patients with LS.<br
CRIS-Team WoS Importer:2022-03-04
Keywords: anti-fibrosis; bleomycin-induced fibrosis; cold atmospheric plasma; localized scleroderma

The AP-1 transcription factor FOSL1 causes melanocyte reprogramming and transformation - Maurus, K.; Hufnagel, A.; Geiger, F.; Graf, S.; Berking, C.; Heinemann, A.; Paschen, A.; Kneitz, S.; Stigloher, C.; Geissinger, E.; Otto, C.; Boßerhoff, Anja Katrin; et al. (Oncogene, 2017)
The MAPK pathway is activated in the majority of melanomas and is the target of therapeutic approaches. Under normal conditions, it initiates the so-called immediate early response, which encompasses the transient transcription of several genes belonging to the AP-1 transcription factor family. Under pathological conditions, such as continuous MAPK pathway overactivation due to oncogenic alterations occurring in melanoma, these genes are constitutively expressed. The consequences of a permanent expression of these genes are largely unknown. Here, we show that FOSL1 is the main immediate early AP-1 member induced by melanoma oncogenes. We first examined its role in established melanoma cells. We found that FOSL1 is involved in melanoma cell migration as well as cell proliferation and anoikis-independent growth, which is mediated by the gene product of its target gene HMGA1, encoding a multipotent chromatin modifier. As FOSL1 expression is increased in patient melanoma samples compared to nevi, we investigated the effect of enhanced FOSL1 expression on melanocytes. Intriguingly, we found that FOSL1 acts oncogenic and transforms melanocytes, enabling subcutaneous tumor growth in vivo. During the process of transformation, FOSL1 reprogrammed the melanocytes and downregulated MITF in a HMGA1-dependent manner. At the same time, AXL was upregulated, leading to a shift in the MITF/AXL balance. Furthermore, FOSL1 re-enforced pro-tumorigenic transcription factors MYC, E2F3 and AP-1. Together, this led to the enhancement of several growth-promoting processes, such as ribosome biogenesis, cellular detachment and pyrimidine metabolism. Overall, we demonstrate that FOSL1 is a novel reprogramming factor for melanocytes with potent tumor transformation potential.
EVALuna2:4756

The cartilage protein melanoma inhibitory activity contributes to inflammatory arthritis - Yeremenko, Nataliya G.; van Tok, Melissa N.; van Duivenvoorde, Leonie M.; Baeten, Dominique L.P.; et al. (British Journal of Rheumatology, 2014)

The delta subunit of rod-specific photoreceptor cgmp phosphodiesterase (Pde6d) contributes to hepatocellular carcinoma progression - Dietrich, Peter; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Cancers, 2019)
Emerging evidence reveals crucial roles of wild type RAS in liver cancer. The delta subunit of rod-specific photoreceptor cGMP phosphodiesterase (PDE6D) regulates the trafficking of RAS proteins to the plasma membrane and thereby contributes to RAS activation. However, the expression and specific function of PDE6D in hepatocellular carcinoma (HCC) were completely unknown. In this study, PDE6D was newly found to be markedly upregulated in HCC tissues and cell lines. Overexpression of PDE6D in HCC correlated with enhanced tumor stages, tumor grading, and ERK activation. PDE6D depletion significantly reduced proliferation, clonogenicity, and migration of HCC cells. Moreover, PDE6D was induced by TGF-_1, the mediator of stemness, epithelial-mesenchymal transition (EMT), and chemoresistance. In non-resistant cells, overexpression of PDE6D conferred resistance to sorafenib-induced toxicity. Further, PDE6D was overexpressed in sorafenib resistance, and inhibition of PDE6D reduced proliferation and migration in sorafenib-resistant HCC cells. Together, PDE6D was found to be overexpressed in liver cancer and correlated with tumor stages, grading, and ERK activation. Moreover, PDE6D contributed to migration, proliferation, and sorafenib resistance in HCC cells, therefore representing a potential novel therapeutic target.
CRIS-Team Scopus Importer:2019-05-02
Keywords: HCC; KRAS; PDE6D; Sorafenib; TGF-β

The importance of melanoma inhibitory activity gene family in the tumor progression of oral cancer - Sasahira, Tomonori; Boßerhoff, Anja Katrin; Kirita, Tadaaki (Pathology International, 2018)
Oral squamous cell carcinoma has a high potential for locoregional invasion and nodal metastasis. Consequently, early detection of such malignancies is of immense importance. The melanoma inhibitory activity (MIA) gene family comprises MIA, MIA2, transport and Golgi organization protein 1 (TANGO), and otoraplin (OTOR). These members of the MIA gene family have a highly conserved Src homology 3 (SH3)-like structure. Although the molecules of this family share 34-45% amino acid homology and 47-59% cDNA sequence homology, those members, excluding OTOR, play different tumor-associated functions. MIA has a pivotal role in the progression and metastasis of melanoma; MIA2 and TANGO have been suggested to possess tumor-suppressive functions; and OTOR is uniquely expressed in cochlea of the inner ear. Therefore, the definite functions of the MIA gene family in cancer cells remain unclear. Since the members of the MIA gene family are secreted proteins, these molecules might be useful tumor markers that can be detected in the body fluids, including serum and saliva. In this review, we described the molecular biological functions of the MIA gene family in oral cancer.
EVALuna2:34285

The metabolite 5′-methylthioadenosine signals through the adenosine receptor A2B in melanoma - Limm, Katharina; Wallner, Susanne; Milenkovi, Vladimir M.; Wetzel, Christian H.; Bosserhoff, Anja Katrin (European Journal of Cancer, 2014)
Several recent studies have shown evidence supporting the general knowledge that tumour cells exhibit changes in metabolism. It is becoming increasingly important to understand how these metabolic changes in tumour cells promote carcinogenesis and disease progression. We recently discovered a lack of methylthioadenosine phosphorylase (MTAP) expression in melanoma, which resulted in an accumulation of the metabolite 5′-methylthioadenosine (MTA) in melanoma cells and in the extracellular environment. MTA was shown to affect cell proliferation of surrounding stroma cells and cell invasiveness and the activation of the transcription factor activator protein-1 (AP-1) in melanoma cells. In this study, we addressed the regulation of cellular signalling by extracellular MTA accumulation. By focusing on putative receptors that could modulate MTA signalling, we identified the adenosine receptor ADORA2B as an important candidate. Knockdown experiments and the use of specific agonists and antagonists confirmed a link between MTA and AP-1 signalling through the ADORA2B receptor. Interestingly, stimulation of the cells with MTA did not result in activation of the classical cyclic adenosine monophosphate (cAMP) signalling cascades or in Ca2+-dependent signalling. We instead showed protein kinase C (PKC) signalling to be involved in MTA-mediated AP-1 activation. In summary, we identified ADORA2B to be the specific receptor and signalling pathway for the metabolite MTA. These findings may influence the use of MTA in a therapeutic manner.
CRIS-Team Scopus Importer:2022-08-05
Keywords: 5′-Methylthioadenosine; Adenosine receptor A2B; AP-1-trascription factor; CREB-1 pathway; MAPK/ERK - PKC signalling; Melanoma

The molecular Effects of cold atmospheric Plasma on malignant Melanoma - Zimmermann, Tom; Schneider, Christin; Gebhardt, L.; Arndt, S.; Karrer, S.; Zimmermann, J. L.; Fischer, M. J. M.; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2020)
CRIS-Team WoS Importer:2020-09-11

The myelin protein PMP2 is regulated by SOX10 and drives melanoma cell invasion - Graf, Saskia Anna; Heppt, Markus Vincent; Wessely, Anja; Krebs, Stefan; Kammerbauer, Claudia; Hornig, Eva; Strieder, Annamarie; Blum, Helmut; Boßerhoff, Anja Katrin; Berking, Carola (Pigment Cell & Melanoma Research, 2019)
The transcription factor sex determining region Y-box 10 (SOX10) plays a key role in the development of melanocytes and glial cells from neural crest precursors. SOX10 is involved in melanoma initiation, proliferation, invasion, and survival. However, specific mediators which impart its oncogenic properties remain widely unknown. To identify target genes of SOX10, we performed RNA sequencing after ectopic expression of SOX10 in human melanoma cells. Among nine differentially regulated genes, peripheral myelin protein 2 (PMP2) was consistently upregulated in several cell lines. Direct regulation of PMP2 by SOX10 was shown by chromatin immunoprecipitation, electrophoretic mobility shift, and luciferase reporter assays. Moreover, a coregulation of PMP2 by SOX10 and early growth response 2 in melanoma cells was found. Phenotypical investigation demonstrated that PMP2 expression can increase melanoma cell invasion. As PMP2 protein was detected only in a subset of melanoma cell lines, it might contribute to melanoma heterogeneity.
CRIS-Team Scopus Importer:2019-05-07
Keywords: glial cell; heterogeneity; invasion; melanoma; PMP2; Schwann cell; SOX10

The neurotrophin Neuritin1 (cpg15) is involved in melanoma migration, attachment independent growth, and vascular mimicry - Boßerhoff, Anja Katrin; Schneider, Nadja; Ellmann, Lisa; Heinzerling, Lucie; Kuphal, Silke (Oncotarget, 2017)
The neurotrophin Neuritin1 (NRN1; cpg15) belongs to the candidate plasticity gene (CPG) family and is expressed in postmitotic-differentiating neurons of the developmental nervous system and neuronal structures associated with plasticity in the brain of human adult.Our newest findings document that NRN1 deregulation could contribute also to disease development and have impact on malignant melanoma. Our analyses displayed the over-expression of NRN1 in melanoma in vitro and in vivo, shown by immunohistochemistry and qRT-PCR on microdissected melanoma tissue; furthermore, soluble NRN1 was detectable in tissue culture supernatant and serum of melanoma patients.To investigate the role of NRN1 in melanoma we performed knockdown, over-expression and recombinant-NRN1-treatment experiments affiliated by functional assays. Our results show that migration, attachment independent growth and vasculogenesis were affected after manipulation of NRN1 on endogenous and extrinsic level. Interestingly, high NRN1 serum levels correlate with low MIA serum levels (< 10ng/ml). Therefore, we speculate that NRN1 could be a marker for early melanoma stages, in particular.In summary, we detected an overexpression of NRN1 in melanoma patient. In functional cell culture experiments we found a correlation between NRN1 expression and the cancerous behavior of melanoma cells.
EVALuna2:4752

The Nuclear Envelope Proteins LMNB1 and LBR influence the Chromatin Structure and Senescence Processes in Melanoma - Lämmerhirt, Lisa; Pommer, Michaela; Zimmermann, Tom; Kluge, Viola; Kuphal, Silke; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

The Role of NRN1 in the Development and Progression of malignant Melanoma - Haller, Lucia; Reichelt, Judith; Boßerhoff, Anja Katrin; Kuphal, Silke (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

The Role of T-Cadherin (CDH13) in Treatment Options with Garcinol in Melanoma - Stäbler, Sebastian; Hoechst, Sebastian; Thongmao, Aranya; Schneider, Nadja; Boßerhoff, Anja Katrin; Kuphal, Silke (Cancers, 2024)
Targeted therapies with chemotherapeutic agents and immunotherapy with checkpoint inhibitors are among the systemic therapies recommended in the guidelines for clinicians to treat melanoma. Although there have been constant improvements in the treatment of melanoma, resistance to the established therapies continues to occur. Therefore, the purpose of this study was to explore the function of garcinol with regards to specific cancer properties such as proliferation and apoptosis. Garcinol, a natural compound isolated from the plant also known as mangosteen (Garcinia mangostana), is a newly discovered option for cancer treatment. Numerous pharmaceutical substances are derived from plants. For example, the derivates of camptothecin, extracted from the bark of the Chinese tree of happiness (Camptotheca acuminate), or paclitaxel, extracted from the bark of the Western yew tree (Taxus brevifolia), are used as anti-cancer drugs. Here, we show that garcinol reduced proliferation and induced apoptosis in melanoma cell lines. In addition, we found that those cells that are positive for the expression of the cell–cell adhesion molecule T-cadherin (CDH13) respond more sensitively to treatment with garcinol. After knock-down experiments with an siRNA pool against T-cadherin, the sensitivity to garcinol decreased and proliferation and anti-apoptotic behavior of the cells was restored. We conclude that patients who are T-cadherin-positive could especially benefit from a therapy with garcinol.
CRIS-Team Scopus Importer:2024-06-07
Keywords: CDH13; garcinol; malignant melanoma; T-cadherin

The Role of the Transcription Factor AP2e in the Development of malignant Melanoma - Stabler, S.; Rottensteiner-Brandl, Ulrike; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2021)
CRIS-Team WoS Importer:2021-09-24

The splicing factor PHF5A influences the growth and variability of melanoma cells - Meissgeier, T.; Linck-Paulus, Lisa; Boßerhoff, Anja Katrin (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2022)
CRIS-Team WoS Importer:2022-09-23

The transcription factor activating enhancer-binding protein epsilon (AP-2ε) regulates the core promoter of type II collagen (COL2A1) - Niebler, Stephan; Bosserhoff, Anja Katrin (Febs Journal, 2013)
The transcription factor activating enhancer-binding protein epsilon (AP-2ε) was recently shown to be expressed during late chondrocyte differentiation, especially in hypertrophic chondrocytes. In this study, we were able to reveal that the promoter of the type II collagen (COL2A1) gene, encoding the extracellular matrix protein type II collagen, is specifically regulated by AP-2ε. Expression of COL2A1 is downregulated at the transition of chondroblasts into hypertrophic chondrocytes and our data provide evidence that AP-2ε is involved in this process. In reporter gene assays, overexpression of AP-2ε in cartilaginous cell lines resulted in a significant reduction in COL2A1 core promoter activity of 45%. Furthermore, we found that this process is dose-dependent and highly specific for the epsilon isoform. Computational analysis offered only a single putative AP-2-binding motif within the chosen promoter fragment but site-directed mutagenesis revealed this motif to be regulatory inactive. After expanding our screening to motifs containing minor differences from the classical AP-2 consensus sequence (5′-GCCN3GGC-3′), we determined the sequence 5′-GCCCAGGC-3′ ranging from position -128 to -135 bp as an important regulatory site and responsible for COL2A1 downregulation through AP-2ε. Interaction of AP-2ε with the COL2A1 promoter at this site was confirmed by chromatin immunoprecipitation and electromobility shift assay. Further, our experiments suggest that at least one additional factor is involved in this process. This is the first study to prove regulation of COL2A1 by AP-2ε highlighting the role of the transcription factor as a modulator of cartilage development. © 2013 FEBS.
CRIS-Team Scopus Importer:2022-08-05
Keywords: AP-2ε; cartilage; chondrocytes; COL2A1; transcriptional regulation

THz Detection of Biomolecules in Aqueous Environments-Status and Perspectives for Analysis Under Physiological Conditions and Clinical use - Weisenstein, Christian; Wigger, Anna Katharina; Richter, Merle; Sczech, Robert; Boßerhoff, Anja Katrin; Bolivar, Peter Haring (Journal of Infrared, Millimeter, and Terahertz Waves, 2021)
Bioanalytical THz sensing techniques have proven to be an interesting and viable tool for the label-free detection and analysis of biomolecules. However, a major challenge for THz bioanalytics is to perform investigations in the native aqueous environments of the analytes. This review recapitulates the status and future requirements for establishing THz biosensing as a complementary toolbox in the repertoire of standard bioanalytic methods. The potential use in medical research and clinical diagnosis is discussed. Under these considerations, this article presents a comprehensive categorization of biochemically relevant analytes that have been investigated by THz sensing techniques in aqueous media. The detectable concentration levels of ions, carbohydrates, (poly-)nucleotides, active agents, proteins and different biomacromolecules from THz experiments are compared to characteristic physiological concentrations and lower detection limits of state-of-the-art bioanalytical methods. Finally, recent experimental developments and achievements are discussed, which potentially pave the way for THz analysis of biomolecules under clinically relevant conditions.
CRIS-Team WoS Importer:2021-06-18

THz Metamaterial Biodetection Platform for Label-Free, Sensitive and Selective DNA-, Protein- or Supermolecular-Based Biomarker Analysis - Richter, Merle; Loth, Yannik; Rachinger, Nicole; Wigger, Anna K.; Boßerhoff, Anja Katrin; Bolívar, Peter Haring (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
This work is dedicated to present a versatile, metamaterial-based sensing platform for biomarker detection in the THz frequency regime. The sensor can be classified as frequency selective surface and exhibits a characteristic dual resonance feature in the transmission frequency response which has been proven to perform well in biosensing applications. The platform is able to selectively detect proteins such as transcription factor EGR2 (early growth response protein 2) from a complex sample matrix with more than 7 · 103 other protein species, to sensitively detect reverse-transcribed MIA (melanoma inhibitory activity) DNA from a complex sample matrix and to respond to extracellular vesicular structures as well.
CRIS-Team Scopus Importer:2024-07-19
Keywords: EGR2; melanoma; metamaterial-based biosensing; metasurface; MIA; sensitivity; specificity; THz spectroscopy

Transcription factor activating enhancer-binding protein 2ε (AP2ε) modulates phenotypic plasticity and progression of malignant melanoma - Stäbler, Sebastian; Rottensteiner-Brandl, Ulrike; El Ahmad, Zubeir; Kappelmann-Fenzl, Melanie; Arkudas, Andreas; Kengelbach-Weigand, Annika; Boßerhoff, Anja Katrin; Schmidt, Sonja (Cell Death & Disease, 2024)
Malignant melanoma, the most aggressive form of skin cancer, is often incurable once metastatic dissemination of cancer cells to distant organs has occurred. We investigated the role of Transcription Factor Activating Enhancer-Binding Protein 2ε (AP2ε) in the progression of metastatic melanoma. Here, we observed that AP2ε is a potent activator of metastasis and newly revealed AP2ε to be an important player in melanoma plasticity. High levels of AP2ε lead to worsened prognosis of melanoma patients. Using a transgenic melanoma mouse model with a specific loss of AP2ε expression, we confirmed the impact of AP2ε to modulate the dynamic switch from a migratory to a proliferative phenotype. AP2ε deficient melanoma cells show a severely reduced migratory potential in vitro and reduced metastatic behavior in vivo. Consistently, we revealed increased activity of AP2ε in quiescent and migratory cells compared to heterogeneously proliferating cells in bioprinted 3D models. In conclusion, these findings disclose a yet-unknown role of AP2ε in maintaining plasticity and migration in malignant melanoma cells.
CRIS-Team Scopus Importer:2024-05-31

Transcriptome sequencing of melanocytic nevi and melanomas from Grm1 transgenic mice to determine melanoma driver mutations - De Jel, Miriam M.; Engelmann, Julia C.; Kunz, Manfred; Schiffner, Susanne; Kuphal, Silke; Bosserhoff, Anja K. (Pigment Cell & Melanoma Research, 2014)
CRIS-Team Scopus Importer:2022-08-05

Transport and Golgi organisation protein 1 is a novel tumour progressive factor in oral squamous cell carcinoma - Sasahira, Tomonori; Kirita, Tadaaki; Yamamoto, Kazuhiko; Ueda, Nobuhiro; Kurihara, Miyako; Matsushima, Sayako; Bhawal, Ujjal K.; Bosserhoff, Anja Katrin; Kuniyasu, Hiroki (European Journal of Cancer, 2014)
Transport and Golgi organisation protein 1 (TANGO), also known as MIA3, belongs to the melanoma inhibitory activity (MIA) gene family. Although MIA acts as an oncogene, MIA2 and TANGO have a tumour-suppressive function in several malignancies; accordingly, the role and function of the MIA gene family in tumours remain controversial. Here the roles of TANGO were investigated in oral squamous cell carcinoma (OSCC). We analysed expression and function of TANGO in human OSCC cell lines. TANGO expression was also examined in 171 cases of primary OSCC by immunohistochemistry and statistically assessed the correlation between TANGO positivity and the clinicopathological parameters including vessel density. By TANGO knockdown in OSCC cells, the growth and invasion were repressed and apoptosis was induced. Activities of platelet-derived growth factor beta polypeptide (PDGFB) and Neuropilin2 were inhibited by TANGO knockdown. TANGO immunoreactivity was detected in 35.1% (60/171) cases of OSCC. TANGO expression was strongly associated with tumour progression, nodal metastasis, clinical stage and number of blood or lymph vessels in OSCC. Patients showing TANGO-expression fared significantly worse disease-free survival than cases without TANGO expression. These findings suggest that TANGO might promote angiogenesis and lymphangiogenesis by upregulation of PDGFB and Neuropilin2 in OSCC. © 2014 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Angiogenesis; Lymphangiogenesis; MIA; Neuropilin2; Oral cancer; PDGFB; TANGO

Tumor Cells Develop Defined Cellular Phenotypes After 3D-Bioprinting in Different Bioinks - Schmidt, Sonja; Schmid, Rafael; Arkudas, Andreas; Kengelbach-Weigand, Annika; Boßerhoff, Anja Katrin (Cells, 2019)
Malignant melanoma is often used as a model tumor for the establishment of novel therapies. It is known that two-dimensional (2D) culture methods are not sufficient to elucidate the various processes during cancer development and progression. Therefore, it is of major interest to establish defined biofabricated three-dimensional (3D) models, which help to decipher complex cellular interactions. To get an impression of their printability and subsequent behavior, we printed fluorescently labeled melanoma cell lines with Matrigel and two different types of commercially available bioinks, without or with modification (RGD (Arginine-Glycine-Aspartate)-sequence/laminin-mixture) for increased cell-matrix communication. In general, we demonstrated the printability of melanoma cells in all tested biomaterials and survival of the printed cells throughout 14 days of cultivation. Melanoma cell lines revealed specific differential behavior in the respective inks. Whereas in Matrigel, the cells were able to spread, proliferate and form dense networks throughout the construct, the cells showed no proliferation at all in alginate-based bioink. In gelatin methacrylate-based bioink, the cells proliferated in clusters. Surprisingly, the modifications of the bioinks with RGD or the laminin blend did not affect the analyzed cellular behavior. Our results underline the importance of precisely adapting extracellular matrices to individual requirements of specific 3D bioprinting applications.
CRIS-Team WoS Importer:2019-11-29

Two novel CreERT2 transgenic mouse lines to study melanocytic cells in vivo - Stüfchen, Isabel; Beckervordersandforth, Ruth; Fischer, Stefan; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin; Beyer, Felix (Pigment Cell & Melanoma Research, 2022)
The skin of adult mammals protects from radiation, physical and chemical insults. While melanocytes and melanocyte-producing stem cells contribute to proper skin function in healthy organisms, dysfunction of these cells can lead to the generation of malignant melanoma—the deadliest type of skin cancer. Addressing cells of the melanocyte lineage in vivo represents a prerequisite for the understanding of melanoma on cellular level and the development of preventive and treatment strategies. Here, the inducible Cre-loxP-system has emerged as a promising tool to specifically target, monitor, and modulate cells in adult mice. Re-analysis of existing sequencing data sets of melanocytic cells revealed that genes with a known function in neural cells, including neural stem cells (Aldh1L1 and Nestin), are also expressed in melanocytic cells. Therefore, in this study, we explored whether the promoter activity of Nestin and Aldh1L1 can serve to target cells of the melanocyte lineage using the inducible CreERT2-loxP-system. Using an immunohistochemical approach and different time points of analysis, we were able to map the melanocytic fate of recombined stem cells in the adult hair follicle of Nestin-CreERT2 and Aldh1L1-CreERT2 transgenic mice. Thus, we here present two new mouse models and propose their use to study and putatively modulate adult melanocytic cells in vivo.
CRIS-Team Scopus Importer:2022-09-02
Keywords: Aldh1L1-CreER; inducible Cre mouse line; melanocyte; melanocyte stem cell; multipotent stem cell; Nestin-CreER

Ultrasensitive marker-free biomolecular THz-detection for tumor-related analytics - Richter, Merle; Loth, Yannik; Weisenstein, Christian; Wigger, Anna Katharina; Schaar, Dominik; Boßerhoff, Anja Katrin; Bolivar, Peter Haring (Frequenz, 2022)
Terahertz (THz) biosensing has emerged as an important research field, mainly driven by the resonant behavior of many biomolecules in this spectral range which holds potential for highly sensitive analyses. In this work, we present a detailed overview of our current research on THz biosensing, focusing on the development and analysis of THz biosensors based on frequency selective surfaces (FSS) for two different measurement scenarios: i) label-free, highly sensitive and selective analysis of dried biomolecules, and ii) sensitive and selective analysis in an aqueous environment. With our carefully designed THz biosensor for measurements in the dry state, we were able to indirectly measure tumor-marker MIA RNA in a concentration as low as 1.55 x 10(-12) mol/L, without the need for biochemical amplification. Our biosensor with substrate-integrated microfluidics for terahertz measurements in an aqueous environment is validated by simulations, showing that the resonance feature in the frequency response of our sensor is maintained even for measurements in water.
CRIS-Team WoS Importer:2022-11-18

Ultrasensitive THz biosensor for PCR-free cDNA detection based on frequency selective surfaces - Weisenstein, Christian; Schaar, Dominik; Wigger, Anna Katharina; Schäfer-Eberwein, Heiko; Boßerhoff, Anja Katrin; Bolívar, Peter Haring (Biomedical Optics Express, 2020)
THz technologies are a powerful tool for label-free detection of biomolecules. However, significant reduction of the lower detection limit is required to apply THz-sensors in biomedical diagnosis. This paper reports an ultrasensitive THz-biosensor based on asymmetric double split ring resonators (aDSRR) for the direct label- and PCR-free detection of DNA at physiologically relevant concentrations. We introduce selective functionalization and localized electric field concentration to enhance aDSRR sensitivity and specificity. The sensor characteristics are demonstrated using the human tumor marker MIA in cDNA samples produced from total RNA without PCR-amplification. Measurements of DNA samples with concentrations as low as 1.55 × 10−12 mol/l are presented.
CRIS-Team Scopus Importer:2020-02-14

Usability and Suitability of the Omics-Integrating Analysis Platform tranSMART for Translational Research and Education - Christoph, Jan; Knell, Christian; Boßerhoff, Anja Katrin; Naschberger, Elisabeth; Stürzl, Michael; Rübner, Matthias; Seuß, Hannes; Ruh, Manuel; Prokosch, Hans-Ulrich; Sedlmayr, Brita (Applied Clinical Informatics, 2017)
Platforms like tranSMART assist researchers in analyzing clinical and corresponding omics data. Usability is an important, yet often overlooked, factor affecting the adoption and meaningful use. Analyses on the specific needs of translational researchers and considerations about the application of such platforms for education are rare. The aim of this study was to test whether tranSMART can be used in education and how well medical students and professional researchers can handle it; to identify which kind of translational researchers-in terms of skills, experienced limitations, and available data-can take advantage of tranSMART; and to evaluate the usability and to generate recommendations for improvements. An online-based test has been done by medical students (N = 109) and researchers (N = 26). The test comprised 13 tasks in the context of four typical research scenarios based on experimental and clinical data. A web questionnaire was provided to identify both the needs and the conditions of research as well as to evaluate the system's usability based on the "System Usability Scale" (SUS). Students and researchers were able to handle tranSMART well and coped with most scenarios: cohort identification, data exploration, hypothesis generation, and hypothesis validation were answered with a rate of correctness between 82 and 100%. Of the total, 72.2% of the teaching researchers considered tranSMART suitable for their lessons and 84.6% of the researchers considered the platform useful for their daily work; 65.4% of the researchers named the nonavailability of a platform like tranSMART as a restriction on their research. The usability was rated "acceptable" with a SUS of 70.8. tranSMART is potentially suitable for education purposes and fits most of the needs of translational researchers. Improvements are needed on the presentation of analysis results and on the guidance of users through the analysis, especially to ensure the compliance of the analysis with the requirements of statistical testing.
EVALuna2:195

UVB radiation represses CYLD expression in melanocytes - Kuphal, Silke; Schneider, Nadja; Massoumi, Ramin; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Oncology Letters, 2017)
CYLD lysine 63 deubiquitinase (CYLD) was originally identified as a tumor suppressor that is mutated in familial cylindromatosis. Unlike in cylindromatosis, downregulation of the deubiquitinase CYLD in melanoma, a highly aggressive tumor, is not caused by mutations in the CYLD gene, but rather by a constitutive and high expression of the snail family transcriptional repressor 1 (SNAIL1). A reduced CYLD level leads to B-cell lymphoma-3/p50/p52-dependent nuclear factor-κB activation, which in turn triggers the expression of genes such as cyclin D1 and N-cadherin. Elevated levels of cyclin D1 and N-cadherin promote melanoma proliferation and invasion. By analyzing the regulation of CYLD expression in melanocytes, the present study identified a signaling pathway that is regulated in response to ultraviolet B (UVB) radiation in melanocytes. UVB light leads to an extracellular signal-regulated kinase-mediated induction of SNAIL1 and subsequent downregulation of CYLD expression in normal human epithelial melanocytes. The UVB-mediated suppression of CYLD in melanocytes may have a key role in the reaction to UV stimuli, and may also potentially be involved in the early malignant transformation processes.
EVALuna2:35803

Validation Study: Response-Predictive Gene Expression Profiling of Glioma Progenitor Cells In Vitro - Moeckel, Sylvia; Vollmann-Zwerenz, Arabel; Proescholdt, Martin; Brawanski, Alexander; Riemenschneider, Markus J.; Bogdahn, Ulrich; Boßerhoff, Anja Katrin; Spang, Rainer; Hau, Peter (PLoS ONE, 2016)
In a previous publication we introduced a novel approach to identify genes that hold predictive information about treatment outcome. A linear regression model was fitted by using the least angle regression algorithm (LARS) with the expression profiles of a construction set of 18 glioma progenitor cells enhanced for brain tumor initiating cells (BTIC) before and after in vitro treatment with the tyrosine kinase inhibitor Sunitinib. Profiles from treated progenitor cells allowed predicting therapy-induced impairment of proliferation in vitro. Prediction performance was validated in leave one out cross validation.In this study, we used an additional validation set of 18 serum-free short-term treated in vitro cell cultures to test the predictive properties of the signature in an independent cohort. We assessed proliferation rates together with transcriptome-wide expression profiles after Sunitinib treatment of each individual cell culture, following the methods of the previous publication.We confirmed treatment-induced expression changes in our validation set, but our signature failed to predict proliferation inhibition. Neither re-calculation of the combined dataset with all 36 BTIC cultures nor separation of samples into TCGA subclasses did generate a proliferation prediction.Although the gene signature published from our construction set exhibited good prediction accuracy in cross validation, we were not able to validate the signature in an independent validation data set. Reasons could be regression to the mean, the moderate numbers of samples, or too low differences in the response to proliferation inhibition in the validation set. At this stage and based on the presented results, we conclude that the signature does not warrant further developmental steps towards clinical application.
EVALuna2:4729

Variation of different histone deacetylases and the functional effects of HDAC inhibitors in hepatocellular carcinoma - Freese, Kim; Dietrich, Peter; Boßerhoff, Anja Katrin; Hellerbrand, Claus (JOURNAL OF HEPATOLOGY, 2019)
CRIS-Team WoS Importer:2019-05-07

When Mechanical Stress Matters: Generation of Polyploid Giant Cancer Cells in Tumor-Like Microcapsules - Antonelli, Yasmin; Krüger, René; Bühler, Adrian; Monavari, Mahshid; Fuentes Chandia, Miguel Angel; Colombo, Federico; Palmisano, Ralf; Boßerhoff, Anja Katrin; Kappelmann-Fenzl, Melanie; Schödel, Johannes; Boccaccini, Aldo R.; Selhuber-Unkel, Christine; et al. (Advanced Functional Materials, 2024)
Biofabrication techniques enable the performance of bioinspired three-dimensional (3D) matrices resembling primary tumors. To validate their reliability, embedded cells may express complex biophysical responses. Among others, the emergence of tumor heterogeneity and the generation of Polyploid Giant Cancer Cells (PGCC), as a result of the mechanical stress, are two of the most challenging hallmarks to resemble in vitro. Here, these phenomena are studied in cells cultured on two-dimensional (2D) flasks, in 3D spheroids, or immobilized within 3D polymer-based tumor-like microcapsules. These results show that cells cultured in 3D microcapsules exhibited an enhanced biomechanical heterogeneity, a higher number of PGCC, and an increased exertion of cell-matrix attachment forces with respect to the other two experimental conditions. Additionally, cells isolated from tumor-like microcapsules redistribute and align the cytoplasmatic protein Caveolin-1, and upregulate markers involved in cell proliferation (i.e., Ki67), metastasis (i.e., TGF-β1, TGF-β-R2), and epithelial to mesenchymal transition, to name a few. These hallmarks are barely described in the past as a result of the confinement and mechanical stress. Thus, in this work it is demonstrated that both the mechanical stress and confinement are required to stimulate cell polyploidy and biomechanical heterogeneity, which can be easily addressed by immobilizing breast cancer cells in tumor-like microcapsules.
CRIS-Team Scopus Importer:2024-02-16
Keywords: 3D cell culture; cancer biomechanics; intratumor heterogeneity; Polyploid giant cancer cells; Tumor-like microcapsules

Wild type Kirsten rat sarcoma is a novel microRNA-622-regulated therapeutic target for hepatocellular carcinoma and contributes to sorafenib resistance - Dietrich, Peter; Koch, Andreas; Fritz, Valerie; Hartmann, Arndt; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Gut, 2017)
Sorafenib is the only effective therapy for advanced hepatocellular carcinoma (HCC). Combinatory approaches targeting mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK)- and phosphatidylinositol-4,5-bisphosphate-3-kinase (PI3K)/protein-kinase B(AKT) signalling yield major therapeutic improvements. RAS proteins regulate both RAF/MAPK and PI3K/AKT signalling. However, the most important RAS isoform in carcinogenesis, Kirsten rat sarcoma (KRAS), remains unexplored in HCC.Human HCC tissues and cell lines were used for expression and functional analysis. Sorafenib-resistant HCC cells were newly generated. RNA interference and the novel small molecule deltarasin were used for KRAS inhibition both in vitro and in a murine syngeneic orthotopic HCC model.Expression of wild type KRAS messenger RNA and protein was increased in HCC and correlated with extracellular-signal regulated kinase (ERK) activation, proliferation rate, advanced tumour size and poor patient survival. Bioinformatic analysis and reporter assays revealed that KRAS is a direct target of microRNA-622. This microRNA was downregulated in HCC, and functional analysis demonstrated that KRAS-suppression is the major mediator of its inhibitory effect on HCC proliferation. KRAS inhibition markedly suppressed RAF/ERK and PI3K/AKT signalling and proliferation and enhanced apoptosis of HCC cells in vitro and in vivo. Combinatory KRAS inhibition and sorafenib treatment revealed synergistic antitumorigenic effects in HCC. Sorafenib-resistant HCC cells showed elevated KRAS expression, and KRAS inhibition resensitised sorafenib-resistant cells to suppression of proliferation and induction of apoptosis.KRAS is dysregulated in HCC by loss of tumour-suppressive microRNA-622, contributing to tumour progression, sorafenib sensitivity and resistance. KRAS inhibition alone or in combination with sorafenib appears as novel promising therapeutic strategy for HCC.
EVALuna2:4776

Wild-type KRAS is a novel therapeutic target for melanoma contributing to primary and acquired resistance to BRAF inhibition - Dietrich, Peter; Kuphal, Silke; Spruss, T.; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Oncogene, 2017)
Malignant melanoma reveals rapidly increasing incidence and mortality rates worldwide. By now, BRAF inhibition is the standard therapy for advanced melanoma in patients carrying BRAF mutations. However, only approximately 50% of melanoma patients harbor therapeutically attackable BRAF mutations, and overall survival after treatment with BRAF inhibitors is modest. KRAS (Kirsten Rat sarcoma) proteins are acting upstream of BRAF and have a major role in human cancer. Recent approaches awaken the hope to use KRAS inhibition (KRASi) as a clinical tool. In this study, we identified wild-type KRAS as a novel therapeutic target in melanoma. KRASi functions synergistically with BRAF inhibition to reduce melanoma proliferation and to induce apoptosis independently of BRAF mutational status. Moreover, acquired resistance to BRAF inhibitors in melanoma is dependent on dynamic regulation of KRAS expression with subsequent AKT and extracellular-signal regulated kinase activation and can be overcome by KRASi. This suggests KRASi as novel approach in melanoma-alone or in combination with other therapeutic regimes.Oncogene advance online publication, 23 October 2017; doi:10.1038/onc.2017.391.
EVALuna2:4759

WLS inhibits melanoma cell proliferation through the β-catenin signalling pathway and induces spontaneous metastasis - Yang, Pei-Tzu; Anastas, Jamie N.; Toroni, Rachel A.; Shinohara, Michi M.; Goodson, Jamie M.; Bosserhoff, Anja K.; Chien, Andy J.; Moon, Randall T. (Embo Molecular Medicine, 2012)
Elevated levels of nuclear β-catenin are associated with higher rates of survival in patients with melanoma, raising questions as to how ß-catenin is regulated in this context. In the present study, we investigated the formal possibility that the secretion of WNT ligands that stabilize ß-catenin may be regulated in melanoma and thus contributes to differences in ß-catenin levels. We find that WLS, a conserved transmembrane protein necessary for WNT secretion, is decreased in both melanoma cell lines and in patient tumours relative to skin and to benign nevi. Unexpectedly, reducing endogenous WLS with shRNAs in human melanoma cell lines promotes spontaneous lung metastasis in xenografts in mice and promotes cell proliferation in vitro. Conversely, overexpression of WLS inhibits cell proliferation in vitro. Activating β-catenin downstream of WNT secretion blocks the increased cell migration and proliferation observed in the presence of WLS shRNAs, while inhibiting WNT signalling rescues the growth defects induced by excess WLS. These data suggest that WLS functions as a negative regulator of melanoma proliferation and spontaneous metastasis by activating WNT/β-catenin signalling. Even though WNT/β-catenin signaling is downregulated, malignant melanomas express high levels of WNT ligands. Here, the authors show that reduced expression of the WNT secretory receptor WLS could be the cause of loss of WNT/β-catenin signaling. © 2012 The Authors. Published by John Wiley and Sons, Ltd on behalf of EMBO.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Beta-catenin; Melanoma; Spontaneous metastasis; WNT secretion; WNTLESS

Xanthohumol, a prenylated chalcone derived from hops, inhibits growth and metastasis of melanoma cells - Seitz, Tatjana; Hackl, Christina; Freese, Kim; Dietrich, Peter; Mahli, Abdo; Thasler, Reinhard Manfred; Thasler, Wolfgang Erwin; Lang, Sven Arke; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Cancers, 2021)
Melanoma is one of the most aggressive and lethal cancers worldwide. Despite recent progress in melanoma therapy, the prognosis for metastasized melanoma continues to be poor. Xan-thohumol (XN), a prenylated chalcone derived from hop cones, is known to possess a broad spectrum of chemopreventive and anticancer activities. However, few studies have analyzed functional XN effects on melanoma cells and there have been no previous in vivo studies of its effects on metastasis. The aim of this study was to investigate the impact of XN on the tumorigenic and liver metastatic activity of melanoma cells. XN exhibited dose-dependent cytotoxic effects on human melanoma cell lines (Mel Ju; Mel Im) in vitro. Functional analysis in the subtoxic dose-range revealed that XN dose-dependently inhibited proliferation, colony formation, and migratory activity of melanoma cells. Subtoxic XN doses also induced markers of endoplasmic reticulum stress but inhibited the phosphorylation of the protumorigenic c-Jun N-terminal kinases (JNK). Furthermore, XN effects on hepatic metastasis were analyzed in a syngeneic murine model (splenic injection of murine B16 melanoma cells in C57/BL6 mice). Here, XN significantly reduced the formation of hepatic metastasis. Metastases formed in the liver of XN-treated mice revealed significantly larger areas of central necrosis and lower Ki67 expression scores compared to that of control mice. In conclusion, XN inhibits tumorigenicity of melanoma cells in vitro and significantly reduced hepatic metastasis of melanoma cells in mice. These data, in conjunction with an excellent safety profile that has been confirmed in previous studies, indicate XN as a promising novel agent for the treatment of hepatic (melanoma) metastasis.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Melanoma; Metastasis; Xanthohumol

YBX1 is a modulator of MIA/CD-RAP-dependent chondrogenesis - Schmid, Rainer; Meyer, Katharina; Spang, Rainer; Schittek, Birgit; Bosserhoff, Anja Katrin (PLoS ONE, 2013)
MIA/CD-RAP is a small, secreted protein involved in cartilage differentiation and melanoma progression. We recently revealed that p54 nrb acts as a mediator of MIA/CD-RAP action to promote chondrogenesis and the progression of malignant melanoma. As the molecular mechanism of MIA/CD-RAP action in cartilage has not been defined in detail until now, we aimed to understand the regulation of p54nrb transcription in chondrogenesis. We concentrated on the previously described MIA/CD-RAP-dependent regulatory region in the p54nrb promoter and characterized the transcriptional regulation of p54nrb by MIA/CD-RAP in cartilage. A series of truncated p54nrb promoter constructs and mutagenesis analysis revealed that the transcription factor YBX1, which has not been investigated in chondrogenesis thus far, is the mediator of MIA/CD-RAP dependent activation of p54nrb transcription. A systematic analysis of genes carrying this binding site in their promoter region revealed further potential MIA/CD-RAP-regulated genes that have been implicated in cartilage differentiation. In summary, we described the effects of MIA/CD-RAP on transcriptional regulation in chondrocytes. Understanding the regulation of p54nrb via YBX1 contributes to the understanding of chondrogenesis. Uncovering new downstream effectors that function via the activation of YBX1 supports the important role of MIA/CD-RAP in these processes. © 2013 Schmid et al.
CRIS-Team Scopus Importer:2022-08-05